澳門普通小學教師職業幸福感：: 現況、影響因素及提升策略 = THE OCCUPATIONAL WELL-BEING OF MACAU PRIMARY SCHOOL TEACHERS：CURRENT STATUS, INFLUENCING FACTORS, AND ENHANCEMENT STRATEGIES - 黎嘉穎 (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 教師; 澳門小學; 職業幸福感

HOW DO FOOD INFLUENCERS ON INSTAGRAM AFFECT CONSUMERS’ VISIT INTENTION TO RESTAURANTS IN MACAU? - Ho, Pui I. (University of Saint Joseph, 2023)
This dissertation examines consumers' perceptions of food influencer content on Instagram and the relationship between exposure to food influencer reviews and consumers' intention to visit restaurants in Macau. A mixed-method research design was employed, combining quantitative survey data from 301 responses with qualitative insights from one focus group session involving six participants. The findings suggest that consumers find food influencer content entertaining and inspiring for dining out and exploring new culinary experiences, but they express concerns over its credibility. While food influencer content has a good exposure to consumers, it has a moderate impact on consumers’ restaurant choices, with various factors affecting the relationship. The results highlight the importance of perceived trustworthiness and enjoyability of food influencer content, the visual appeal of food and restaurant environments in photos, and personal relationships in shaping Macau consumers' visit intention to restaurants. The findings can serve as a basis for future research on credibility perceptions of food influencers, the enjoyability of influencer content, and the visual appeal of food and restaurant environments on Instagram. Practically, food influencers should prioritize transparency, authenticity, appealing photos, engaging captions, and leverage the role of personal relationships to increase their impact on consumers' restaurant choices
Keywords: Instagram; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph; food influencers; influencer marketing; social media

VALUE-BASED ADOPTION OF MOLECULAR CHINESE MEDICINE (MCM): AN EXPLORATORY INVESTIGATION - Hong, Chi Kit (University of Saint Joseph, 2023)
The world we live in today is constantly changing, with new technologies and innovations being introduced all the time. Through the continuation and innovation of Chinese medicine theories, scientific research methods, and progress, Traditional Chinese Medicine continues to evolve and develop more innovative Modern Chinese Medicine. In this research, Molecular Chinese Medicine is studied as a new form of Chinese medicine, intended to provide a more pleasant and safe experience for consumers. Thus, the objective of this study is to identify both positive and negative perceptions that contribute to the adoption of innovative technologies and their related products. In order to reach this goal, a robust value-based theoretical model is used. To examine behavioural intentions to adopt Molecular Chinese Medicine (MCM) in Macau, this study combines quantitative and qualitative methods. Thus, a Value-based Acceptance Model (VAM) was used to determine Macau citizens' attitudes towards Molecular Chinese Medicine, including their perceptions of its usefulness, enjoyment, technicality, and perceived fee, in relation to the perceived value of the product, which may ultimately determine adoption intentions. Structural Equation Modeling (SEM) was used to process a sample of 194 Macau residents. The data analysis supported our model's explanatory and predictive power and helped describe the characteristics of the local population. Our results provide insight into the acceptance of innovative products that may be useful in designing more accurate strategies and facilitating the introduction of MCM to Macau and similar markets. It was found that low perceived fees demonstrated a relatively strong positive correlation with potential users' perceived value, whereas usefulness and enjoyment showed a medium-strong positive correlation. Also, a strong positive correlation was found between potential consumers' perception of the value of Molecular Chinese Medicine and their intention to adopt it
Keywords: Molecular Traditional Medicine (MCM); SmartPLS; Technology Adoption; Thesis and Dissertations Master of Business Administration (MBA); Traditional Chinese Medicine (TCM); University of Saint Joseph; Value-based Adoption Model (VAM)

THE POWER OF SCENT MARKETING: INFLUENCING CONSUMERS TO PURCHASE - Fong, Un I. (University of Saint Joseph, 2023)
Examining consumer perceptions of scent marketing in Macau's retail setting is the goal of this study. The study focuses on the following two primary uses of scent marketing in retail environments: subliminal application and application as a component of branding strategy. Qualitative research methodology is used. A total of ten consumer interviews produced the data. The findings show that consumers are in favor of scent marketing's use in retail settings. The use of scent marketing as a tool for establishing brands is preferred, and consumers find this approach to scent marketing to be more acceptable than its subliminal application. Although consumers believe that other factors, such as price, are typically more significant than scent when making purchases, the use of subliminal scents was not always evaluated negatively. Unless occasionally when making an unplanned purchase, consumers do not think that a subliminal scent can significantly impact their purchasing behavior
Keywords: Consumer behavior; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; branding; consumer opinion; marketing strategy; scent marketing; subliminal advertising

Teacher's Teaching Style and the Learning Attitude of Elementary School Students: A Macau Case Study = 小學生學習態度與教師教學風格現況之研究—以澳門某小學為例 - 洪麗 (University of Saint Joseph, 2024)
Keywords: Learning Attitude; Macau; Primary School; Teacher's Teaching Style; Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Externalizing Behaviour in Macao: Gender and Parental Participation - Kuok, Oi Lou (University of Saint Joseph, 2023)
There are gaps in the research on gender differences and parental participation and the interaction between gender and parental participation in non-Western cultural contexts, particularly the Macao context. The current study aims to fill these gaps by examining gender and parental participation (i.e., father only, mother only, or both) differences and interactions in externalizing behaviour (oppositional defiant disorder and conduct disorder) during late childhood and adolescence (i.e., from age 10 to 18) in Macao. The methodological approach for the current study was a cross-sectional design with a quantitative methodology based on self-rated questionnaires. In certain items, we did discover gender differences. More boys than girls appeared to concur that they occasionally misbehave at school or start fires. And it appeared that girls were more likely than boys to concur that they occasionally exhibit unexpected mood or emotion changes and strong tempers. The children in the groups where only the mother or father participated tended to agree more than they prefer to hang out with older kids than kids their own age. This is in contrast to the group with more parental participation, which is represented by both parents submitting the questionnaire. Although none of the hypotheses proposed were supported, our outcomes implied culture and subculture may play important roles on youths’ externalizing behaviour
Keywords: Externalizing behaviour; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; gender; parental participation

FACTORS INFLUENCING BRAND IMAGE AND BEHAVIOR OF CONSUMERS OF THE XIAMEN MARATHON - Xu Teng (University of Saint Joseph, 2024)
Many sports events have been reopened since the recovery from the global Covid19 epidemic. As countries work toward the third sustainable development goal of good health and well-being, sports events have received increasing support and investments. This study focuses on the Xiamen Marathon, which had reached the platinum level of sustainable development and is a benchmark marathon race in China. To assess the factors that influence the brand image and behavior of consumers of the Xiamen Marathon, this dissertation references the conceptual models in previous studies and hypothesizes that experience, brand image, loyalty, satisfaction, motivation, organization, quality, and trust are the direct influencing factors of brand image and indirect determinants of word of mouth, sport, and behavioral intention. This study surveyed participants of the Xiamen Marathon in 2024 and collected data from a sample of 285 participants. All the respondents were local residents and over 90% were contestants. The largest proportions were 36-to-55-year-old, married, highly educated, and employed, earning monthly income between ¥5000 to ¥15000 and spending over ¥1000 on marathon equipment. IBM SPSS and Amos were used for the quantitative analysis based on structural equation modeling techniques, including reliability test, validity test, and hypothesis testing. The questionnaire quality was good, the scale data were suitable for factor analysis, and the questionnaire data fitted well. However, quality and trust were excluded due to low significance. The results show that experience, loyalty, satisfaction, motivation, and organization have significant and positive impacts on brand image, which in turn has significant and positive impacts word of mouth, sport, and behavioral intention. The results support the eight hypotheses of direct effects and the 15 hypotheses of intermediate effects
Keywords: Brand experience; Brand image; Brand loyalty; China; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

探討澳門普通小學教師在融合教育背景下的工作相關壓力及有效應對策略 =: Exploring Work-Related Stress and Effective Coping Strategies in the Context of Inclusive Education Among Mainstream Primary Teachers in Macau - 黃家敏 (University of Saint Joseph, 2024)
Since 2006, the Government of Macau has been promoting inclusive education. This has now been ongoing for seventeen years. As education policies gradually improve, the focus has shifted from students in inclusive settings to the realm of teachers. With an increasing number of inclusive students, the corresponding work pressures faced by teachers has also increased. The aims of this study are to better understand the work-related stress, sources of stress, and subsequent coping strategies used by mainstreamteachers within the inclusive education sector of Macau. This study used qualitative research methods, interviewing twelve frontline teachers from eight different private primary educational institutions. Eight of these teachers work in schools practicing inclusive education, while four were employed in regular schools. However, all twelve participating teachers had experience in teaching inclusive students but also lacked any specialized background in special education. Following and obtaining and meticulously analyzing interview data, supported by relevant literature, the study findings are presented as follows: 1. Views and Attitudes of Regular Teachers in Inclusive Schools towards Inclusive Education The interviewed teachers support the concept of inclusive education but were concerned about student behaviors and their learning challenges. These concerns included inappropriate behaviors, learning disabilities, and the teachers’ own pedagogical demands. In managing student behaviors, teachers found it difficult to handle the emotional control of inclusive students, leading to disruptions in class. Regarding learning, teachers had to use additional and extra time on after-class tutoring, increasing their workload. Teaching inclusive students also complicated the instruction, requiring teachers to undergo additional training and preparation. 2. Work-Related Stress and its Sources among Regular Teachers within Inclusive Schools The participating teachers rated their stress-resilience as not low, but rather they experienced medium to high levels of work-related stress, mainly due to long working hours and extensive workloads. The study identifies four main sources of stress: （i） The nature of work, including extensive teaching and non-teaching tasks, including heavy class management, or multiple roles. （ii） Social relationships, where regular teachers lacked an understanding of resource teachers’ roles, leading to ineffective communication and an underutilization of resource teachers in schools. （iii） Organizational structure, where schools involved in inclusive education required improvements in facilities and teaching environments, particularly in the safety of sports areas. Additionally, not all mainstream teachers had access to inclusive education resources, and the instructional adjustments for inclusive students did not fully meet their needs. （iv） Social aspects, where the public did not fully understand the concepts of inclusive education, and expectations on teachers were excessively high. Furthermore, teachers were dissatisfied with their salaries and benefits, which they felt were not commensurate with their heavy workload. The study also found that female teachers faced additional stress from both work and family responsibilities, as they also bear the burden of caring for and educating their own children at home. 3. Responses and Coping Methods of Regular Teachers in Inclusive Schools to Work-Related Stress The study analyzed the negative impacts of work-related stress on teachers’ physical health, psychological state, and behavior. The impacts included poor sleep quality or insomnia and emotional states of worry and anxiety. In response to stress, teachers engaged in communication and social activities, exercise and rest, and dietary adjustments. However, these stress-relief methods did not effectively address the root causes of the stress, making long-term stress management a crucial issue for teachers. Based on the findings regarding stress perceptions, sources, and coping methods, the researcher proposes recommendations for teachers, educational institutions, and relevant government departments, with an aim to support and aid future policymaking in the area of inclusive education in Macau
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 小學; 工作壓力; 應對策略; 普通教師; 融合教育

Do job satisfaction and supervisory support affect burnout among security guards in Macao? - Leong, Chi Ian (University of Saint Joseph, 2023)
We see security guards around in Macao in our daily lives and they are the ones who are responsible for protecting people’s safety and properties. Most security guards are non-local workers and might have different workplace stress levels. This study’s main aim is to investigate how job satisfaction and supervisory support are related to burnout among security guards in Macao. The research is carried out through a quantitative questionnaire to collect data and deliver it to the local and non-local security guards working in Macao. A total of 132 questionnaires were collected. It is expected that when security guards have higher job satisfaction and more supervisory support, they will experience less burnout. This intention enables the organization to make some changes to help the security guards from burnout due to job dissatisfaction and no supervisory support. The practical implication for reducing stress is introducing training courses such as mindfulness-based stress training programs. Future research will investigate other support like organizational support, peer support, and family and friends support on security guards
Keywords: Burnout; Job satisfaction; Supervisory support; Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

THE VALUATION OF MCDONALD’S CORPORATION (NYSE: MCD) - Lao, Hong U. (University of Saint Joseph, 2023)
This paper analyses the valuation of McDonald's Corporation (MCD) as of December 31, 2021. An estimate of the Company's intrinsic value will also be provided. In addition, the internal company factors and external market conditions influencing company valuations and share prices will be discussed. The study has two main objectives: Determine the intrinsic value of McDonald's common stock as of December 31, 2021, and compare it to the actual stock market price on the same date. An assessment of the stock’s market price should represent the Company's true value on that day. Research can then verify whether it was overvalued or undervalued on that day. Identify internal company factors and external market environment factors that affect the Company's operations. This information will be used to gain a deeper understanding of the sensitivity analysis results. Possible scenarios will be discussed to reflect how these factors stimulate macroeconomic, industry, and business developments, as well as the strategic responses of industry players or competitors. McDonald's possible strategic responses to these scenarios will also be assessed. In this paper, a combination of qualitative and quantitative research methods will be employed. Data collection and analyses in Chapters 2 to 5 will use a qualitative approach, which includes data related to McDonald's, industry, and economic analyses. Chapters 5 to 8 will apply qualitative and quantitative data collection and analysis methods. Data will be collected from McDonald's annual report for the fiscal year from December 2017 to December 2021
Keywords: Intrinsic Value; McDonald's; Sensitivity Analysis; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; Valuation

EVALUATION OF MANGROVE BLUE CARBON AS A POTENTIAL FOR CLIMATE CHANGE MITIGATION IN MACAU - Lao, Hio Wai (University of Saint Joseph, 2023)
Climate change is a global issue but its impact can be felt locally. Macau SAR has been rapidly developing since the single shift towards a gaming industry-dominated economy, the overwhelming anthropogenic activities contributing to increasing pollution. Mangroves, which play an essential role as the blue carbon system with a high carbon sequestration rate could be a natural base solution to the pollution. This study aims to determine 1) the total organic Carbon (TOC) in the soil of Macau mangrove sites, 2) comparison with the methodology evaluating the organic Carbon, and 3) organic Carbon comparison between Macau and other regions. Soil sampling were processed under the Blue Carbon Initiative guideline, and the samples were divided into two parts for determining the TOC%, combustion method from Hong Kong, and methodology of ashing in our laboratory. The overall estimated TOC% of Macau mangrove sites was 1.29%. There are still a lot of potentials in Carbon storage and for climate change mitigation in Macau
Keywords: Carbon sequestration; Mangroves; Master of Environmental Sciences and Management (MESM); University of Saint Joseph; blue Carbon

Gender Differentiated Parenting and Family Characteristics Affecting Parent-Adolescent Relationship in Macao: Che Iok Seng a.k.a Matthew - Che, Iok Seng (University of Saint Joseph, 2023)
This study aims to investigate gender-differentiated parenting and the factors that affect parent-adolescent relationships in Macao families. The study will address the following research questions: A) Does gender-differentiated parenting exist in Macao families? B) How does the academic level of parents relate to conflict resolution and acceptance levels? C) How does the length of time parents have lived together relate to conflict resolution and acceptance levels? D) How does the sibling position of adolescents relate to conflict resolution and acceptance levels? The study employed a quantitative research approach with a purposive and convenient sample of parents with children aged between 12 to 18 years old in Macao. The data were collected using the Parent-Child Interaction Questionnaire—Revised-Parent version (PACHIQ-R-P) through a questionnaire survey from May to August 2022. Out of the 172 completed questionnaires, seven were invalid, resulting in 165 valid questionnaires. The findings showed that gender differentiation in parenting was confirmed, with significant results showing that fathers had lower acceptance and conflict resolution levels when their child was a boy. Mothers showed similar acceptance and conflict resolution levels regardless of their child's gender. Furthermore, the study found that parents' acceptance of their children was influenced by their academic level, length of time living together, and the child's sibling position. This study is the first of its kind in Macao and could provide valuable insights for family and adolescent services in the region
Keywords: Adolescents; Conflict Resolution; Gender differences; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Effect of Empathy on Relationship Satisfaction in Young Adult Lovers in Macau: The Role of Love Maintenance Behaviors - 黎志濠 (University of Saint Joseph, 2024)
The purpose of this study was to explore the correlation between empathy, love maintenance behaviors, relationship satisfaction in a convenience sample of young adult lovers in Macau. Participants were N = 183 (84 males, 99 females) recruited from the social media platform (e.g. Instagram, WeChat, Facebook). Firstly, young adult lovers who tended to have high relationship satisfaction and empathy are tended to use positive love maintenance behaviors but less likely to use negative love maintenance behaviors. Besides, there were differences found by gender in empathy (affective empathy & total empathy), some dimensions of positive love maintenance behaviors (openness & advice), and negative love maintenance behaviors (causing jealousy, destructive conflict & negative love maintenance behaviors in general). Lastly, the findings in this study supported the hypotheses that love maintenance behaviors mediated the relationship between relationship satisfaction and empathy among young adult lovers in Macau. It was revealed that there was higher satisfaction in younger adult lovers in younger group (18-24 years) compared to older groups (32-40 years). For empathy, it correlated positively with relationship satisfaction and most positive love maintenance behaviors, but also with certain negative love maintenance behaviors. Positive love maintenance behaviors mediate the relationship between relationship satisfaction and empathy, highlighting their critical role in maintaining healthy relationships
Keywords: Love maintenance behaviors; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; empathy; relationship satisfaction

THE RELATIONSHIP BETWEEN PARENTING STYLES, ACADEMIC ACHIEVEMENT AND BEHAVIORAL PROBLEMS OF PRIMARY STUDENTS IN MACAO - Tang, I. Sam (University of Saint Joseph, 2023)
"Parenting styles may have various effects on children’s development and educational outcomes, particularly a relationship with behavioral problems and academic achievement. This study examines the relationship of between parenting styles, behavioral problems and academic achievement. A cross-sectional and questionnaire-design (Parenting Style Scale (Saunders et al., 2013); Strength and Difficulties Questionnaire (Goodman & Goodman, 2009; Goodman, 1999; Goodman, 1997)) study was used with a sample total of 98 parents with the eldest child of the family aged between six to twelve. Results of the findings are mainly inconsistent with the majority of literature. Indulgent and authoritative parenting are the predominant parenting styles, yet parenting styles does not relate to academic achievement. On the other hand, the correlation between behavioral problems, specifically prosocial behaviors and academic achievement are moderate. Furthermore, there is no difference between the type of behavioral problems according to gender. In further studies, a larger sample size, teachers and students as informants, and the inclusion of the analysis of other factors that could be influencing parenting styles, behavioral problems and academic achievement are suggested to be considered. "
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

THE RELATIONSHIP BETWEEN INTERNALISING PROBLEMS, ACADEMIC ACHIEVEMENT, SCHOOL ADAPTATION, AND GENDER, AS VIEWED FROM THE PERSPECTIVES OF BOTH TEACHERS AND STUDENTS - Ao, Hoi Ian (University of Saint Joseph, 2023)
The present study aimed to analyse the differences in the internalising problems (anxiety, depression, somatic complaints), assessed by different informants (teachers and students), according to the level of academic achievement and school adaptation level in secondary students. Furthermore, we examine the gender difference in the level of internalising symptoms. Finally, we analyzed the differences between teacher-rated and adolescents' self-reported internalising symptoms. The Achenbach System of Empirically Based Assessment (ASEBA) was used for collecting informants’ data. The sample consisted of 882 secondary students (349 males and 473 females), while 50 came from public schools and 772 from private schools. No significant differences are found in internalising problems according to the level of academic achievement from both teachers’ and students’ perspectives. Generally, students who are well-adapted to the school context have the least symptoms of internalising problems compared to average and less-adapted groups from the teachers' perspective. In addition, from students’ perspectives, adolescent females present more internalising problems than males. Finally, teachers rated fewer internalising problems when compared to the students. In conclusion, the low level of awareness of teachers towards the internalising problems of students arouse attention. It is suggested that teachers should attend professional development programs in order to address to students’ internalising problems
Keywords: Internalising problems; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; academic achievement; gender differences; school adaptation

A Financial Valuation of Starbucks (SBUX) - Lok, Ka Ian (University of Saint Joseph, 2023)
Starbucks Corporation (hereinafter “Starbucks” or “the Company”) is a worldwide coffee retailer, which operates over 33,000 stores located in over 83 countries nowadays. The purpose of the study is to estimate Starbucks’ intrinsic value as of December 31, 2021 and identify whether the Company was overvalued or undervalued. Several analyses give investors and shareholders an insight into how the Company may develop or identify the ability to generate positive returns from investing in Starbucks. This study is mainly separated into two aspects. The first part specifically discusses the Company overview, industry analysis, and economic outlook, which includes SWOT analysis, PESTEL analysis, Porter's five forces analysis, and value chain analysis to identify external and internal factors that may influence the Company. The second part focuses on financial analyzes, including both historical and forecasted financial statement. Three valuation models and a sensitive analysis are applied to understand the Company’s financial conditions and performance. Starbucks’ intrinsic value is derived from the three discounted cash flow models, indicating the market overvalued the Company’s stock price as of December 31, 2021. Finally, investors and shareholders can understand more about Starbucks’ capital structure, financial highlights, and intrinsic value, because this set of information is critical for existing investors and potential investors to make investment decisions
Keywords: Starbucks; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; financial valuation; value valuation

EXPERIENCING THE PRESENT AND EXPLORING THE FUTURE WITH IMMERSIVE TECHNOLOGIES CASE STUDY: " ST. LAZARUS CHURCH PEDESTRIAN STREET", MACAU - Zhou RenWei (University of Saint Joseph, 2024)
In the present world, many cities have historical and culturally rich districts, but protectionism or economic reasons have slowed their development. Therefore, how to generate more value for these areas is crucial for a city with a deep and complex history. Using immersive virtual reality technology can help solve this problem, and this paper takes Macau's famous historical district as an entry point and starts from the perspective of the general public to explore and design some of the existing buildings and public areas in the district. The focus of this study is to explore the future development possibilities of historical and cultural districts in cities and experience the current situation of the district. Specifically, by studying the historical background and human investigation of ST. LAZARUS CHURCH PEDESTRIAN STREET (Chinese official name: 疯堂斜巷), the study uses immersive virtual reality technology to first create a scene of the existing building group in the district as a stage of protection for historical buildings. Then, it creates and presents a future building group scene in the district, which includes completed buildings and public area facilities after renovation and sustainable design. This renovation does not destroy the protected historical buildings at all, but is a protective exploration. The researchers used 3D computer graphics software (Blender) and virtual tour software (Kuula) to create the design, and users can freely explore the scene by ""walking"" virtually. The design includes two groups of architectural scenes of the ST. LAZARUS CHURCH PEDESTRIAN STREET in the present and the future. After entering the scene, users can freely switch between the present and the future time points to experience the different architectural scene atmospheres. Users can enter some buildings and public areas, and interact with objects in the scene to generate visual or auditory introductions to the target. Users can see the rough outline of the future historical and cultural district after the protective development in the free exploration of the virtual reality environment, which can inspire further public thinking about the development of historical and cultural street areas in the city. Users can explore and experience the project using professional virtual reality equipment or directly on the web. By using immersive virtual reality technology, the public can have a more intuitive and comprehensive understanding of the future development of historical and cultural street areas, and urban planners, professional architects, and clients of architectural design can all benefit from this technology, especially in the initial conceptual design and prototype design of buildings
Keywords: Conservation of historical building; Exploratory design; Reconstruction of historic district; Thesis and Dissertations Master of Design (MDG); University of Saint Joseph; Virtual reality technology

EXPLORING MACAU SECONDARY SCHOOL TEACHERS’ UNDERSTANDING, PROFESSIONAL SKILLS, AND CHALLENGES TO INCLUSIVE EDUCATION OF STUDENTS WITH DISABILITIES/SPECIAL EDUCATION NEEDS - Sin, Sam I. (University of Saint Joseph, 2024)
Quality inclusive education creates educational opportunities for all students to achieve enhanced educational outcomes, and the quality of inclusive teaching depends on teachers’ knowledge, skills, resources and school support. However, not all schools are implementing inclusive education well enough to cater to the learning needs of students with special educational needs. This phenomenological case study explored the perspectives and experiences of five teachers in one inclusive secondary school in Macau. An Interpretative Phenomenological Analysis (IPA) of the in-depth semi- structured interview data revealed four themes: varied conceptualisations of inclusive education, professional training in inclusive practice, professional knowledge and practice experiences, and challenges to implementing inclusive education. Generally, while the teachers demonstrated awareness and some understanding of inclusive education, they also expressed the need for more knowledge and skills to implement inclusive education effectively in their schools. Additionally, they referred to time pressure, workload and insufficient professional development as impeding their personal processes of evolving inclusive teaching in their school. Recommendations were made considering Booth and Ainscow's (2002) Index of Inclusion to enable effective development and practice of inclusive education in the Macau secondary school and extend this to other schools
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; students with special education needs; teachers' professional skills; teachers' understanding

學以致用中文課程（演講）對疑似中文資優學生中文素養提升之研究 ——以澳門某中學高中學生為例 =: A Study On The Improvement Of Chinese Literacy Of Suspected Gifted Chinese Students In The Course Of Learning-to-Use Chinese (Speech) -- Taking Senior High School Students Of A Middle School In Macau As An Example - O, Chi Wa (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 中文素養; 學以致用中文課程; 演講; 疑似中文資優; 資優教育

EXPLORING THE IMPACTS ON MENTAL WELL-BEING OF UNIVERSITY STUDENTS UNDER COVID-19 PANDEMIC. A QUALITATIVE STUDY - Sit Chin Pok (University of Saint Joseph, 2024)
Coronavirus disease (COVID-19) is a public health emergency happening worldwide. It brought tremendous impacts to the global economy and people’s mental health (Jiaqi Xiong et al., 2020). Many people suffered physically and psychologically with the sudden arrival of COVID-19. Among the different age groups, studies identified that undergraduate students as a vulnerable group with a higher risk of mental health problems, such as depression and anxiety (Silva et al., 2022; King et al., 2022; Mansor & Ahmad, 2022). This qualitative study collected data from six focus group interviews with undergraduate students studying in Macao. Thematic analysis was used to understand the COVID-19 impact on students' mental well-being and coping strategies, as well as to explore the protective and risk factors that contribute to students’ mental well-being in the local context of Macao. Results showed four themes with 15 contributory sub-themes: COVID-19’s impact on students’ mental well-being, key impacting sources, coping strategies, and risk and protective factors. This study provides a picture of the mental health condition of undergraduate students during the zero-COVID period in Macao and raises an urgent call for extra attention to university students’ mental health during crises, showing the social and mental needs of undergraduates. This research also uniquely contributes insight into how the dysfunctionality of families could be a significant risk factor for students’ mental health during the crisis, which is rarely found in other COVID-19 studies. This research suggests a promotion of future programs or workshops that would strengthen and benefits students’ relationship with their family. Future research could explore the family function in Macao and its relationship with students’ mental well-being
Keywords: Mental Well-being; Qualitative; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); Undergraduate Student; University of Saint Joseph

The Spread of Buddhism in Japan and The Spirit of Japanese Tea Ceremony - Rosa, Alfredo Augusto da (University of Saint Joseph, 2023)
Buddhism was founded by Shakyamuni, and this religion has appeared in opposition to Brahmanism's caste system since its inception. Shakyamuni emphasized the important concept of “all beings are equal” from the very beginning. Buddhism spread from India to other regions, and was introduced to China through Central Asia. In China, Buddhism merged the two native cultures of Confucianism and Taoism and finally produced the socalled Chinese Buddhism. Buddhism and its value of equality were also developed and extended in China, and finally spread to Japan. After Buddhism was spread to Japan, it developed rapidly due to official support. Different Buddhist sects have established their own temples in Japan, and among them, Zen Buddhism has the greatest influence among all social classes in this country. Later, after years of development, Zen Buddhism penetrated into many aspects of Japanese culture, such as religion, aesthetics, garden design, samurai spirit and tea ceremony. With the spread of Zen Buddhism, the core value of Buddhism which is “Buddhist concept of equality” was also spread to Japan. The tea ceremony is precisely the place where this value of equality can be detected. This dissertation explains the many processes that reflect this value no matter inside or outside the tea room, and argues that the spirit of the tea ceremony is to pursue the value of equality
Keywords: Buddhism; Equality; Tea Ceremony; Thesis and Dissertations Master of Philosophy (MPH); University of Saint Joseph

澳門小學普通班教師實施融合教育的教學困擾與因應策略之研究 =: A STUDY ON TEACHING DIFFICULTIES AND RESPONSE STRATEGIES OF TEACHERS IMPLEMENTING INTEGRATED EDUCATION IN ORDINARY CLASSES OF PRIMARY SCHOOLS IN MACAO - Ng, Wa Seng (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 因應策略; 小學普通班教師; 教學策略; 澳門

LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE INFLUENCE ON EMPLOYEES’ ORGANIZATIONAL COMMITMENT UNDER THE PANDEMIC SITUATION - Sun Leung, Wai Chai (University of Saint Joseph, 2023)
The aim of this study is to investigate the influence of leadership styles and organizational cultures to employee’s organizational commitment under the pandemic situation in Macao. The dependent variables comprise of the three dimensions of organizational commitment. Among those three, affective commitment and continuance commitment are considered to be analyzed in this study. The leadership styles concept and organizational cultures are applied as the independent variables. The objectives are achieved using quantitative research method with questionnaires in Likert scale scores. The two significance reveals that laissez-faire leadership style had a positive relationship with continuance organizational commitment (H4) and innovative culture had a positive correlation with continuance organization commitment (H6). Such outcomes were extended to a qualitative study with qualitative approach on discourse analysis to explore the potential factor and a leadership discourse analysis was initiated. While the findings on influence of leadership and culture on organizational commitment is not a major concern for Macao employees in the pandemic situation, the significance of specific leadership style and culture rationalizes the transformation and status of Macao employees’ views towards leadership and employers’ perspective on organizational culture. The data collected in this study may also provide valuable resources for future study and training programs for the coming batch of employees in the coming new phase of Macao in entering the 2nd round of gaming licensing. Create the right leadership and culture for the organization to bring back the passion of Macao employees
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

SenSwave: DRAW YOUR MUSIC BY EXPLORING THE RELATIONSHIP BETWEEN MUSIC, IMAGES, AND EMOTIONS - He, Minghao (University of Saint Joseph, 2024)
According to research, it is found that images, music, and emotions are closely related, and integrating visual and tactile elements into the music creation process, combined with auditory experience, can enhance emotional expression and understandability. The results highlight the potential of tangible interfaces in autonomous music creation and promoting emotional well-being. This work aims to explore the intersection of music creation, emotional expression, and technological innovation by creating a unique tangible interface for music. It does this by combining the challenges presented by the complexity of modern music production, the emotional issues faced by today's youth, and bringing a new way of expression to the phonograph technology. It hopes to draw inspiration from the historical significance of the phonograph through visual expression, user experience, and algorithmic music generation technology, and seek to provide a new way of music creation for young people who are creative and curious but not musicians, and provide a new way to express emotions. All things considered, the project demonstrates the feasibility and effectiveness of combining historical inspiration with modern technology to create innovative solutions for music technology. Furthermore, it is focusing on enhancing the interface design even more and carrying out longitudinal research to assess the long-term effects on emotional expressiveness and user experience. It is also being explored as an artistic installation, hoping to bring more changes and presentation methods and provide users with a more comprehensive and immersive music creation and emotional expression experience
Keywords: Artificial Intelligence; Interaction design; Interdisciplinary; Music generation; Tangible interface; Thesis and Dissertations Master of Design (MDG); University of Saint Joseph; Well-being Emotional expression

FACTORS THAT INFLUENCE MACAO EMPLOYEES’ DECISION TO PARTICIPATE IN CORPORATE VOLUNTEERING ACTIVITIES: FROM THE SOCIAL IDENTITY THEORY PERSPECTIVE - Cheong, Ieng (University of Saint Joseph, 2024)
This dissertation aims to shed light on the factors derived from employee identity that contribute to corporate volunteering participation. The study explores the influence of perceived organizational support (POS), group cohesion, perceived volunteering meaningfulness, and transformational leadership on engagement in corporate volunteering activities. The study employed a correlational quantitative design, collecting data through a questionnaire survey. The findings reveal that POS and group cohesion positively impact corporate volunteering, with volunteering meaningfulness mediating these relationships. Transformational leadership moderates the effect of volunteering meaningfulness on the relationship between POS and corporate volunteering. This research adds to the literature on identity and corporate volunteering by establishing a connection between employee identity and engagement in corporate volunteering activities. It emphasizes the importance of volunteering meaningfulness as a key factor in this relationship, highlighting the positive influence of POS and group cohesion. By considering both POS and group cohesion as antecedents, this study offers new insights into the understanding of identity and corporate volunteering. Practically, organizations can enhance employee participation in corporate volunteering by cultivating a supportive work environment, showing care for employees' well-being, and recognizing their contributions. Promoting group cohesion through effective communication of organizational goals can increase employee identification and motivation for volunteering. Emphasizing the personal significance of corporate volunteering and highlighting its impact can boost employees' intrinsic motivation and sense of purpose. To implement successful corporate volunteer programs, organizations should provide support and appreciation for employees' efforts, utilize transformational leadership to inspire commitment, and consistently reinforce the value of corporate volunteering. The practical implications of this research provide guidance for organizations seeking effective implementation of corporate volunteer programs as part of their corporate social responsibility strategies. It also holds relevance for researchers interested in exploring the intersection of employee identity and corporate volunteering
Keywords: Corporate Volunteering; Group Cohesion; Mediator; Moderator; POS; Perceived Organizational Support; SIT; Social Identity Theory; Thesis and Dissertations Master of Organisational Psychology (MOP); Transformational Leadership; University of Saint Joseph; Volunteering Meaningfulness

SINGERS' ONLINE MARKETING STRATEGIES IN GUANGDONG PROVINCE: HOW TO ESTABLISH AND MAINTAIN A STRONG ONLINE PRESENCE FOR EFFECTIVE MUSIC PROMOTION AND FAN ENGAGEMENT - Feng, Qiuyuan (University of Saint Joseph, 2024)
Previous research has explored the development of online music and singers in Guangdong Province; however, there is a gap in understanding how singers establish and maintain a strong online presence through effective online marketing strategies. To fill this gap, this study employs a mixed-methods approach to deeply investigate how Guangdong singers leverage digital platforms for effective music promotion and fan engagement. Online questionnaires were distributed via Xiaohongshu and WeChat, collecting 153 valid responses from fans, which were analyzed to understand interaction methods and their impact on singers. Additionally, semi-structured interviews were conducted with three Guangdong singers and one music company employee, and the interview data were thoroughly analyzed.The findings indicate that Guangdong singers utilize specific social media platforms (such as TikTok) to create and share personalized content and establish direct interactions with fans. These strategies are crucial for successful music promotion and fan engagement. In the highly competitive online music market, adopting such targeted digital marketing strategies allows singers to significantly enhance their visibility and fan engagement. This approach not only holds significant importance for the personal development of singers in Guangdong but also has far-reaching implications for the prosperity of the music industry and the creative economy as a whole
Keywords: Guangdong singer; Internet influence; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph; audience engagement; music promotion; online marketing; singer fans

澳門小學中文科基本學力要求的實施現況研究: 個案研究 - 鄧樂怡 (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Study of Tesla's Marketing Strategy in the Chinese Market - Xian Wenhao (University of Saint Joseph, 2024)
This study assesses Tesla's marketing strategies and their effectiveness in the Chinese market. Given Tesla's leading position in the global electric vehicle sector and the importance of the Chinese market, this study aims to analyze in-depth how Tesla has succeeded in China with its unique marketing tactics, and to suggest improvements to enhance its competitiveness. By utilizing analytical tools such as PEST, Porter's Five Forces Model, SWOT, and STP, this study comprehensively evaluates Tesla's marketing environment and thoroughly analyzes its marketing mix of products, prices, channels, promotions, etc., combined with consumer feedback and market research data. The study reveals that the key factors for Tesla's success include innovative design, unique branding, effective marketing strategies and digital marketing applications. Nevertheless, Tesla still needs to face the challenges of localization, pricing strategy, channel adjustment and promotion innovation. In order to maintain its leading position, Tesla should continue to innovate, strengthen its localization strategy, improve service quality, and adapt to policy changes. The optimization suggestions proposed in this study will help Tesla overcome challenges and achieve sustained growth, and they will also provide valuable references for other new energy vehicle companies
Keywords: China; Marketing evaluation; Marketing strategy; Tesla; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploring the Problems and Strategy Use by Primary School Teachers in Conducting Classroom Management Under the Policies of Inclusive Education in Macau =: 探討澳門融合教育政策下小學老師面對班級經營的困難及策略 - Lam Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

CHARACTERIZARION OF ENVIRONMENTAL NOISE IN MACAO S.A.R. OVER THE PAST DECADE: IMPLICATIONS FOR NOISE POLLUTION MANAGEMENT - Deng, Ziyang (University of Saint Joseph, 2023)
With the rapid urban development, Macao SAR has become one of regions with the with highest population density in the world, characterized by high traffic flow and dense building aggregations. Noise has become one of the major environmental problems in Macao. Besides having an impact on human health and wellbeing, noise pollution is known to impact ecological systems and the image of a place. Before proposing a plan to reduce noise pollution, it is necessary to have a general understanding of the current noise levels in Macao, how they have changed over time and the main noise pollution sources and environmental concerns. This dissertation relies on the publicly available data from DSPA (Macao Environmental Protection Bureau) monitoring stations concerning noise levels over the past decade. The main research goals were: 1) Characterize changes in noise levels from 2010 to 2021 during daytime, nighttime, and full-day from multiple noise stations located in Macao, Taipa, and Coloane Peninsula; and 2) associate changes in noise levels with potential factors such as location, number of residents/tourists, number of vehicles, among others. This work provides an important framework for future studies concerning noise monitoring and mitigation strategies
Keywords: Environmental policies; Legislation; Master of Environmental Sciences and Management (MESM); Noise management; Noise pollution; University of Saint Joseph; mitigation

FLIIP: AN INTERACTIVE MULTIFUNCTIONAL TABLE DESIGN FOR PRESCHOOLERS - Tang, Qinghua (University of Saint Joseph, 2024)
With the rapid development of China's social economy, attention to children's education is also increasing. Among them, the preschool stage, the starting point of children's education, is the primary stage of children's cognitive, emotional, social, and motor skills development. At this critical time, providing children with an age-appropriate educational environment can significantly affect their personal growth, intellectual development, and emotional cultivation. Therefore, a multifunctional table that can meet the learning needs of preschool children and promote early cognitive development is essential. This work takes preschool children as the user object of our study to deeply explore the needs and obstacles of the target users. It summarizes the requirements and principles of children's furniture design based on children's physiological and psychological characteristics. A design scheme of an intelligent multifunctional preschool children's table is proposed based on ergonomics and digital technology. The objective through this work, is to create a preschool children's table that not only meets the learning needs of preschool children but also promote fun and can encourage the development of children's early cognitive ability
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph; children's furniture; interactive; multifunctional; preschool children; preschool children's table

Exploring Interactive Wearable: Enhancing Emotional Release and Expression in Modern Fashion Design - Zhai, Jingwen (University of Saint Joseph, 2024)
As technology evolves swiftly and consumers call for more customization, the study of interactive fashion design is increasingly emerging as a key topic within the fashion industry. The goal of this research is to investigate merging intelligent technology with apparel design, realizing functional enlargements and enriching the user experience by employing interactive design. Initially, this document examines key theories and ongoing studies in interaction design, intelligent textiles, and wearable tech, pinpointing the current research voids and difficulties. This section then presents a range of methodologies used in the study, encompassing literature review, case analysis, and interviews with experts, to thoroughly analyze and assess all facets of interactive apparel design. This document suggests a methodical design of interactive clothing, outlining the entire process from initial design to the creation of prototypes. The practicality and efficiency of the design methodology are proven by creating prototypes and conducting trials. Findings from the experiments indicate that interactive attire offers substantial benefits in terms of functionality, comfort, and user experience. The research offers both theoretical backing and pragmatic advice for designing interactive attire, while also highlighting paths for upcoming advancements in fashion technology. In conclusion, the document examines the shortcomings of the existing research and potential research paths, aiming to offer valuable guidance for advancing the development of clothing styling and wearable tech
Keywords: Fashion design; Thesis and Dissertations Master of Design (MDG); University of Saint Joseph; clothing interactive devices; emotion and perception; emotional user experience; interactive design

Resale value of used electric vehicles-based on consumer perception in Zhuhai area - Lu, Yueying (University of Saint Joseph, 2024)
China leads in global automobile production and sales, but fuel vehicle usage causes energy crisis and pollution. Electric vehicles, as energy-saving and environmentally friendly transportation, can alleviate urban ecological pressure and reduce dependence on non-renewable energy. Development of electric vehicles is thus prioritized. However, the current electric vehicle market is immature and faces slow growth due to various constraints. Despite state policies, market performance lags, and consumer acceptance is low, leading to a mismatch between praise and sales. Therefore, exploring factors influencing consumer demand and purchase intention for electric vehicles is crucial. This paper focuses on consumer perceived value to study factors affecting second-hand electric vehicle resale value, offering practical relevance and value. Consumer behavior theory suggests that consumers' purchase decisions hinge on their perception of a product. Consumer perception involves a subjective, overall evaluation of a product or service based on usage purposes and needs, and an analysis of relevant information from various channels. For used electric vehicles, perception includes understanding of appearance, function, cost, and performance.This study aims to analyze factors affecting the resale value of used EVs and explore consumers' perception of this value. Guided by consumer perception, the study conducted a literature review-based comprehensive analysis and qualitative exploration of used EV resale value. The findings reveal that price, battery performance, endurance, environmental protection, and safety significantly impact the resale value of used EVs. Finally, combined with the research conclusions of this paper, management suggestions are put forward, and countermeasures are summarized from the two levels of government and second-hand electric vehicle marketing enterprises
Keywords: Resale value of used electric vehicles; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; Zhuhai area; consumer perception

COMMUNITY INVOLVEMENT IN CRISIS MANAGEMENT: A CASE STUDY OF MACAO ‘s PANDEMIC MANAGEMENT DURING THE COVID-19 - Ng Pui Weng (University of Saint Joseph, 2024)
The aim of this study is to analyze the crisis management of Macao SAR and the extent to which the community were engaged in the COVID-19 pandemic prevention and control. There are some issues found that when the pandemic breaks out and after outbreaks, such as poor information communication, low efficiency of prevention and control work, unsatisfactory compliance of the public, lack of pandemic prevention materials which affect the government's control of the pandemic in the past study. In Macao SAR, densely residential areas and dense population are the main considerations for pandemic prevention and control. Communities, as the main first line of defense for pandemic prevention and control, are also the bridge for communication between the government and the residents. The community have the advantages of timely and accurate information collection and accurate implementation of prevention and control measures. In this study found that the involvement of the Macao community may not be the key to the success of epidemic prevention in Macao. Community participation also faces many challenges, such as uneven distribution of facilities and services, lack of medical expertise of community workers, shortage of manpower and other shortcomings of community participation. It is possible that the Macao community is not playing a key role in the COVID-19 pandemic prevention and control. Given this scenario, the government needs to give full play to social forces and the role of the community in pandemic prevention and control. Currently, there are few studies on community involvement in COVID-19 prevention and control. Through COVID-19, this study puts forward some ideas that the government needs to pay attention to community development and improve citizens' community awareness to promote the Macao community. Improving the Macao community is conducive to Macao in the future crisis and community cooperation
Keywords: Digital Finance; Digital Financial Infrastructure; Greater Bay Area; Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

An Investigation In The Theory And Boundaries Of The Firm And Their Possible Application To Public Institutions - Leong, Victor (University of Saint Joseph, 2024)
Industrial organization, theory of the firm and boundaries of the firm are well established fields of study involved in the size, structure and scope of a corporate entity (i.e. firm) to the market. However, a key characteristic of corporate entities is that economic concerns (costs and profit) is the overriding or dominant factor. This paper attempts to apply the above mentioned concepts to organizations such as public institutions where economic concerns are secondary considerations, to seek a more objective analysis on what the structure and scope of such organizations should be
Keywords: Hamiltonian Formulation; Theory of the Firm; Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Exploring the learning effectiveness under the "formative assessment" reform of non-tertiary education in Macao: A Case Study =探討澳門非高等教育改革「形成性評核」下的學習成效－個案研究 - 何愛琴 (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 個案研究; 學習成效; 形成性評核; 教育改革

Transitional Spaces of a Community Center in Macau - Lin, Yanzi (University of Saint Joseph, 2024)
In a fast-paced and densely populated city, community activity centers can provide a social place for residents. This thesis is a study of this promise of social life for a new urban development in Macau. Community centers play an important role in promoting community cohesion and resident participation. Yet, public space for Macau residents is increasingly unable to meet growing and diversified needs. In what ways can the development of activity centers improve the quality of life of residents? Can transitional spaces between different functional areas in community centers play a more effective role in promoting social interaction within the community? The principal tasks of this thesis are as follows: (1) an in-depth examination of the impact of shared transitional spaces on the overall design of community activity centers, (2) a discussion of transitional spaces in community centers in terms of the functional efficiency of these centers and the interactive experience of users, and (3) articulation of principles and recommendations for the design of transitional spaces in community centers. Overall, this thesis argues that, by designing efficient and user-friendly shared transitional spaces, architects can better serve the community and its users, and foster a closer connection between architecture, people, and communities
Keywords: Community Centers; Social Interaction; Social Space; Theses and Dissertations Master of Architecture (MARCH); Transitional Spaces; University of Saint Joseph

FLOWING PATH: SPORTS CENTER AS SOCIAL CONNECTOR - Xin, Ziyan (University of Saint Joseph, 2024)
In the age of the information society, the prominence of internet communication and social media has meant that the role of face-to-face encounters in public life has been diminished. This trend has been exacerbated by public health concerns in the aftermath of the COVID pandemic. The social role of architecture and its contribution to the sustainability of interpersonal relationships has become a significant issue for architects. As a place to accommodate sporting activities and social space in the community, sports centers play an important role in promoting social cohesion and interaction. This is the focal topic of the present thesis. The principal tasks of this thesis are as follows: (1) This thesis collects and studies relevant literature on sports centers as social spaces. A special emphasis is placed on discussions of social spaces. The intention is to articulate design characteristics of community sports centers that merit further exploration. (2) This thesis selects three representative sports facilities as case studies and considers how they promote the formation of social bonds and interactions. The thesis offers a review of design ideas, planning strategies and specific methods of implementation. (3) This thesis takes the design project for a sports center in New District A in Macau as an example, and puts forward a design strategy of ""vertical intensification + shared application"". This strategy aims to promote the integration of the sports center with the urban environment, while creating a flexible public space that can adapt to the needs of spontaneous and social activities. The intention is to make the sports center a place that promotes community interaction and connectivity. Overall, this thesis argues that community sports centers can become important places to promote social interaction through well-designed architectural space. Specific design factors and strategies explored in this thesis provide useful points of reference for architects. Through on-going processes of optimization and innovation, sports centers can better serve the community of Macau
Keywords: Circulation strategies in architecture; Theses and Dissertations Master of Architecture (MARCH); University of Saint Joseph; integrated sports facilities; social connectors; sports centers

A CONTEMPORARY VENUE FOR TRADITIONAL CANTONESE OPERA IN MACAO - Li, Zebin (University of Saint Joseph, 2024)
Cantonese opera has a long and profound history and has evolved over 700 years, making it unique and distinctive. In a diversified media and entertainment, Cantonese opera culture in Macao, like many other aspects of traditional Chinese cultures, is facing a general decline. Specific challenges include loss of audience, the decline and disintegration of professional groups, and reduced scope of the active repertoire. How can a new venue for traditional Cantonese opera promote a positive response to the contemporary challenges that threaten its cultural vitality? How can a new design approach respond to local issues and contemporary architectural production? Can programmatic diversification of a performance venue (cultural exchange, art display, education) be a useful strategy? This thesis consists of five parts. Part 1 of this thesis outlines the background of research, describes the purpose and significance of the research, and deal with issues of research method. Part 2 considers the artistic characteristics of Cantonese opera, including the spatial characteristics of traditional Cantonese opera theatres, the characteristics of Cantonese opera costumes, and the changing characteristics forms of performance. Part 3 is focused on the uses of parametric models in architectural design. Part 4 offers three case studies of opera houses in China, the Guangzhou Opera House, the Harbin Grand Theatre, and the Xiqu Centre in Hong Kong. Part 5, the core of this thesis, proposes a design of a new performance venue for Cantonese Opera House in Macao. Overall, this thesis offers an account of main considerations in the transformation process from traditional Cantonese opera venues to modern Cantonese opera houses and situates these considerations in the context of contemporary discussions of parametric architecture
Keywords: Architectural Parametric; Cultural Characteristics of Cantonese Opera; Design of Cantonese Opera House in Macao; Modern Opera House Design; Theses and Dissertations Master of Architecture (MARCH); University of Saint Joseph

THE MARKET AS SOCIAL LANDSCAPE IN MACAU - Ma, Jianjun (University of Saint Joseph, 2024)
Markets in Macau are not merely places for commercial retail, they are also social spaces. As a centre of communal life, markets are of great significance to the lives of Macau residents. However, with the rise of supermarkets and online shopping, the role of traditional markets has been reduced. At the same time, the messy and unkempt nature of traditional markets has become a negative factor of their social viability. The result has been a downward spiral of poor operation, decline in rental yield and loss of customers. Can the markets be revitalized for Macau residents? Can the social attributes of markets be reactivated? How can the experience of markets be re-imagined for different user groups? The present thesis is organized into 5 parts. The first part deals with the background of research. It also describes the purpose and significance of the research and discusses research methodology. The second part details market pressures in Macau, including insufficient land and space resources, poor sanitary environment, and tourism promotion needs. The third part examines the idea of “walkable cities” in terms of four concerns—usefulness, safety, comfort, and spatial interest—and in terms of specific case studies. The fourth part concerns a design project for a market at ZONE A in Macau. The thesis details the needs of a market in this zone and considers them in the light of the idea of walkable cities. Overall, this thesis attempts to contribute to public discussion of the future of markets in Macau in terms of service, socialisation and promotion
Keywords: Markets in Macau; Social Spaces; Theses and Dissertations Master of Architecture (MARCH); University of Saint Joseph; Walkable Cities

ARTIFICIAL INTELLIGENCE (AI) GENERATED ART & VISUAL COMMUNICATION: ITS EFFECTS ON HUMANS' IMAGINATION, CREATIVITY, COMMUNICATION, AND CULTURE - Cheong, Weng Chim (University of Saint Joseph, 2024)
Technological advancements have enabled machines to offer more efficient assistance to people across several domains. Art and creativity are what distinguish people or societies the most. The arrival of AI has caused a fresh wave of concern among many of us; it is crucial that we evaluate the weight of the positives and the drawbacks of how people employing these technologies will influence societies. Legislation is frequently delayed because of the various revolutions througout history. Along with the difficulties raised in the continuing debate, it is critical to identify a route or alternative to assist existing challenges for artists. This dissertation includes our case studies, analysis, and conclusions, which explain the effects on imagination, creativity, communication, and culture when individuals use AI technologies to create art or/and images. According to our findings, AI technology should be considered as one way to solve problems. The vast majority of created outputs are unable to accomplish the desired reach. Furthermore, even if the ethical issues cannot be resolved, individuals should not ignore it and keep their moral compass. Importantly, we must realise that individuals should always be involved in and influence the intricacies and components of the creative process. However, it is commonly understood that the deployment of artificial intelligence has an influence on people’s communication and societies. There are still no standards, frameworks, or norms on this front of Ai-generated images. This might contribute to an increase in industrial imbalance and discrimination. As a result, to safeguard our individuality, we must take the initiative to uncover any answers or directions that would aid in this scenario. As with any experience, whether internal or external, we should use it to our advantage to apply our creative process, something the computer cannot accomplish. Still, it gives many benefits and is effective in assisting people in completing challenging tasks, so it is smart not to avoid teamwork. Furthermore, because social media and the internet provide powerful expression and communication tools, their advantages should help build universal rules to safeguard artistic work
Keywords: AI-generated art; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph; communication; creativity; culture; imagination

Evaluating the Acceptance of Portuguese Residents Towards Chinese Electric Vehicles: the Role of the Country-of-Origin Effect - Xian, Si Tong (University of Saint Joseph, 2023)
This study identifies Portuguese residents’ behavioural intention towards Chinese electric vehicles from the perspective of the Country-of-Origin Effect (COE) and uses the Unified Theory of Acceptance and Use of Technology 2 (UTAUT-2) as a guide to design interview questions. According to the existing literature, UTAUT-2, a comprehensive technology acceptance model, has not been used to assess the Portuguese electric vehicle market, and no relevant research has been found to apply the method of combining the COE into the UTAUT-2 framework. The purpose of this study is exploratory in nature, it uses qualitative methods to identify the behavioural intention of Portuguese residents towards the acceptance of Chinese electric vehicles. Data from 16 Portuguese residents was collected through semi-structured interviews and analyzed with qualitative methodology. The study found that factors such as performance expectations, environmental concerns, effort expectations, hedonic motivation, and social influence have a positive impact on Portuguese residents' purchase of electric vehicles, while price value, habits, and convenience conditions have a neutral or negative impact. Regarding COE, apart from social influence, it has no impact on other factors. To increase the popularity and sales of Chinese electric vehicles in Portugal, it is recommended that advertising and marketing efforts focus on price, charging services, after-sales service, and design
Keywords: Consumer Behavior; Country of Origin Effect; Electric Vehicles; Environmental Awareness; Portugal; Sustainability; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Park-meter: Designing an Innovative Macau System - Cheang, Chi Tat (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

Study on User Acceptance on Customer Behavior for Online Payment in Macau: MPAY Case Study - Wong, Chi Cheng (University of Saint Joseph, 2023)
With the rapid expansion of mobile e-commerce, an increasing number of businesses have jumped into the fray in all facets of the mobile electric commerce industry chain. The payment link is the most competitive. From the norm in the sector to the consumer market, telecom operator rivalry, as well as third-party payment between different companies, never ceases. In the context of mobile e-commerce, however, competition has shifted from traditional product-centered to customer- centered, and business success frequently rests on the customer. As a result, the competition in the mobile e-commerce payment industry is essentially about competing for users. Mpay is characteristic of mobile e-commerce payment firm representatives; on the basis of theoretical analysis, combined with the reality of the economic background, the study chose Mpay mobile payment users as research subjects and analyzed the major variables of user acceptability. The model was built on the basis of an extensive evaluation of past research results of user acceptance model and reference to UTAUT model. The model considered performance expectancy, effort expectancy, and social influence, facilitating condition as independent variables determining user behavior intention, Based on the conceptual model, the paper conducted an empirical investigation as a case study of a Mpay mobile payment user using data from a questionnaire, while also conducting a separate discussion of the impact of perceived risk and trust on user acceptance. The empirical results indicate that for mobile payment users, performance expectancy has the greatest positive effect on behavior intention, while facilitating conditions, social influence, perceived risk, effort expectancy, and trust have no effect. In addition, gender and age were discovered to influence user acceptance
Keywords: Online mobile payment; SmartPLS; Thesis and Dissertations Master of Business Administration (MBA); UTAUT model; University of Saint Joseph; user acceptance

ENVIRONMENTAL, SOCIAL AND GOVERNANCE (ESG) PRACTICES IN THE MACAU SMALL AND MEDIUM-SIZED ENTERPRISES (SMES): A STUDY OF THE RESTAURANT INDUSTRY - Fong Wai Man (University of Saint Joseph, 2024)
This research used a qualitative approach to explore the environmental, social, and governance (ESG) practices implemented by SME restaurants in Macau. In-depth interviews were conducted with eight (8) SME restaurant owners and managers to understand their ESG initiatives and their challenges. Key findings include: Environmental Initiatives: Many restaurants have adopted practices such as limiting plastic use, better food management, and organic waste recycling, often driven by government regulations rather than broader ESG considerations. Community Engagement and Social Responsibility: Social practices are less adopted, with some restaurants collaborating with charities, hiring individuals with disabilities, and donating food. However, most do not make monetary donations or engage in sponsorship activities due to financial concerns rather than a lack of consumer trust. Governance Initiatives: Restaurants have adopted electronic workflows, risk management practices, and stakeholder management approaches, including a flexible approach to employee management focused on operational efficiency rather than investor attraction. The findings indicate that for SME restaurants, the key drivers for ESG implementation are more focused on factors such as cost-savings and operational efficiency rather than broader considerations around investor interest or consumer trust. This study provides insights into how SME restaurants integrate ESG elements into their operations
Keywords: Environmental; Small and Medium Enterprises (SMEs); Social, and Governance (ESG); Sustainable Practices; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Feasibility Study on the R&D and Production of VOCs Environmental Protection Equipment - Chen Le Qi (University of Saint Joseph, 2024)
This study focuses on China's volatile organic compound treatment industry and deeply analyzes the current situation, challenges, and development trends of the volatile organic compound environmental protection industry. This study discusses technological advancements in reducing VOC emissions, environmental regulations' impact, and market demand changes. The market size, growth potential, and primary driving factors were analyzed by studying the business scope and competitive advantages of VOC management companies. Predict the company's operational status, investment return rate, and other related financial data through financial analysis. Finally, emphasis was placed on technological innovation, market positioning, and risk management while pointing out the industry's principal risks and response strategies. The research findings indicate that, in the context of increasing environmental awareness and policy support, China's VOC ecological protection industry has enormous growth potential. The company is expected to achieve significant success in both business and finance through technological innovation and market adaptation. The research and production of VOC environmental protection equipment is feasible
Keywords: China; Equipment; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; VOCs

The Effects of Distributive Justice, Perceived Organizational Support, Job Satisfaction and Caring Climate on Insurance Agents’ Turnover Intention: Mediating role of Affective Commitment and Its’ Implication For Insurance Company Management - Chan, Wang Cheong (University of Saint Joseph, 2023)
The insurance companies in Macau are potentially facing a crisis of high turnover rates, exacerbated by the limited studies conducted on the insurance industry to address this issue, as the gaming and travel industries are currently experiencing a significant demand for human resources due to economic recovery. In light of this, a study was conducted to better understand the attitudes of 105 currently employed insurance agents in Macau insurance companies, specifically their commitment and thoughts of staying or leaving their employers. The study examined several independent variables (distributive justice, perceived organizational support (POS), job satisfaction, and caring climate) in relation to insurance agents’ turnover intention and the role of affective commitment. The aim was to determine the association between these variables and turnover intentions among insurance agents. The snowballing methodology was employed to effectively engage with the insurance agents and gain insights into their perspectives. The results of the statistical analysis revealed positive correlations between all independent variables and affective commitment. Job satisfaction and POS were identified as strong positive predictors. Additionally, mediated regression analyses demonstrated that affective commitment significantly mediated the relationship between all independent variables and turnover intention. Finally, the study provides implications for insurance company management to address and reduce the high turnover rate. Furthermore, the importance of future orientation is further discussed
Keywords: Affective commitment; Distributive justice; Insurance company; Thesis and Dissertations Master of Organisational Psychology (MOP); Turnover intention; University of Saint Joseph

IMPACTS OF CHINA’S ENTRY ON THE PRODUCT LINE RIVALRY IN THE GLOBAL CIVIL AIRCRAFT INDUSTRY - Chen, Yawen (University of Saint Joseph, 2024)
As international tourism continues to flourish and airlines are eager to expand their fleets, the demand for civil aircraft has continues to grow in the global market. The market has been a duopolistic one, shared by Boeing and Airbus. However, the recent entry of the Chinese company, Comac, had the potential to turn it into a triopoly within certain segment of the product line. This observation motivates the research objective to analyze the impact of Comac's entry on the production strategies of the incumbents. Specifically, this dissertation studies the impact on each firm’s allocation of production capacity toward different civil aircraft in the product line in response to how Comac’s entry, which can also impact the effects of capacity increase and market expansion on the product line rivalry. This dissertation is based on a multi-product, oligopolistic model of Boeing and Airbus. To provide insights on the strategy and behavior of each firm in the evolving competitive environment, this dissertation solves and extends the mathematical model to incorporate Comac as the entrant and compares model results with data of orders and deliveries of the three companies in the past 15 years. This model finds that when Comac's C919, a relatively small plane, enters the global civil aircraft market, Boeing and Airbus will increase the production of their small planes and decrease the production of the relatively large planes under the production capacity constraints. If the production capacity increases, both Boeing and Airbus will produce more planes, but will allocate more additional capacity to large planes than to small planes compared to the duopolistic competitive environment. When the market demand increases, despite the entry of the C919, Boeing and Airbus iv will continue to increase the production of both large and small planes, but the response is greater to an increase of demand for large planes than that for small planes. The orders and deliveries data provide some but insufficient support for the model predictions. As the market participation of Comac continues to grow, future researchers can re-assess the models’ propositions with more available data
Keywords: Capacity allocation; Civil aircraft; Comac; Duopoly; Oligopoly; Product line rivalry; Thesis and Dissertations Master of Business Administration (MBA); Triopoly; University of Saint Joseph

RELATIONSHIP BETWEEN PSYCHOLOGICAL CONTRACT FULFILLMENT, WORK ENGAGEMENT AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR, AND ABUSIVE SUPERVISION OF EMPLOYEES IN MACAU SIX GAMING AND INTEGRATED RESORTS - U, Weng Ian (University of Saint Joseph, 2024)
In Macau, gaming is a pillar industry. The job performance of the employees is a determining factor for gaming and integrated resorts’ ability to improve their competitiveness in an evolving environment. Therefore, organizational behavior is an important topic for gaming and integrated resorts. In view of social exchange theory, this study takes the employees of the six gaming and integrated resorts in Macau as sampling. The study would be overviewing how psychological contract fulfillment affects their organizational citizenship behavior in the organization, and relationship between work engagement and their abusive supervision in the six gaming and integrated resorts employees in the Macau gaming and related industry. This study takes psychological contract fulfillment as the independent variable, organizational citizenship behavior as the dependent variable, work engagement as the mediating variable, abusive supervision as the moderating variable. Data was collected through random online questionnaire research method and 257 valid questionnaires were obtained. SPSS statistical software applied for reliability and validity analysis, Pearson correlation and regression analysis. The conclusions are listed in following: (1) Psychological contract fulfillment has a partial positive impact on organizational citizenship behavior ; (2) Psychological contract fulfillment has a partial positive impact on work engagement; (3) Work engagement has a positive impact on organizational citizenship behavior; (4) Work engagement has a positive mediating effect between psychological contract fulfillment and organizational citizenship behavior; (5) Abusive supervision has no moderating effect between psychological contract fulfillment and work engagement; (6) Abusive supervision has no moderating effect between work engagement and organizational citizenship behavior
Keywords: Abusive Supervision; Organizational Citizenship Behavior; Psychological Contract Fulfillment; Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph; Work Engagement

A STUDY OF PATTERNS OF CONSUMPTION OF THE NEW GENERATION of Macao - Wang, JiaBao (University of Saint Joseph, 2024)
The increasing contribution of Generation Z (Gen Z) to Macao’s economy may be the driving force behind the recent changes in Macao’s consumption patterns. This dissertation analyzes how consumption patterns of Macao’s Gen Z differ from other generations. To investigate the types of goods and services consumed, the shopping modes, and the factors that influence the consumption decisions of different generations of Macao, this study conducts a survey to collect primary quantitative data from 296 Macao residents. This study found that the most Macao residents consumed 21%-60% of their income, showing a balance between consumption and saving. They spent most on food and non-alcoholic beverages, healthcare, and education. In terms of receiving information about new products, many Macao consumers learned from family and friends and social media, such as the Red Book and TikTok. Electronic payments have become increasingly popular, such as the local payment system, MPay. The t tests for statistically significant differences show that Gen Z was more likely to make online purchases when buying beauty products and electronic devices than other generations. Compared to other generations, Gen Z was more concerned with the level of fun of the brand, impacts on the environment, society, and local community of the product, personal preference and research, and the recommendations of online reviewers, influencers, and salesperson. Based on the findings of this study, businesses can develop up-to-date marketing strategies to introduce their products to different generations in Macao
Keywords: Consumption pattern; Generation Z; Macao; Millennial; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Food Waste Management In Macau: Assessing Public Awareness, Recycling Facilities, And Policy Implementations In Comparative Perspective - Hoi, Hang Ian (University of Saint Joseph, 2023)
Food waste has become an increasingly pressing issue worldwide, and Macau is no exception. A substantial portion of municipal solid waste in Macau is comprised of organic waste, with household food waste being a significant contributor. This can be attributed to households purchasing excessive food, preparing more than necessary, or not consuming items before they spoil, leading to detrimental resource and environmental impacts, particularly in the form of greenhouse gas emissions. It is crucial for Macau to develop a sustainable food waste management system that fosters prevention and responsible consumption and to develop food waste recycling habits among its residents. This study employed a two-pronged approach: a literature review of food waste source separation policies and practices in four neighboring regions to identify adaptable good practice examples for Macau, and a questionnaire survey completed by 143 local residents. The survey aimed to comprehend residents' behaviors and awareness regarding food waste prevention and treatment, evaluate their satisfaction with Macau's existing food waste recycling program, examine their resistance and motivation toward participating in the recycling program, and assess their attitudes toward implementing a polluter-pays-principle system in Macau. The survey aimed to provide insights into the current state of household food waste in Macau and inform future waste management policies and strategies of stakeholders. The survey findings highlight the need for enhanced public awareness and education on food waste prevention. Additionally, upgrading recycling facilities may encourage residents to participate more actively in food waste recycling. Ultimately, implementing suitable policies can help prevent food loss and waste and regulate food waste generation and elevate recycling rates. This study offers preliminary recommendations for policymakers or government entities as a orientation for future planning
Keywords: Food Loss and Waste (FLW); Food Waste Hierarchy; Food Waste Management; Food Waste Separation; Sustainable Development Goals (SDGs); Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

METAVERSE: A STUDY OF CONSUMER PERSPETIVE IN MACAU - Chan, Vanda Cardoso (University of Saint Joseph, 2023)
Technology is an essential and valuable tool nowadays. New technology and innovations are introduced to the public day by day. Metaverse will be a new trend, as the Macau government has been trying to promote this technology since the COVID-19 pandemic is still here. Before this technology goes deeply to the public, this paper attempts to examine the consumer’s perspective of Metaverse and understand the cognition of Macau people about Metaverse. And bring out what factors and conditions will make them accept this technology. A qualitative research method will address the questions and problem to understand consumer perspectives towards this technology. Entrepreneurs, managers, and professionals will be invited to take part in this research. Ten interviews will be carried out in this research for data analysis, which may provide a board overview of this technology in Macau and give recommendations to local entrepreneurs. In conclusion, consumers think it is still not a well-developed technology and is not globally used at this stage. In contrast, if this technology is ready-to-use, it will be a helpful assistant in their businesses. They expect the metaverse to be fully developed in ten or more years
Keywords: Consumer perspective; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; augmented reality; extended reality; marketing strategy; virtual reality

Variational Approaches and Mathematical Models for Food Waste Management - Leong, Mei Kei (University of Saint Joseph, 2024)
The global food industry generates substantial waste, posing significant environmental, economic, and social challenges. This dissertation explores circular business strategies for food waste management, aiming to develop an efficient model that integrates circular economy principles and innovative technologies. Key research questions include: What are current food waste management practices? How can circular economy principles reduce food waste effectively? What role can technology play in improving these systems? The study also examines barriers to implementation and identifies gaps in existing literature. The methodology involves a comprehensive literature review, case studies, and the development of a detailed mathematical model. The literature review covers circular economy concepts, current food waste treatment technologies, machine learning and Al applications in waste management. Case studies from various countries provide insights into regulatory frameworks and innovative solutions. Central to this research is the mathematical modelling of food waste management systems. The model employs Hamiltonian and/or Lagrangian formulations to optimise waste transportation and processing. This approach allows for the simulation of various scenarios, helping to identify the most efficient pathways for food waste reduction and resource recovery. The model also incorporates phase transitions better to understand the dynamics of waste generation and treatment processes. Phase transitions mark changes on tendencies and in this case they help us to evaluate the viability of the construction of a fast track for the transportation of food waste in any city. Results indicate that adopting circular economy principles in food waste management is feasible and beneficial. Effective strategies include bioplastics, insectutilisation, and machine learning models for waste prediction and management. The developed mathematical model suggests efficient waste transportation through a coupled network approach, ensuring rapid and effective waste evacuation. The research highlights the importance of technological integration and cross-sector collaboration for sustainable food waste management. It also stresses the need for robust regulatory frameworks and consumer education to drive behavioural changes and support circular practices
Keywords: Circular Economy; Consumer behaviour; Environmental; Food Waste Management; Machine Learning and Artificial Intelligence; Quantum Mechanics; Social and Governance (ESG) principles; Sustainable Business Strategies; Thesis and Dissertations Master of Business Administration (MBA); Transportation Mathematical Modeling; University of Saint Joseph

將CRA教學法融入澳門小學融合班數學課程 之行動研究-以二年級兩位數減法單元為例 =: An Action Study of Integrating Concrete-to-Representational-to-Abstract (CRA) into the Mathematics Learning of Integrated Classes in Macao Primary Schools - Taking the Two-digit Subtraction Unit of Grade 2 as an Example Concrete-to-Representational-to-Abstract (CRA) - Zhuang, YanYan (University of Saint Joseph, 2023)
Keywords: CRA教學策略; Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 兩位數减法; 小學數學課程; 融合生; 行動研究

Experience the Past in the Present with Immersive Technologies Case Study: “The Old Ladies’ House”, Albergue, Macau - Chang, Tin Lan (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

SLEEP PROBLEMS IN MACAU CHILDREN AND ADOLESCENTS: ASSOCIATION WITH BEHAVIOURAL PROBLEMS AND ACADEMIC PERFORMANCE - Hio, Sam U. (University of Saint Joseph, 2024)
The adverse impact of sleep problems on children and adolescents’ health and development raises concern in the community. Although some studies have examined the association of sleep problems with behavioural problems and academic performance, few have been done in Macau, especially for the children population and regarding academic performance. Hence, the primary purpose of the present study was to identify sleep problems of children and adolescents in Macau and explore its relationship with behavioural problems and academic performance. 948 participants (466 children and 482 adolescents) from Macau were included in the study. Data was collected using the Achenbach System of Empirically Based Assessment (ASEBA) forms: CBCL, TRF and YSR. Children sleep problems were assessed by the reports of mother and father, in addition self-report was also included to measure adolescents sleep problems. Behavioural problems were reported by mother, father and teacher for children, as well as self-report for adolescents. Academic performance was the average of teacher’s rating of all academic subjects. The prevalence of sleep problems was 10.1% in children and 17.4% in adolescents. The results showed significant difference between children’s sleep problems and their mother and father-reported total behavioural problems, but not with teacher-reported total behavioural problems. However, whereas the t-test found that adolescent’s sleep problems significantly predicted all informants reported total behavioural problems, the chi-square test found no significant relationship between the two factors in teacher’s ratings, suggesting that while adolescents who had more sleep problems did show a higher frequency of total behavioural problems in the teacher’s perspective, but they may not be severe enough to be considered clinical. In addition, significant association between academic performance and sleep problems were only observed in children but not in adolescents; and no significant relationship was found between sleep problems and grade retention. Findings provided further support for some associations of sleep problems with behavioural problems and academic performance. In general, the findings of Macau were similar to those in other countries. Given that chronic sleep problems create multiple negative consequences to students’ lives, practical implications are provided to help lower it through the collaboration between parties, education about sleep hygiene and the development of healthy sleeping habits. Keywords: sleep problems; behavioural problems; academic performance; children; adolescents
Keywords: Macau; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; academic performance; adolescents; behavioural problems; sleep problems

基模教學對百分比問題之程序流暢程度的有效性研究 =: EFFECTIVENESS OF SCHEMA-BASED INSTRUCTION (SBI) ON PROCEDURAL FLUENCY WITH PERCENTAGES PROBLEMS - Zhou, Mingyan (University of Saint Joseph, 2024)
Research suggested that students struggle because of lacking understanding of basic concepts, formulas, and procedures in algebra, leading to inefficiency in logical thinking and problem-solving skills. (Julius et al., 2018; Jupri et al., 2021). Schemabased instruction (SBI) aims to enhance learning and problem-solving by activating and building upon students' prior knowledge structures, known as schemas (Powell et al., 2008). The common schemas include the total, difference, change, equal groups, comparison, ratios/proportions (Hughes & Cuevas, 2020). SBI has been found to be effective, particularly for students who struggle with mathematics word problems (Marshall, 2012; Hughes & Cuevas, 2020). Research related to SBI has not yet been conducted in Macau region. An early pre-test was administered by the researcher, thirty-one students were asked to solve 10 questions about percentages. The results showed that some students lacked the fundamental knowledge needed to investigate and explore the abstract ideas, patterns, and relationships in percentages problems. A daily schema-based instruction (SBI) as a part of an experimental intervention study was implemented, pre-test and post-tests were administered to investigate the effect of SBI on students' mathematical procedural fluency skills. Thirty-one students from the researcher’s class were invited to engaged in 40 minutes of daily SBI lessons for two weeks, 12 lessons in total. During each of the twelve 40-minute session, students practiced schemas to develop procedural fluency competencies, such as solid number sense and arithmetic operations, to solve percentages problems. Within-group descriptive and inferential statistics were adopted. The results indicated that after SBI, students can solve mathematical problems with greater procedural fluency. This research shares implications and provides suggestions regarding SBI and procedural fluency
Keywords: SBI; Thesis and Dissertations Master of Education (MED); University of Saint Joseph; mathematics; percentages problems; procedural fluency; schema-based instruction; secondary education

THE IMPORTANCE OF VISUAL ELEMENTS IN BRAND COMMUNICATION IN MACAU CASE STUDY: DESIGN OF CULTURAL AND CREATIVE PRODUCTS - Long, On Nei (University of Saint Joseph, 2024)
The research highlights the significance of souvenirs in contributing to the preservation of cultural heritage and communicating cultural messages to tourists. However, a need for more study exists on the visual elements and brand communication employed in designing cultural and creative products that represent local culture. This research aims to investigate the cultural and creative products industry's status and identify the essential visual elements for designing Macau's cultural and creative products. The study also seeks to understand the visual elements and communication strategies that significantly influence product design and brand communication while capturing the image and style of Macau. The research collected 265 valid questionnaires from online participants and interviewed four designers from small local artist brands. The analysis revealed that local consumers prefer products from small local artist brands, but there needs to be a higher brand awareness. Respondents suggested that utilising social media platforms would effectively increase brand awareness and engage with consumers. Furthermore, it was found that Macau's cultural and creative products can integrate various local elements and design styles to represent its unique style. These visual elements are deemed adequate for cultural and creative product design. This research contributes to the creative and tourism industries by providing designers and scholars with insights and references to better comprehend visual and brand communication for local small artist brands
Keywords: Brand Communication; Cultural and Creative Products; Images of Macau; Souvenirs; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Investigating the influence of Instagram on the local foodservice sector in Macau: A Consumers' Perspective - Mac, Hoi Kuan (University of Saint Joseph, 2023)
Nowadays marketers and practitioners recognize the importance of social marketing as a strategy to acquire customers. Accordingly, the enterprises and brands are embracing the use of social network in communicating with potential consumers ad actual consumers, in order its performance so as to increase its sales. Among all those social media platforms, Instagram is one of the platforms which is image orientated and can easily connect with users and provide information with photos and images. As Macau is small‐sized city where there are abundant small to medium‐sized enterprises, the local small firms are switching their marketing strategies by utilizing the Instagram to promote their product online. In order to get a better grasp of how Instagram affects the promotion of the food and beverage product in Macau, the research question has been formulated: “To what extend can the local food sectors in Macau use Instagram as a marketing tool to engage purchasing intention and strengthen their brand equity? From the perspective of customers.” Semi‐structured interviews were conducted with 13 participants who are the Instagram users, with diverse situations of engagement on Instagram. According to the interviews, participants expressed that how Instagram can associate effects with arousal and brand equity (brand awareness, brand image, perceived quality and brand loyalty) and formation of purchase intention eventually through the Instagram marketing activities. The results showed that Instagram marketing activities strongly correlated the brand equity (brand awareness, brand image, and perceived quality while which in turn led to purchasing intention towards the brand. This research comprehensively illustrates the influences of Instagram marketing activities on customer‐based brand equity. The findings of this study will enable local food brands to more accurately forecast the future purchasing behaviors of their customers through Instagram marketing activities and provide a guide in managing brand equity as well
Keywords: Brand Equity; Instagram; Purchase Intention; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

COPING WITH WAR TRAUMATIC EXPERIENCES: CHRISTIAN AND MUSLIM PERSPECTIVES IN EAST TIMOR - Costa, Julieta da (University of Saint Joseph, 2024)
The researcher aims to understand how Christian and Muslim communities in East Timor cope with and recover from trauma arising from war, violence, and conflict. The research seeks to identify critical spiritual and religious coping mechanisms as present in East Timor (Timor Leste) that could help victims heal and reconstruct their lives after a war trauma experience. The study uses a mixed method, first deploying a quantitative investigation of Christian and Muslim communities in East Timor. The questionnaire aimsto understand how religion and spirituality feature in individuals' coping with trauma and the healing practices prescribed or encouraged by religious institutions and practices. In addition, a qualitative research and thematic analyses have been conducted and added with the facilitation of 6 Interviewees, 3 Muslims, and 3 Christians. This study aimed to investigate trauma levels and religious coping strategies among participants from East Timor. The quantitative findings indicated that the participants experienced a moderate level of trauma, with trouble sleeping being the most significant symptom. The qualitative findings revealed in some participants a high level of traumatic experiences. Recurrent thoughts of traumatic events and feeling jumpy were also prevalent. However, feeling strange around people or objects and feeling personally damaged by the trauma were less common. Regarding coping strategies, participants tended to rely on positive religious coping, seeking a stronger viii connection with God, finding comfort in religious communities and beliefs, and using spiritual interventions to manage emotions and worries, finding healing and a path toward the future. Both Catholics and Muslims employed positive religious coping strategies, with Catholics showing a slightly higher level in their utilization. However, the difference between the two groups was minimal. Positive coping strategies were more frequently used by participants from both religious backgrounds, highlighting their importance in dealing with trauma. Positive religious coping did not significantly impact trauma symptoms, showing no decrease or increase. However, a notable positive correlation existed between negative religious coping and more severe trauma symptoms. Individuals relying on negative coping strategies were more likely to experience heightened trauma symptoms. These findings align with previous research, emphasizing the positive association between Islamic appraisals and religious coping with better post-traumatic adjustment, while trauma-related appraisals are linked to worse adjustment. The study underscores the need to respect individual coping variations and recognizes the impact of negative religious coping on trauma experiences
Keywords: COPING STRATEGIES; COUNSELING; EAST-TIMOR; RELIGION; SPIRITUALITY; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; WAR

Walking with John: the go-along as ethnographic tool to explore the lives of adolescents with autism spectrum disorder - Gnanaraj, Steffi (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

IMPACTS OF CARBON TRADING SYSTEM ON GREEN FINANCE: Ziyan Yin - Yin, Ziyan (University of Saint Joseph, 2024)
Against the backdrop of escalating global climate change and China being the world’s largest carbon emitter, this study explores the impact of the carbon trading system on green finance in Chinese power sector. This study uses a quantitative research method, namely a difference-in-differences (DID) model, to investigate power companies that participated or had the potential to participate in carbon trading in 2019 and 2022. The key finding is that companies that participated in carbon trading had significantly higher green finance than those that did not participate, indicating that the carbon trading system has a positive impact on promoting green finance. However, the impact does not significantly intensify after the national carbon trading scheme was implemented in mid-2021. The green finance of listed companies and state-owned enterprises were less affected by carbon trading, possibly because these companies rely on alternative financing options and government financial support. Due to the findings, this study recommends that policy makers should strengthen the promotion of the carbon trading scheme and provide more support for non-listed companies and non-state-owned enterprises. At the same time, the companies should actively participate in the carbon market to take advantage of the industrial policies to enhance green finance, and ultimately promote environmental protection and their own sustainable development
Keywords: Carbon trading scheme; Carbon trading system; China; DiD; Difference-in-difference; Green finance; Power companies; Power plants; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

NEUROCINEMATIC: WALTER MURCH’S VIDEO EDITING PROCESS AND FILM SOUND DESIGN CASE STUDY - Nyögéri, José (University of Saint Joseph, 2024)
This dissertation examines the enduring influence of Walter Murch's seminal editing principles and techniques on contemporary film editors, highlighting how his ideas continue to shape the craft even among those who may not be directly aware of his work. Central to this study is an exploration of Murch's ""Rule of Six,"" which prioritizes emotion, story, rhythm, eye-trace, two-dimensional plane of the screen, and three-dimensional space of action in editing decisions. Additionally, the research delves into Murch's concepts of rhythm and pacing, as well as his emphasis on preserving the emotional impact of a scene. Through a series of in-depth interviews with working editors, this dissertation investigates the extent to which Murch's theoretical framework is manifested in modern editing practices. The study seeks to identify how contemporary editors incorporate these principles into their workflows, consciously or subconsciously, and how these techniques contribute to the narrative and emotional effectiveness of their films. By analyzing the practical decision-making processes of today's editors, this research aims to uncover the degree to which Murch's legacy endures in the film industry. The findings underscore the significant, yet often implicit, role that Murch's editing philosophy plays in shaping the aesthetic and emotional resonance of contemporary cinema. This dissertation thus provides a comprehensive understanding of the lasting impact of Walter Murch's contributions to the art and science of film editing
Keywords: Neurocinematic; Sound Design; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph; Video Editing; Walter Murch

DEVISING THE IMPACT OF THE FEMALE PERSPECTIVE IN THE GAME DESIGN - Luo, Min (University of Saint Joseph, 2024)
Within the realm of video games, female characters often become ensnared in stereotypes, thus becoming objects of the male gaze. Moreover, the neglect of female characters' subjectivity in game design reflects a failure to acknowledge their agency. Additionally, the female perspective is frequently disregarded in game design. These issues have had adverse effects, leading to designs that are less hospitable to women, perpetuating misogyny, sexual harassment, and discrimination in online gaming, and further marginalizing women within the gaming industry. Integrating feminist principles into video game design has the potential to dismantle the cultural center of inequality within gaming culture and foster a more diverse and inclusive video game world, brimming with possibilities. This research investigates such phenomena through a blend of questionnaires and online interviews. Following data refinement and summarization, it explores the potential fusion of feminism and game design. While findings from these studies aid in establishing a framework for this synthesis, feminist game research presents complexity. The study offers pertinent references aimed at advancing the field
Keywords: Female Characters; Feminism; Game Design; Stereotypes; Thesis and Dissertations Master of Design (MDG); University of Saint Joseph; Video Games; Women

Exploring the Impact of the Metaverse on Macau's Fashion Industry Development - Chan, Ka I. (University of Saint Joseph, 2024)
The emergence of the virtual world through social media, technical advancements, digital fashion, and the concept of the Metaverse begs the question of whether Macau's fashion sector can transfer to the virtual sphere. Macau fashion designers have different needs for virtual fashion vs traditional fashion manifestations. The designer's experience, Macau residents' interest in the virtual world and metaverse, and communication inside the metaverse all play an important role in this study. This research study shows our design work, analysis, and conclusions, which explain the concepts and research incorporating the Metaverse virtual platform, virtual characters, user interaction for various target groups, and survey feedback. This detailed research provides a deeper understanding and insights into the Metaverse concept's usefulness in marketing Macau fashion businesses and providing essential information to local Macau fashion designers, fashion industry experts, and Macau people. According to preliminary investigation, utilising avatars and virtual fashion in the virtual world is a novel and promising way for fashion brand operations and expansion. This technique provides cost savings, endless creative options, and effective brand messaging, with the opportunity to predict future virtual fashion trends while keeping a real retail presence
Keywords: Communication; Digital Fashion; Macau's Fashion Industry; Metaverse; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph; Virtual World

ONLINE IMPULSE BUYING BEHAVIOR: A STUDY OF MACAU CONSUMERS - Cheong, I. Lam (University of Saint Joseph, 2023)
Due to the expansion of the Internet and advancements in technology, e-commerce has been frequently and widely used nowadays. The popularity of online shopping continues to develop and become increasingly common, yet, the concept of impulsive buying has consistently drawn significant attention over the years. In order to fit into the current shopping trend, recognizing the needs and wants of online shoppers as well as providing appropriate approaches are essential tasks for companies to achieve. The question of how to attract consumers to make purchases has been a concern for a long time, and in fact, it is necessary to explore consumers’ online purchase decisions in relation to their impulse buying behavior. In accordance with current academic knowledge, the main objective of this study is to investigate factors that influence consumers' online impulsive buying behavior based on external stimuli (such as sales promotions and websites characteristics) and the elements of marketing mix strategy (product, price, place, and promotion). According to the analysis, the promotion strategy has been identified as the most significant influence on consumers’ decision to make an online impulsive purchase. Therefore, the findings from this study are beneficial for companies and marketers to build a framework in order to develop suitable and effective strategies in order to encourage and stimulate consumers' desire for purchases. Furthermore, the research applies the qualitative methodology by conducting semi-structured interviews with 11 consumers who have previously experienced an online impulse buying
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; e-commerce; external stimuli; marketing mix strategy; online impulse buying; online shopping

Perceptions of Sports Agents in a Small Territory: The Case of Macao - Deng, Hao You (University of Saint Joseph, 2024)
This study aims to investigate the difficulties and challenges faced by sports agents in the development of Macao, as well as the feasibility of the emergence of this industry in Macao. Since there is a lack of research on sports agents and related sectors in Macao, this study analyses the current environment of Macao's sports industry and tries to explore the development of sports tourism projects in Macao as an industrial upgrading and transformation and to promote the emergence of sports agents as a breakthrough, which will help Macao find a better way of development to become a world center of tourism and leisure, in the context of the diversification of the ""1+4"" industries. This study also aims to contribute to developing sports tourism in Macao. This study also provides modest suggestions for the professionalization of sports and the commercialization of the sports market in Macao, as well as for the future personal development of Macao's athletes and the sustainable development of the sports industry. This study adopts a qualitative research approach, starting with a basic introduction to sports agents, the origin and development of sports agents, and the definition of the concepts, and then further insights into the current development status, constraints, and future outlook of sports agents in Macao through industry experiences. The study sought out ten local sports industry practitioners in Macao for in-depth interviews. By analyzing and summarising the data, the study proposes meaningful recommendations for the sustainable development of the sports agent industry in Macao. Overall, the study found that the development of sports agents in Macao is still early. With the improvement of the talent admission system in Macao, society will pay more attention to the development of the sports industry, and the profession of sports agent will be nurtured in the context of a developed sports environment. However, the lack of professional athletes and large-scale sports events in Macao and the lack of innovative thinking of the General Sports Association in cultivating sports talents will limit the emergence of sports agents to a certain extent
Keywords: Macao; Sport Agent; Sport Industry; Talent Introduction; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

DAOIST PERSPECTIVES ON TEACHER-STUDENT RELATIONSHIP: TAKING MACAO AS AN EXAMPLE = 道家視角下的師生關係-以澳門為例 - Lei, Sok Fan (University of Saint Joseph, 2024)
Keywords: Teacher-student Relationship; Thesis and Dissertations Master of Philosophy (MPH); University of Saint Joseph; Wuwei; the Dao De Jing

兩晉之際中原統治集團和江南豪族合作之探討 =: A Discussion on the Cooperation Between The Ruling Group in Middle China and the Jiangnan Indigenous Families Between Western and Eastern Jin Dynasties - Wong, Seong I. (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph; 僑姓士族; 合作; 晉室; 江南豪族

小學資源教師教學成效及影響因素之研究 =: A STUDY ON THE TEACHING EFFECTS AND INFLUENCING FACTORS OF PRIMARY SCHOOL RESOURCE TEACHERS - Lam, Iok Ian (University of Saint Joseph, 2024)
Keywords: Inclusive Education; Resource Teachers; Teaching Effects; Teaching and Learning Situation; Thesis and Dissertations Master of Education(MED); University of Saint Joseph

Regulating the Use of Artificial Intelligence(AI): Achievements and Challenges - Hamamoto, Mayumi (University of Saint Joseph, 2024)
This dissertation is research regarding the achievements and challenges in artificial intelligence (A) regulation at a domestic level and international level. This study is important because there are more legal issues regarding the application of AI, and AI has grown to be part of the public’s daily lives. A mixed method has been adopted in this research: doctrinal legal research and a comparative legal research method. AI was invented in the 1950s and in the 2000s, has been more accessible to the public. The first AI regulation, the EU AI ACT, has recently been enforced, an AI regulation that has been around for nearly seven decades after its invention. It is high time that regulators in different states invest more effort in AI regulations
Keywords: AI; Artificial Intelligence; System Learning; Thesis and Dissertations Master of Lusophone and International Public Law(MLIPL); University of Saint Joseph

AI in Counselling: Perceptions on Human vs AI Generated Chat Counselling - Ieong, Ka U. (University of Saint Joseph, 2024)
The rapid development of counselling began after World War II. Meanwhile, texting services became available in the 1980s. Texting has been widely applied in both health area and mental health areas. A chatbot is a specific type of artificial intelligence (AI) that can have conversations with humans through texting. The combination of counselling and texting is known as chat counselling. The effectiveness of chatbots in alleviating psychological symptoms was supported by scientific research. Nonetheless, people hold different perceptions towards chatbots. Some common factors in counselling, including empathy and warmth, were also important in evaluating AI chatbots. Other important factors included acceptability, satisfaction and trust. The current study is the first to use AI as a counsellor. This study investigates people’s perceptions of human and AI counsellors (ChatGPT) and whether people can differentiate between human and AI. Participants needed to rate the counsellors in three scenarios: the original scenario taken from a training book, the human counsellor scenario generated from a text conversation with a human counsellor and the AI counsellor scenario produced by texting with ChatGPT, which acts as the counsellor. Prompts used to generate conversation with ChatGPT are included. The dialogues were parts of the conversations containing similar client responses and were presented using the WhatsApp interface. Questionnaires were delivered both online and in paper form. Results demonstrated that people’s ratings of human counsellors and AI counsellors did not differ in perceived empathy, acceptability, and satisfaction. While the warmth and trustworthiness of AI counsellors were perceived to be higher than those of human counsellors. On the other hand, people were unable to differentiate between human and AI counsellors in uncertain conditions. Younger people and the general population are more accurate in identifying between humans and AI, while people above 40 and psychologists or counsellors are less capable of doing so. The current study supports the potential of utilising ChatGPT in counselling. Having people experience and evaluate real chat counselling with human and AI counsellors can potentially eliminate some limitations of the current studies. Future studies can investigate how prior knowledge contributes to AI detection and examine AI counsellors' efficiency in longitudinal studies
Keywords: AI (Artificial Intelligence); Chat counselling; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; human perceptions

The Collaboration and Challenges Faced by Therapists within Professional Inclusive Education Teams in Macau =: 澳門治療師在融合教育專業團隊中的合作情況及挑戰 - Lao, Pek San (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 合作模式; 團隊合作; 治療服務; 澳門治療師

The Exploration of the Methadone Treatment Program in Heroin-Dependent: The Perspective from Users and the Quality of Life - Ma, Sara Vanessa (University of Saint Joseph, 2024)
This thesis explores the impact of the exploration of methadone treatment programs in heroin-dependent the perspective from use and the quality of life. The primary objective of this research is to investigate how different types of participants that methadone will affect their quality of life. A mixed-methods approach was employed, combining quantitative surveys with qualitative interviews to gather comprehensive data from a sample of 59 participants, 8 female, and 51 male, for the questionnaire to know about their quality of life and well-being. A structured questionnaire was used to quantitatively assess participants' quality of life, well-being, and satisfaction with methadone treatment. The survey included standardized scales measuring various dimensions of quality of life, such as physical health, mental health, social functioning, and overall life satisfaction. A mixed-methods approach was adopted, combining quantitative and qualitative research methods to provide a comprehensive understanding of treatment efficacy and genetic influences. In the course of this research on the impact of methadone treatment programs on the quality of life for heroin-dependent individuals, several key findings emerged from both the quantitative surveys and qualitative interviews. To overall improvement in quality of life the participants reported significant improvements in various dimensions of quality of life after starting methadone treatment. On average, scores for emotional well-being, social functioning, and physical health showed marked increases over the treatment period
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

澳門普通班教師與資源教師合作教學現況與改進建議之個案研究 =: A CASE STUDY OF CO-TEACHING PRACTICES AND IMPROVEMENT SUGGESTIONS AMONG GENERAL EDUCATION TEACHERS AND RESOURCE TEACHERS IN MACAO - Lai, Chong Weng (University of Saint Joseph, 2023)
Keywords: Inclusive education; Resource teacher; Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 合作教學; 澳門; 融合教育; 資源教師

INFORMAL RECYCLING IN MACAU: CHALLENGES AND OPPORTUNITIES FOR SUSTAINABLE DEVELOPMENT - Ng, Sut Wa (University of Saint Joseph, 2023)
Informal recycling plays a crucial role in municiapl solid waste management in many cities, particularly in the global South. This study examines the practices, challenges, and opportunities of informal recycling in Macau, a small city and Self Autonomous Region (S.A.R.) in China. Using qualitative research methods, including semi-structured interviews, this study explores the motivations and strategies of informal recyclers, the challenges they face, and the potential for collaboration with formal waste management systems. The findings of this study reveal that informal recycling in Macau is a complex and multifaceted reality and practice that involves a range of actors, from waste pickers to small-scale processors to exporters, all with their specific challenges. Informal recyclers are motivated by economic necessity, and they employ a variety of strategies to collect and process recyclable materials. However, they also face significant challenges, including high rental and transportation costs, lack of manpower, China’s waste import policies and ensuing restrictions, fluctuating global price rates of materials and the unstable income as serious consequence, accompanied by limited support from the local Government. This study also identifies opportunities for sustainable development of informal recycling in Macau, supported by the analysis of data collected via questionnaire survey regarding Macau citizens’ waste separation habits and their willingness to pay for resource separation and recovering process. The identified oppurtunities include establishing partnerships between informal and formal waste management actors, improving the infrastructure, and introducing environmental levy system and consistent policies and regulations. Overall, this study contributes to a better understanding of the role of informal recycling sector in waste management in Macau and provides insights into potential strategies for improving the sustainability of resource and waste management practices in the city
Keywords: Circular Economy (CE); Informal Recycling; Integrated Solid Waste Management (ISWM); Recycline Rate; Sustainable Development Goals (SDGs); Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph; Waste Hierarchy

THE USE OF AI TECHNOLOGY IN MACAO JOURNALISM: A CASE STUDY - Chan, Weng Fai (University of Saint Joseph, 2024)
Artificial Intelligence (AI) is the most advanced technology nowadays and has already been adopted by the media industry globally. Some research has stated that journalists use these technologies to improve their work. Studies found that the extent to which journalists use these technologies depends on the size of their organization and regional circumstances. This study explores how interviewed Macao journalists integrate AI tools into their work, focusing on text processing, translation, and idea generation to improve efficiency and creativity. In addition, respondents expressed that there is not enough information about AI for a small place like Macao. And the problem of application in a “three primary written languages and four spoken languages” environment. At the same time, respondents’ concerns about AI’s accuracy, reliability, and impact on journalistic professionalism are discussed, emphasizing the need for credible and trustworthy AI outputs. This study reveals a significant difference in AI tool adoption between Chinese and Portuguese respondents, with the former group showing a higher inclination towards using these technologies. Therefore, further research is suggested. In the absence of media competition in Macao, the use of AI and its knowledge is spread by journalists sharing it among different organizations, and there seems to be no official decision on the use of AI by media organizations in Macao
Keywords: Artificial Intelligence; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph; generative AI; journalism; journalists; media; multicultural; multilingual; newsroom

EXPLORING MUSLIM STUDENTS LIVED EXPERIENCES IN MACAU: A PHENOMENOLOGICAL APPROACH - Ho, Kit Ieng (University of Saint Joseph, 2024)
Muslim community is one of the minority groups in Macau SAR China. Muslims are an interesting group in terms of research because of its diversity in respect to language, nationality, social status, and education level. Groups of people migrate for various reasons such as religion, politics, economy, and education. Individuals experience the age in between nineteen and twenty-four, which fall in the category of youth. Studies of Muslim youths have gained more attention in scholarship, statistical data, and research. The study seeks to understand Muslim students’ life and the needs of this minority group and explores how Muslim students perceive Islam and their own ability to cope with school related cultural pressures through qualitative, phenomenological approach, and focuses on exploring the common experiences of Muslim students in this city. This study used a conceptual framework based on critical race theory (CRT). We use in-depth interviews of five Muslim youth, ages between 19 and 24, to investigate their school life experiences and Islamic practices. We also administered questionnaires and field note to understand their social mobility, social capital and to gain a deeper understanding of their daily lives. A thematic analysis of the interview data produced the following themes: 1) Social mobility; 2) Social capital Relationship with friends; 3) Discrimination and micro-aggressions; and 4) Religion Identity. The study found that the Muslim status of the participants did not have a significant impact on their school experience, as they were able to find accommodation in their practice of religion and school life. However, the multiple identities of the participants as Macau citizens and their ethnic backgrounds did affect their social capital and sense of belonging. The study also examined the experiences of the participants within Macau society, including social factors such as racism. The results indicated that language and ethnicity were factors that hindered their integration into the community. In addition to the original themes, the analysis of the participants' stories in this research revealed two counter-narratives that challenge prevailing narratives. These counter-narratives include the deconstruction of oppressed Muslim women's narratives and the influence of local mainstream religious schooling on Muslim students' religious loyalty. These alternative narratives provide new insights into the lives of Muslim youths and challenge conventional stories. The findings of this study have important implications for educators, academics, and members of both Muslim and non-Muslim communities. By allowing youth to establish broader connections with society and increasing their motivation to participate in and contribute to the community, this study highlights the need for inclusive educational environments that support the diverse identities of students. Furthermore, the study provides young Muslims with a voice in society, empowering them to challenge dominant narratives and promote counter narratives that reflect their experiences and perspectives to meet critical race theory ethos of ongoing active struggle
Keywords: Critical Race Theory; Muslim youth; School experience; Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Study of the Cross-Border Family Mediation Mechanisms and Practices in the Greater Bay Area (China, Hong Kong SAR, and Macau SAR”) - Wong, Hang Si (University of Saint Joseph, 2024)
The dissertation is about the study on the usage of mediation as the dispute mechanism on the cross-border family dispute issue in the Guangdong -Hong Kong- Macau Greater Bay Area through a comparative law aspects. Under the background of the Country’s Policy in integrating the citizens of the two SARs into China. The citizens of different provinces in PRC and the two SARs have frequent contact such as in business, in personal affairs and so on, the more the contact the more the possibility disputes will arise. With three different jurisdictions and the backlogs from the Courts, to find out the possibility of using another dispute resolution is essential. The study found out the perspectives of the disputed / litigated parties, courts and legal practitioners in usage of mediation, the nature of mediation in use in GBA and the strengths and limitations on the usage of mediation. This research used a mixed methods including doctrinal legal research, comparative legal research method and empirical legal research method. It result from the finding that though there is no specialized legislation in usage of mediation in Macau SAR, there is practice in usage of family mediation. Besides that the judicial mediation in PRC is not the mediation we defined in the literature review, thus it is the conciliation. Whether the recent development in Hong Kong SAR on the procedures M-FDR and M-CDR are in conflict with the facilitative mediation which has all along been practiced in Hong Kong SAR. In conclusion, the perspectives in usage of mediation in PRC and Hong Kong SAR are higher than Macau SAR and the nature of mediation in usage are different in the three jurisdictions. Lastly, in the dissertation provided some reflections on the development of family mediation mechanism in Macau SAR and how to merge the different natures of mediation in GBA
Keywords: ADR; Alternative Dispute Resolution; GBA; Greater Bay Area; Mediation; Mediation Mechanism; Thesis and Dissertations Master of Lusophone and International Public Law(MLIPL); University of Saint Joseph

Challenges and Possibilities of Cultural Heritage: The Case of Portuguese Tiles (Azulejos) in Macau - Chu, Hou Man (University of Saint Joseph, 2023)
Macao is a city of culture, and history and culture are the wealth of Macao. Over the centuries, the exchange and transmutation of Chinese and Western cultures have given Macao a unique cultural charm, and have also formed and preserved a considerable amount of cultural heritage. Cultural heritage has received increasing attention from all sectors of the community in the tourism industry in Macao, the promotion of the preservation and transmission of cultural heritage through tourism development has become a new issue in the tourism sector. As an independent art form in the urban public space, tile painting has both practical and aesthetic functions, and is a special vehicle for the convergence of multiple cultures in the urban cultural ecology. It is also a medium through which the city's cultural message can be fully disseminated. The paper presents a detailed analysis of the strengths, weaknesses, opportunities and challenges of the development of Macao's cultural heritage tile murals, based on an introduction to the existing status of Macao's cultural heritage tile murals, using the SWOT analysis method, which provides a reference for Macao's cultural heritage tourism
Keywords: Azulejo; Cultural heritage; Macao; SWOT analysis; Strategy; Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

The Study of Social Support and Stress Among Gambling Industry Workers in Macau - Wong, Sut Ieng (University of Saint Joseph, 2024)
This research explores the dynamics of stress and social support among professionals in Macao's gambling industry during the COVID-19 pandemic. The economic impact of the pandemic, coupled with the border restrictions, has severely affected Macao's gaming industry, leading to a 70% decrease in gaming revenue and a significant increase in unemployment rates among residents. As a result, many employees have faced downsizing or unpaid leave, posing significant challenges to their daily lives and raising concerns about mental health within the community. To gain a deeper understanding of these changes and the experiences of residents, this research utilized phenomenology as the methodology, employing qualitative interviews. During the recruitment of interviewees, three scales (PSS, MSPSS, and DASS21) were used as screening tools to assess the mental status of participants, allowing for the identification of various combinations of mental states. Through in-depth interviews, significant findings emerged. It was observed that interventions aimed at enhancing social support had a remarkable impact on reducing daily life stress among the interviewees. This included interventions focused on marital relationships, digital communication support, and positive personal beliefs with encouragement. In conclusion, by recognizing and proactively responding to these insights, the industry can create an ecosystem where professionals not only achieve professional excellence but also maintain robust mental and emotional well-being. Future studies should focus on developing holistic support systems within the gaming industry
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Assisting the Creative Processes in Visual Merchandising for Luxury Fashion Retail - Soares, Patricia Alexandra Ferreira (University of Saint Joseph, 2023)
This dissertation aims to research the need and viability of creating a digital platform that assists the creative processes naturally linked to Visual Merchandising. Through the proposal of a digital platform that works as a co-creative tool for display archives and a co-creative tool for display set-ups through mood boards, we will aim at improving the teamwork in retail and provide a unique, fast-forward platform for information sharing and input under the direction of Visual Departments. Building on rich source materials such as bibliography, scientific papers, news, and articles, and interviewing Visual Merchandisers actively working in the field, we will show the importance of creativity in Luxury Retail and what are the most common challenges in the field that we will propose a solution to. We will focus on the study of concepts, reviewing digital application tools being used by professionals and their best features and improvement opportunities. By gathering this information, we hope to provide accurate insights and information that proves the viability of this proposal and understand what features could serve best the target audience. Finally, we will present a conceptual idea in the form of sketches with functions of this digital application tool to be fully developed in the future and hopefully build a consistent well, designed commercial web-based application
Keywords: Luxury Retail; Thesis and Dissertations Master of Design (MDG); University of Saint Joseph; VM Digital Platform; VM Display Archives; VM Moodboard; Visual Merchandising

TO EXPLORE SMOKING BEHAVIORS OF ADULTS IN MACAO: DISCOVERIES BY QUANTITATIVE AND QUALITATIVE STUDIES - Dias, Luis Borges (University of Saint Joseph, 2023)
The purpose of the study was to explore the smoking behaviour of the smokers living in Macao. I was part of the 1st group of doctors to have chosen to initiate smoking cessation in Macau. In addition to my diverse academic background of study in laws- a dissertation about the effect of tobacco control program in Macao (submitted in 2011), a master in Public Administration, and five years of working experiences as an Inspector Assistant of tobacco, I had the conviction that I have to write to share my experience and knowledge about smoking cessation to contribute to the field of counselling and psychotherapy as there is little research data concerning smoking prevalence and demographics in Macao. This study consists of two parts – PART I presents the quantitative data collected by a questionnaire-survey over 1378 smokers and PART II qualitative data from semi-structured interviews with 10 adult smokers to explore their experiences of smoking and smoking cessation in Macao. Quantitative data analysis was conducted with the SPSS, while qualitative analysis with coding and theme identification by following the grounded theory procedures. The study found that about 85% smoker surveyed consumed more than half a pack of cigarette per day and about 31% reported various symptoms like irritability, fatigue, loss of appetite and difficulties in concentration. The qualitative study has identified major positive factors related to initiation and maintenance of smoking cessation, namely health concerns, financial concerns and family support. Major negative factors related to relapse of smoking are peer influences, smoking of family members, and impacts of stressful life events. Based on findings of the study, it is argued that preventive anti-smoking education should be implemented among young people. Promotion of health education and preventive anti-smoking strategist and policy in Macao are discussed. The data collected indicate the fact that individuals who have pathologies of the cardiovascular system as a motivating factor for contemplating or taking actions for smoking cessation. Moreover, financial problems, gender (male predominantly), married with family support, higher educational level, without psychological diseases, better economic status, lower nicotine dependent are predictors to success in quit smoking. It also raises the possible need to deepen some evaluation parameters hither to be only superficially addressed. Therefore, and by limitations inherent to the study, this hypothesis needs further investigation. I argue that non-pharmacological treatment methods alone have proven to be effective in the smoking cessation process. However, it is argued that this combined with pharmacological therapy, in particular in specialized consultations, would be more effective and capable in increasing success rates in smoking cessation
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; grounded theory; relapse; smoking behaviour; smoking cessation

「融合教育下澳門小學普通班教師班級經營面對的困難及可行策略之研究」 =: "A Study on the Difficulties Faced by Macau Primary School General Education Classroom Teachers in Class Management and Possible Strategies" - LEI, WENG KIT (University of Saint Joseph, 2024)
Keywords: Class Management; Inclusive Education; Macau Primary Schools; Qualitative Research; Teacher Attitudes; Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 教師態度; 澳門小學; 班級經營; 融合教育; 質性研究

THE LIFE DILEMMA AND ADJUSTMENT OF PARENTS OF CHILDREN WITH AUTISM SPECTRUM DISORDER IN MACAO =: 澳門自閉症類群障礙幼童的家長生活困境與調適 - Ieong, I. Teng (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 困境; 特殊教育; 自閉症兒童家長; 調適

THE ANALYSIS OF MACAO TRADITIONAL PUBLICATION INDUSTRY BETWEEN 2000 TO 2023: TRANSFORMATION BEFORE AND AFTER PANDEMIC AND SUGGESTED STRATEGY - Ung, Cheng Nam (University of Saint Joseph, 2024)
In this dissertation, the Macau traditional printing industry between 2000 and 2023 is studied. This period is critical for the publication industry due to several key events that have transformed the landscapes of both local and global publishing. These events include the rise of the internet, electronic devices, and the Chinese economy, the establishment of the Macao ISBN Agency, the emergence of online digital platforms, and the outbreak of the Covid-19 pandemic. This dissertation will mainly focus on written Chinese publications and consider publications in other languages as references. Governmental official data, academic literature, questionnaires, interviews, and participant observation analysis will be used as the major approaches when collecting data and analyzing the Macao publication industry. Several development and transformation strategies will be suggested. In the future, the Macau publishing industry will need to make significant adjustments to stay competitive in the market. It will need to incorporate current technologies, such as electronic platforms and Print-on-demand (POD), into the publication process. Books will exist in electronic and physical formats at different stages. Vanity in publications will also be another new trend in the future. The role of the publisher has evolved in the modern publishing industry. Participants in publishing industry will need to acquire new skill sets to adapt to the industrial transformation. Allocating resources to structural training courses will help develop talent in the publication industry during the transition. We hope to provide insights into solutions for the transformation of the publishing industry in Macao
Keywords: Linguistic industry; Print on Demand; Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph; digital publication; publication; vanity publication

澳門小學非特教專業教師對融合教育之態度研究 =: A study on the Attitudes of the Non-specialized Teachers of Primary Schools in Macau towards Inclusive Education - Ng, Ka Man (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 小學; 融合教育; 非特教專業教師

小學聽覺障礙學生的融合教育現狀： 以澳門C學校為例 =: CURRENT STATUS OF INTEGRATED EDUCATION FOR STUDENTS WITH HEARING IMPAIRMENT IN PRIMARY SCHOOLS: TAKE MACAU SCHOOL C AS AN EXAMPLE - LIO, I TENG (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 支援服務; 澳門; 聽障學生; 融合教育

澳門教師的情緒智力、幸福感與教學效能之相關研究 =: AN EXPLORATORY STUDY ON THE RELATIONSHIP OF MACAU TEACHERS’ EMOTIONAL INTELLIGENCE, SENSE OF WELL-BEING AND TEACHER SELF-EFFICACY - Wong, Pou I. (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 幸褔感; 情緒智力; 教學效能

澳門教師自我效能感、集體效能感與融合教育態度之相關研究 =: A STUDY ON THE CORRELATION BETWEEN TEACHERS’ SELF-EFFICACY, COLLECTIVE EFFICACY AND ATTITUDES TOWARDS INCLUSIVE EDUCATION IN MACAO - Lei, Man Teng (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 教師自我效能感; 教師集體效能感; 融合教育態度

TURNOVER INTENTIONS IN MACAO: THE ROLE OF PERCEIVED SUPPORTS AND JOB ALTERNATIVE PERCEPTIONS - U, Lai Heng (University of Saint Joseph, 2024)
The aim of the current study was to explore the relationship between perceived organisational support and co-worker support, with turnover intentions, and the role of perceived job alternatives. Turnover intentions have been a global issue for employers. In this study, we would like to investigate whether the previous global findings could also be applied in Macao. Although some similar researches were conducted in Macau, it’s not exactly the same as ours. We would like to further focus on the front-line and non-frontline group. A quantitative methodology was applied using a cross-sectional design through an online questionnaire disseminated via social media and completed by 339 full-time workers in Macao. We found that only perceived organisational support, not co-worker support, showed a negative relationship on turnover intentions. the effect seems weak for the general sample but stronger for non-frontline workers. Concerning the moderating effect of perceived job alternatives, the analysis confirmed a significant interaction to predict turnover intentions. We discussed that employees may feel trapped in their current positions due to limited job prospects elsewhere. However, employees who perceive high levels of organisational support are more likely to remain loyal and engaged even when external alternatives are scarce. Practical implications include that it might be beneficial for both employees and organisations if organisations in Macao could develop effective human resources policies and retention strategies to enhance employee retention and mitigate the negative consequences of turnover. In this study, we confirmed a negative relationship between POS and turnover intentions, but still, the effect seems weak. The effect of POS on turnover intentions seems much stronger for non-frontline employees. We confirmed co-worker support had a negative correlation with turnover intentions, which was not enough to predict turnover simply based on co-worker support. Moreover, Perceived job alternatives are confirmed to have significant interaction with POS but non-significant interaction with co-worker support on turnover intentions
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph; co-worker support; perceived job alternatives; perceived organisational support; turnover intentions

ANALYSIS AND MODEL PROPOSITION OF USER WILLINGNESS TO ADOPT MOBILE BANKING FINANCE+ SCENARIO SERVICES UNDER THE BACKGROUND OF DIGITAL TRANSFORMATION - Lin, Jingying (University of Saint Joseph, 2024)
In the wave of digital transformation, Chinese banks have taken digital and scenario-based finance as primary strategic goals. The goal is to revolutionize the mobile banking experience and encourage frequent use of mobile banking services. However, assessing customer satisfaction with the various financial and contextual services mobile banking provides is crucial. The main objective of this study is to propose a model based on users' perception of financial usage in mobile banking scenarios and how the development of mobile banking finance and scenarios affects users' choice motivations. The study examined the interview records of 12 mobile banking users through qualitative in-depth interviews and utilized Nvivo qualitative analysis software to analyze the interview content. Through repeated thinking, sorting, and differentiating the data, nine core coding categories were formed. The coding was further refined and deepened to include Financial professionalism, Security, Marketing Stimulation, Innovative Products, Use Experience, Strong Relationship, Trust, Perceived usefulness, and Willingness to use. Based on these categories, a theoretical model of user willingness in the financial scenario of mobile banking has been proposed by referring to the optimized TAM model. The results may provide support to the banking industry in Macau in understanding customers' needs and fostering the positive development of mobile finance and the scene field in Macau
Keywords: Banking in Macau; Finance+ scenarios; Grounded Theory; TAM model; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; Willingness to use

The Valuation of Nvidia Corporation (NYSE: NVDA.) - Wang, Hai (University of Saint Joseph, 2024)
This dissertation provides an in-depth valuation assessment on NVIDIA Corporation which is a leading technology company known for its GPUs, study its financial results, strategic initiatives by SWOT Analysis, and access its market positioning in semiconductor industry by using PESTEL Analysis and Poter’s Five Forces Analysis. In order to ascertain the intrinsic value and assess the future prospects of NVIDIA, the study then utilizes several financial models, Enterprise Discounted Cash Flow (EDCF), Adjusted Present Value (APV) and Discounted Economic Profit (DEP). The study presents NVIDIA is potentially overvalued
Keywords: Adjusted Present Value (APV); Discounted Economic Profit (DEP); Enterprise Discounted Cash Flow (EDCF); NVIDIA; SWOT Analysis; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

STRATEGIES FOR DEFINING AND RESOLVING NON-PERFORMING ASSETS IN STATE-OWNED CHINESE BANKS - Wu, Xiao (University of Saint Joseph, 2024)
Given the rapid growth of China's economy and its maturing financial market, state-owned banks have played a crucial role in driving national economic growth and ensuring financial stability. However, this progress has been accompanied by a pressing challenge - the accumulation of non-performing assets (NPAs), which pose significant obstacles to both the banking industry and China's economic development. Therefore, it is imperative to comprehensively analyze strategies aimed at mitigating NPAs in state-owned commercial banks, with an emphasis on seeking more effective resolution mechanisms. This study delves into the institutional environment surrounding NPAs in state-owned banks, including improvements in laws and regulations as well as advancements in financial market structures and legal frameworks. The initial step involves analyzing the current status and manifestations of NPAs within state-owned banks to clarify their ambiguously defined areas. Furthermore, considering China's unique policy context and socio-economic landscape, this study conducts an analysis and comparison of diverse strategies for addressing NPAs from the perspectives of asset quality management, risk-profit equilibrium, and legal regulatory support system. Ultimately, several suggestions are proposed regarding the trajectory of NPA resolution
Keywords: Bank; NPA; NPL; Risk management; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

澳門私立融合教育學校中資源教師現況與問題之研究 =: A RESEARCH STUDY ON THE CURRENT SITUATION AND FACING PROBLEMS OF RESOURCE TEACHERS IN PRIVATE INCLUSIVE EDUCATION SCHOOLS IN MACAO - Chan, Lok In (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 澳門; 私立融合教育學校; 融合教育; 資源教師

Attitude of middle school students toward persons with mental illness in Macau - Fan, In Kuan (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph; 污名化; 現象學; 精神疾患; 青少年

CONSUMER PROTECTION POLICY IN MACAO'S FINANCIAL SERVICES SECTOR: ANALYSIS OF THE STRENGTHS AND WEAKNESSES IN COMPARISON TO GLOBAL PRACTICES - Kuan, Ho Tong (University of Saint Joseph, 2024)
This research is to assess the current status quo, strengths, and weaknesses of financial consumer protection mechanisms in Macao. According to the World Bank, financial consumer protection can bring positive impact on the development of financial sector, broadening financial inclusion and fostering economic growth. In 2022, under the backdrop of COVID-19 and downturn in economy, Macao Government announced its ambition to recover and diversify the economy of Macao by leveraging “1+4” Diversified Development Strategy, in which developing modern finance is one of the main priorities. The new Financial System Act took into effect on 1st November 2023 and this Act will enable non-financial institutions to apply for temporary licenses on fin-tech innovations within a controllable risk area. In the local context, does Macao have a strong financial consumer protection mechanism in place to goal for developing modern finance and face challenges brought by fin-tech? In this research, a mixed method consisting of doctrinal legal research method and comparative legal research method is adopted. 10 jurisdictions (Ireland, Singapore, Australia, United Kingdom, Malaysia, Hong Kong, China, European Union, Canada, and United States) were selected in comparison of rights for financial consumer protection based on the G20/OECD High-Level Principles on Financial Consumer Protection and the results of which were then compared to the rights for financial consumer protection in Macao. The findings of this study show that the main strength of financial consumer protection mechanisms in Macao lies on the supervision of the Monetary Authority of Macao (AMCM) on the banking sector and insurance sector, other financial institutions according to international principles; however, the in-depthness of work done by Macao in financial consumer protection is not as much as those done by other jurisdictions: in Macao, there is no policyholder protection scheme in the event of failure of insurance companies; no mystery shopping and consumer survey done by oversight bodies; narrow range of definition of vulnerable consumers; no financial literacy survey; no in-depth competition law; no in-depth guidelines to monitor advertising materials for financial products; no database for consumers to search for unregulated firms and scammers; no in-depth financial educational materials about the rights of financial consumers. It is recommended that Macao Government can learn from United Kingdom, Canada and European Union to adopt behavioural insights in developing financial consumer protection policy to protect financial consumers from being exploited by the financial service providers based on the consumers’ behavioural biases. Some literature suggested that consumers are vulnerable in digital landscape. Therefore, it is strongly recommended that Macao Government shall take proactive actions to strengthen the current financial consumer protection mechanism by adhering to the G20/OECD High-Level Principles on Financial Consumer Protection, in order to develop modern finance and protect consumers from the risks posed by fin-tech
Keywords: Macao; Thesis and Dissertations Master of Lusophone and International Public Law(MLIPL); University of Saint Joseph; financial consumer protection; financial education; financial inclusion; financial literacy

A financial Valuation Study for Moody’s Corporation - Sio, Lai Teng (University of Saint Joseph, 2023)
This study presents the intrinsic value of Moody’s Corporation, a leading credit rating agency in the U.S. The results of the valuation were compared to the market value of Moody’s Corporation of the same date. The aim of the research is to provide a perspective to the investors on whether the actual value of the Company was overvalued or undervalued in the market, and how much the volatility of the stock price by the change of some factors. Both qualitative and quantitative analyses were applied in the research. The historical data, economic outlook, and the Company’s strategies were collected to be the metrics to determine the intrinsic value and provide an analysis of the prospects of Moody’s Corporation. Three valuation models were applied in the research to estimate the intrinsic value of the Company’s common stock. The cost of debt, cost of equity, the weighted average cost of capital, and the market risk premium were introduced and calculated in the research as they were the critical components in the valuation process. Since the valuation was based on assumptions and historical data to determine future growth, which indicates that the results could be changed due to uncertain factors. This study demonstrates that there was some discrepancy between the stock’s market price and the intrinsic value per share of Moody’s Corporation as of December 31, 2021
Keywords: Intrinsic Value; Moody's; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph; Valuation

澳門融合教育下資源老師心路歷程之質性研究 =: A QUALITATIVE STUDY ON THE SPIRITUAL JOURNEY OF RESOURCE TEACHERS IN INCLUSIVE EDUCATION IN MACAO - Ke, Li Ping (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 心路歷程; 融合教育; 資源老師; 質性研究

NATURE EXPOSURE AND CREATIVITY IN THE WORKPLACE: THE ROLE OF JOB SATISFACTION - Ao, Si Weng (University of Saint Joseph, 2024)
This dissertation investigates the relationship between nature exposure in the workplace, job satisfaction, and creativity among full-time employees in Macao. The study aims to examine the impact of exposure to greenery and sunlight on job creativity and job satisfaction, as well as the mediating role of job satisfaction in the relationship between workplace nature exposure and creativity. Drawing on existing literature, the study proposes the following hypotheses: (H1) Workplace nature exposure, including greenery and sunlight, positively influences job creativity. (H2) Workplace nature exposure, including greenery and sunlight, positively affects job satisfaction. (H3) Job satisfaction mediates the positive relationship between workplace nature exposure (specifically, greenery and sunlight) and job creativity. A quantitative methodology utilizing cross-sectional self-response questionnaires was employed for data collection. The measures used were pre-validated and translated into Chinese through a rigorous process of translation and back-translation. The final sample consisted of 450 full-time workers in Macao. The results highlight the significance of integrating natural elements, such as greenery and sunlight, into the work environment to promote a more favourable setting for innovation and the overall well-being of employees. The implications of these findings, both in theoretical and practical terms, are thoroughly discussed. By examining the relationships, this study contributes to the understanding of how the physical environment influences employee well-being and performance. The findings offer valuable insights for organisations and policymakers in designing workspaces that foster creativity and job satisfaction among employees
Keywords: Job Creativity; Job Satisfaction; Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph; Workplace Nature Exposure

PUBLIC POLICIES AND INFRASTRUCTURE FOR ELECTRIC VEHICLES IN MACAO: LOCAL PERSPECTIVES AND EXPERIENCES - Tai, On Teng (University of Saint Joseph, 2024)
This dissertation explores Macao residents' experiences and perspectives regarding Macao's public policies and infrastructure for electric vehicles. It delves into residents' viewpoints on the effectiveness of electric vehicle policy implementation, the layout and convenience of public facilities such as charging stations and designated parking spaces for electric vehicles, and their actual experiences and feedback while using electric cars. This study is significant because it provides valuable insights into Macao residents' fundamental attitudes and needs toward electric vehicle policies and public facilities. By understanding these perspectives, policymakers can make more informed decisions to optimize electric vehicle policies and improve public facilities, ultimately promoting the healthy development of the electric vehicle market in Macao and facilitating the construction of a green transportation system. In terms of research methods, this study primarily employed questionnaires to collect data from road users in Macao. The questionnaires were designed to gather comprehensive information on their experiences and feedback related to electric vehicle policies, infrastructure, and usage. The findings of this study are intriguing. Firstly, it was discovered that Macao residents have a relatively low awareness of electric vehicle policies, but generally, they believe these policies contribute to environmental protection. Secondly, regarding public facilities, some residents reported issues such as uneven distribution and insufficient number of charging stations, as well as inadequacies in using and managing designated parking spaces for electric vehicles. Additionally, residents provided specific opinions and suggestions regarding the purchase costs of electric vehicles and government subsidy policies. Based on these findings, my conclusion is that there is an urgent need to optimize and improve Macao's electric vehicle policies and public facilities. Policymakers should increase publicity efforts to raise residents' awareness of electric vehicle policies and reasonably plan the layout of charging stations and designated parking spaces for electric vehicles to enhance their convenience and availability. Furthermore, the government could consider providing more subsidies and preferential policies for purchasing electric vehicles to reduce the financial burden on residents. These measures will help promote the further development of the electric vehicle market in Macao and facilitate the construction of a green transportation system
Keywords: Electric vehicles; Green transportation; Macao; Public infrastructure; Public policies; Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

The international law against tax avoidance: “status quo” and perspectives for development of the regime - Wong, Chang Man (University of Saint Joseph, 2024)
This dissertation examines the critical need to continuously update the international tax law against tax avoidance: “status quo” and perspectives for development of the current regime. Employing a doctrinal methodological approach, the research first seeks to uncover the most common forms of international tax avoidance through an extensive literature review. This crucial step provides invaluable insights into the diverse strategies and mechanisms utilized by individuals and businesses to circumvent taxation on a global scale. The dissertation then proceeds to examine how current international tax law addresses the identified forms of tax avoidance. This implies a multi-faceted analysis, including an identification of the relevant international norms and treaties, and an exploration of the main sources of international tax law and their practical application. Recognizing the dynamic nature of the global tax landscape, the dissertation also provides perspectives for the future development of international tax law to better address the challenge of tax avoidance. By thoroughly examining the strengths and limitations of the current international tax law regime, the dissertation offers recommendations for potential improvements to the application of international tax avoidance conventions. The findings of this comprehensive study contribute to the broader understanding of international tax avoidance and its regulation within the framework of international law. The research questions and objectives serve as a guiding framework, enabling a thorough analysis that can inform practitioners, and scholars engaged in the ongoing discourse surrounding global taxation and its implications for economic fairness and transparency
Keywords: Global taxation; International norms and treaties for tax; International tax avoidance; International tax law against tax avoidance; Limitation and development of current international tax law regime; Status quo; Thesis and Dissertations Master of Lusophone and International Public Law(MLIPL); University of Saint Joseph

FEMALE EMPLOYEES’ PERCEPTIONS OF WORK-LIFE BALANCE AND TURNOVER INTENTIONS IN MACAO - Lei, Hon Nei; Silva, Maria Rita (University of Saint Joseph, 2023)
"This study explored the relationships of work-life balance and turnover intentions of full-time employees in Macao, and role of gender, parenting, and elderly care. Namely: (1) What is the relationship between work-life balance perceptions and turnover intentions? (2) What is the moderating role of gender in the relationship between work-life balance perceptions and turnover intentions? (3) What is the moderating role of parenting (i.e., having children or not) in the relationship between work-life balance perceptions and turnover intentions? And, (4) what is the moderating role of care for elderly family members (i.e., having to provide care or not) in the relationship between work-life balance perceptions and turnover intentions?"
Keywords: Elderly Care; Gender; Parenting; Thesis and Dissertations Master of Organisational Psychology (MOP); Turnover Intention; University of Saint Joseph; Work-Life Balance

Factors Affecting Customer Satisfaction for Fitness Club: A Case Study of Noble Fitness Club in Zhongshan - Zhu, Junwen (University of Saint Joseph, 2024)
This paper selects Noble Fitness Club in Zhongshan as a research object, adopting a qualitative method and conducting in-depth interviews with its members to determine what factors affect customers’ choice of a fitness club. This study is important because it enriches the theoretical guidance framework of the fitness market. Moreover, it helps partitioners from the fitness industry realize what factors directly impact customer satisfaction, providing recommendations for them to foster sustainable development. In-depth interviewing is the primary method for data collection. And, the thematic content analysis (TCA) approach is used to analyze the data derived from interview transcripts. Existing research identified eight factors affecting customers’ choice of a fitness club. However, the author discovered three additional factors that also significantly influenced their selection of a fitness club: geographical location, group courses, and fitness atmosphere. The fitness industry has an issue of product homogenization. Attracting more customers while retaining existing members is a challenge many fitness clubs face nowadays. Therefore, operators should avoid engaging in a price war, reducing the profit margin to attract more customers at the expense of sacrificing service quality. Instead, they should prioritize customers’ practical needs and make the best effort to meet their expectations
Keywords: Case Study; Customer Satisfaction; Fitness Club; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

THE IMPACT OF SOCIAL MEDIA AMONG MACAU BAPTIST COLLEGE SCHOOL STUDENTS: ATTITUDE TOWARDS LEARNING AND RELATIONSHIP WITH PEOPLE - Leong, Fong Hio (University of Saint Joseph, 2024)
This study explores the attitudes of students at Macau Baptist College toward social media usage and its influence on their relationships and academic performance. The research utilized mixed methods to incorporate focus group discussions, in-depth interviews with eight students, eleven teachers, and seven parents, and an online questionnaire administered to 341 students across all college levels. Findings reveal that WeChat is the primary communication tool among college members, significantly facilitating relationships within the school community. Students reported spending extensive time online, especially during holidays, which raises concerns about its impact on academic performance and mental well-being. While many students acknowledge the potential benefits of social media for learning, they also express skepticism regarding the reliability of online information and experience challenges in seeking help due to fears of judgment. The study highlights students' mixed attitudes toward social media, emphasizing the need for digital literacy and guidance to navigate online interactions safely. Ultimately, this research underscores the importance of fostering a supportive environment for students, enabling them to balance their digital engagements with academic responsibilities. Recommendations for parents, educators, and policymakers include: - Promoting responsible social media use. - Enhancing media literacy education. - Facilitating open communication to address online challenges. By addressing these aspects, stakeholders can optimize the positive effects of social media while mitigating its potential drawbacks on students' well-being and academic success
Keywords: Attitude; Learning; Relationship; Social Media; Students; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

FINANCIAL VALUATION OF WALT DISNEY - Guo, Ying (University of Saint Joseph, 2024)
Disney is a leading global cross-media entertainment giant. With its diversified business model, Disney has achieved significant success in film production, television programs, theme park and resort operations, product sales, and media networks. Disney not only has strong capabilities in content creation but also excels in distribution channels and platform construction. By continuously expanding its direct streaming services to consumers, such as Disney+, Disney is adapting to the changes in the digital age and further consolidating its leadership position in the global entertainment market. Nevertheless, Disney still faces many challenges, including rising copyright costs, threats from emerging competitors, the impact of global political and economic uncertainty, and addressing the long-term impact of the COVID-19 pandemic. Therefore, an analysis of Disney's financial position considering these internal and external factors will help assess the company's intrinsic value and its future position. Based on the above background, this thesis aims to provide in-depth insights into the current financial situation and future development prospects of Disney Company through detailed financial analysis
Keywords: Disney 2; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; financial valuation 1; pandemic 3

A STUDY OF GREEN FINANCIAL TECHNOLOGY ACCEPTANCE IN TONGZHOU DISTRICT OF BEIJING - An, Bo Yang (University of Saint Joseph, 2023)
China’s economy has entered a critical period of structural adjustment. The developing green industries and the transforming traditional industries have increasing demand for finance, making ""green finance"" increasingly essential. While China's green finance is in the development stage, some newly developed zones serve as pilots for the launch of green financial products. An example is Tongzhou District of Beijing, which aims to expand Beijing’s space, promote the coordinated development of Beijing-Tianjin-Hebei, and explore the optimal development mode of the densely populated economic areas. This thesis aims to study consumer acceptance of green financial technology (fintech) in the case of Tongzhou District. This thesis extended the commonly applied theoretical model for the problem of study, the Energy Augmented Technology Acceptance Model (EA-TAM), to analyze the impacts of perceived usefulness, perceived ease of use, attitude toward use, intention, usage intention, environmental awareness, and green knowledge on the acceptance of green fintech in Tongzhou District. The survey collected 403 valid responses from people that had been active in Tongzhou District. The quantitative analysis is based on structural equation modeling techniques, including reliability analysis, validity analysis, standard method deviation test, and hypothesis testing. The analytical results show that all the hypothesized factors are significant. In addition, the sample is divided into different gender groups and education groups, so that the impacts of the socio-demographic characteristics can be explored. Males’ environmental awareness and green knowledge are insignificant in determining their acceptance of green fintech. The low-educated group’s acceptance of green fintech does not significantly depend on environmental awareness and perceived usefulness
Keywords: Fintech; Green Gintech; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

AN EMPIRICAL STUDY ON THE DRIVERS OF CONSUMER SHOPPING BEHAVIOR IN LIVE-STREAMING COMMERCE - Song, Wilson (University of Saint Joseph, 2024)
This dissertation identifies factors driving consumer shopping behavior within the realm of live-streaming commerce, an area fast emerging in the e-commerce domain. Live-streaming shopping or commerce involves real-time interaction and entertainment with traditional online shopping, forming a unique endogenous environment where consumers can contact sellers or influencers directly. The study employed quantitative surveys that identified some of the main determining factors of consumer behavior within this context. The findings show that the significant factors in determining consumer behavior are trust and engagement, which are strongly influenced by the credibility and authenticity of the live streamer. Another significant finding is the role of social interaction and community building in providing consumers with a sense of belonging and validation, enhancing their confidence and purchase intention. Moreover, it highlights how marketing strategies of flash sales, limited-time offers, and partnerships with influencers make their way into the system to help invoke engagement and impulsive buying behavior among consumers. The implications of these findings extend to e-commerce platforms and marketers. Any improvements in features leading to trust, engagement, and interactivity within the community would drive higher customer satisfaction and sales. According to researchers, working partnerships with believable influencers and more extensive integrations of real-time marketing might further activate live-streaming commerce. This study thus fills a gap in the existing body of literature by detailing the drivers of consumer behavior toward live-stream commerce. It also identifies areas of future research on the current studies, including developing technologies and the cultural variances in the impact of live-stream commerce, including ethical considerations. These results are principle for guiding work on potential live-stream commerce in the digital age for anybody from workers to academicians
Keywords: E-Commerce; Live-Streaming; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; consumer behavior

A Financial Valuation of Hewlett-Packard Inc. (NYSE: HPQ) - Ma, Heng (University of Saint Joseph, 2024)
As one of the world's leading technology companies, HP occupies an essential position in the printer and personal system markets. In order to analyze HP's current market value and predict its future financial performance, this thesis values HP by applying three models: EDCF, DEP, and APV. Based on the financial statement from 2019 to 2023, this thesis conducts a common size analysis of the financial data to facilitate the comparison between various indicators. HP's asset structure and profitability are analyzed and the company's beta is also tested. To analyze HP's position and environment in the technology industry, Dell Inc. will be analyzed as its main competitor. At the same time, the intrinsic value of HP is estimated based on the financial statements for the next ten years which is predicted. The valuation results are compared with HP's stock price at the end of 2023 to determine whether HP's stock price is overvalued or undervalued. In order to improve the accuracy of the valuation, sensitivity analysis is also used to evaluate the impact of variables such as internal factors and external market factors on the company's value. Studies have shown that HP's intrinsic value is greatly affected by the market risk premium. This thesis also uses SWOT and PESTEL to analyze the company's strengths, weaknesses and operating environment which will help to identify the company's competitiveness. It also helps to identify HP's potential opportunities and risks in technological innovation and market expansion. The impact of the macro-economy on HP's development is also analyzed. The results of this thesis provide a reference for investors and management, which helps to understand the market positioning and future development potential of HP and other technology companies. The limitations of the study are the subjectivity of data forecasts and the uncertainty of the market environment
Keywords: Case Study; Customer Satisfaction; Fitness Club; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

澳門小學教師對融合教育態度之研究 =: A Study on Macao Primary School Teachers ’Attitudes towards Inclusive Education - Kwok, Siu Kam (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 小學教師; 澳門; 融合教育

The VALUATION OF TENCENT HOLDINGS LIMITED - Lo, Hao Weng (University of Saint Joseph, 2023)
This study analyzed Tencent Holdings Limited’s internal and external factors and future strategies, forecasted the financial statements of the Company for the next ten years, and measured the intrinsic value of the Company on December 31, 2021 and compared it with the stock market price on the same date. The share price’s sensitivity analysis was also conducted to understand the Company's capital structure and profitability, and the sensitivity analysis can be used to reflect the impact of these factors and strategies on the future share price, which can have a high impact on investors' future investment decisions. This study also used the SWOT Analysis and Michael Porter's Five Forces Analysis to analyze the Company's strengths, weaknesses, opportunities and threats and the Five Competitive Forces that shape the technology industry to evaluate the Company's external and internal environment and enrich the management with a more intuitive analysis leading to recommendations
Keywords: PEST Analysis; SWOT Analysis; Technology Industry; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

澳門幼稚園非特教專業教師在融合教育班級經營的困難與應對策略之研究 =: Challenges and Strategies in the Management of Integrated Education Classes: Insights from Non-certified Kindergarten Special Education Teachers in Macau - Leong, Choi Cheng (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 澳門幼稚園; 班級經營; 融合教育; 非特教專業教師

IMPLEMENTATION OF SDG 1 IN CAPE VERDE: AN ANALYSIS OF POLICIES AND ACTORS - Pasquinha, Patrick Delgado (University of Saint Joseph, 2024)
In the 21st century, poverty still remains a serious issue for the world, halting development and growth of nations. SDG 1 refers to the first Sustainable Development Goal (SDG) established by United nations. It has as goal to “end poverty in all its forms everywhere”. Cape Verde as an UN member also adopted it and aligned national policies to achieve it. This thesis aimed to analyze the different policies adopted by the government of Cape Verde to implement SDG 1. Moreover, this dissertation will also point out the different actors behind the implementation of SGD 1 in Cabo Verde (both national and international actors), as well as find out their role in alleviating poverty in Cabo Verde, in other words, how they contribute to poverty alleviation in Cabo Verde. Based on a qualitative methodology, using document analysis as method to collect the data and further using thematic analysis to analyze, code and categorize the collected data, the study was able to answer the two research questions: Research question 1: What are the different policies adopted by the government of Cape Verde to implement SDG 1. Research question 2: Who and what are the roles of the actors involved in the implementation of SDG 1 in Cape Verde? The findings of the study revealed that: As to research question 1, the study found out that the government of Cape Verde has adopted several policies geared towards poverty reduction. Such policies included social protection policies, investment in infrastructure policies, investment in education policies, investment in health policies, investment in rural development policies, economic diversification policies, gender equality and women empowerment policies, job creation policies and climate change adaptation policies. As for research question 2, the study 4 revealed there are two main Actors are responsible for the implementation of SDG 1, government institutions and National and International Partners. On one hand, the government of Cape Verde is focused on creating and adopting polices that target the poor, as result this make sure that they can lift from poverty or at least avoid they sinking into deeper poverty. On the other hand, the partners (here known as Actors) helping on the implementation of SDG 1 in Cape Verde work as a backup for the government, helping it on other issues related to SDG 1 implementation such as knowledge and capital provision and so on. The Cape Verde government is dedicated to reducing poverty, focusing on the unemployment and migration phenomenon. These factors contribute to poverty and exacerbate it. Despite these challenges, the overall outlook on poverty reduction in Cape Verde is optimistic, indicating a significant commitment to address the root causes of poverty
Keywords: Actors; Cape Verde; Multidimensional poverty; Poverty reduction policies; SDG 1 implementation; Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

SOCIAL PERSPECTIVES ABOUT CANTONESE OPERA IN MACAO ACROSS GENERATIONS: CULTURAL IDENTITY AND SOCIAL BONDING - Sin, Shuk Ching; Silva, Maria Rita (University of Saint Joseph, 2023)
"Cantonese opera (CO) represents an art form that had its golden time in Macao during the mid-twentieth century. CO still has many loyal fans but they mainly are in the older generation. The purpose of this study was to explore if CO is considered a cultural capital heritage in Macao, related to cultural identity and transmitted across generations to support social bonding. Applying a qualitative methodology, a script for exploring participants’ experiences and opinions about CO was designed, and different groups of individuals were recruited for semi-structured interviews and focus groups. The data collected was analysed by a thematic analysis of the verbatim transcripts. Findings show that in the past first contacts with CO happened in family and related social context, mainly during participants’ developing age. However, currently CO is no longer passed on to the next generation. Despite that the young generations acknowledging their cultural identities in CO, mainly in terms of Cantonese culture and Cantonese language, older individuals engaged with CO seemed to perceive their cultural identities more in depth in its history, literacy and music. Actually, engagement is an important factor that generates social bonds. The CO leisure practitioners, no matter young or old, experienced the effects of social bonding during the ritual of enquiry in the process of learning and practising CO. To improve CO’s preservation in Macao, the adoption of strategies such as developing new productions, crossover with other media, innovations in promotion targeting the young audiences, and absorbing audiences in the Great Bay area were proposed. Finally, the potential use of CO as a tool in counselling and community work is discussed. "
Keywords: Cantonese Opera; Cultural Identity; Individual Well-being; Social Bonding; Thesis and Dissertations Master of Counselling and Psychotherapy (MCP); University of Saint Joseph

Comparative study of the implementation of the National Security Law in the SARs: A Case study of Hong Kong SAR and Macao SAR - Wu, Ka Seng (University of Saint Joseph, 2024)
The aim of this study is comparing the jurisdiction of the National Security Law in Hong Kong SAR and Macau SAR, also reviewing the practical implementation of the law in the two SARs, analyzing the Chinese government's participation in the governance of national security in two SARs, and exploring the future sustainability of National Security Law in two SARs
Keywords: Hong Kong; Macao; National Security; National Security Law; Thesis and Dissertations Master of Lusophone and International Public Law(MLIPL); University of Saint Joseph

EXPLORING THE RELATIONSHIP BETWEEN WRITTEN COMMUNICATION COMPETENCE AND CULTURAL INTELLIGENCE (CQ): A CASE STUDY OF EFL LEARNERS IN MACAO - Sin, Man Teng (University of Saint Joseph, 2024)
Although Macau students received years of English lectures as compulsory, the outcome could be more favorable when applied to English written performance. In that written communication requires the individual to consider audience perception of the message, a challenge for ESL writers, this study explores whether different forms of feedback can enhance one’s cultural intelligence.The current study looked into the effect of incorporating peer involvement and instructor feedback in written communication, gaining insight into cultural nuances. In order to attain the objective, data were gathered through the utilization of an action research methodology employing a mixed-method design. Grade twelve local students attended a six-week six-week intervention consisting of two cycles. The focus of the intervention nurtured essay writing; the topics of which were inspired by popular musical lyrics, and involved a drafting process that incorporated feedback both from peer editing and the instructor.. The data collected throughout the study involved analysis of written samples (scores of draft and final version) using a paired samples t-test. In addition, students completed a pre-test and post-test survey of the cultural intelligence instrument (CQ), which measured their performance across four domains. There were statistically significant differences between cognitive CQ and motivational CQ between the scores attained before and directly after the intervention.. This study's findings suggest that the written communication of ESL students may be enhanced by adjusting . These findings enriched our understanding of how peer editing and teacher feedback with songs affected the outcomes of second language learners
Keywords: Music; Thesis and Dissertations Master of Education (MED); University of Saint Joseph; cultural intelligence; foreign language anxiety; writing competence

粵繡工藝及修復研究: 以私人收藏的一組四件樣品為例 = THE CRAFT AND CONSERVATION OF CANTONESE EMBROIDERY: A CASE STUDY OF A SERIES OF FOUR SAMPLES FROM A PRIVATE COLLECTION - Lou, Fong I. (University of Saint Joseph, 2024)
Keywords: Bainiaochaofeng; Cantonese embroidery; Cantonese embroidery in Macau; Embroidery’s preservation; Guangzhou embroidery; Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph; 刺繡修復; 廣繡; 澳門粵繡; 百鳥朝鳳; 粵繡

INTEGRATING ROBOTS INTO READING IN AN INCLUSIVE ESL CLASSROOM AT LOWER PRIMARY - Lei, Ut Wa (University of Saint Joseph, 2023)
Establishing and improving the independent reading ability of middle school students has become one of the critical topics in the world, especially for second language learners. The cultivation of independent reading ability has specific challenges. This action research investigated the effectiveness of integrating robot-assisted teaching in reading lessons at lower primary grades. A group of third-grade students (n=15) participated in this research. The instruments include the pre-and post-test of a reading competency test (RCT) and motivational index (MI), a teacher reflection journal, and focus group discussion with parents. The whole intervention is conducted in two cycles, and requires the completion of four 40-minute lessons each week per cycle. The findings support the view that integrating robot-assisted teaching in the classroom can improve students' learning motivation to a certain extent, and that intervention programs positively impact students' learning motivation and independent reading ability in English. This study provides suggestion for the design of English reading instruction, and encourages English teachers to pay more attention to improving students' independent reading ability
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; independent reading skills; learning motivation; robot-assisted teaching

Impact of green finance on Asian economic development - Wong, Kuan Lam (University of Saint Joseph, 2024)
The development of green financial products like green bonds and industry financing has gained momentum, showing positive impacts on sustainable economic development, renewable energy investment, and greenhouse gas emission reduction. As the research problem is inadequately explored, this dissertation aims to fill the research gap to evaluate the impacts of green finance on economic development. Furthermore, this study assesses the differences between Asian and non-Asian economies in the impacts of green finance on economic development. Two empirical measures are analyzed in this study.Green finance is measured with the Global Green Finance Index (GGFI), a composite index that captures over 100 instrumental variables, covering the business environment, human capital, infrastructure, and sustainability aspects of a financial center. Growth rate of gross domestic product (GDP) per capita reflects economic development. The dataset encompasses 83 international financial centers from 2018 to 2022. The regression model finds a significant negative relationship between growth rates of GGFI and GDP per capita in the full sample, the Asian subgroup, and the non-Asian subgroup. GGFI growth is confirmed to have Granger caused GDP per capita growth, but GDP per capita growth did not Granger cause GGFI growth. Combined with the insights of the previous studies, this study justifies the findings as a short-term negative impact of green finance on economic growth. However, the Asian region, with many emerging economies, could transition faster, so the regression derives a less negative coefficients for Asian financial centers. The policy implication 5 is that continued government support to improve the effectiveness of green finance is necessary for the long-term benefit of green finance to be fully realized
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Effective Promotion for Old Tea Restaurant Base On Marketing Mix Approach After Covid-19 Pandemic In Macau - Ho, Ka Ian (University of Saint Joseph, 2023)
This research paper analyses the marketing efforts and important attributes of Macau tea restaurants that have been open for more than 20 years, especially the digital methods that tea restaurants have used to sustain their business and meet customers' needs in the era of digital transition after the onset of the 2019 Covid 19 pandemic year. Using online marketing channels nowadays become an important tool for communicating with customers today. Despite the old Tea Restaurants in Macau did not put much efforts on digital channels for communication yet, to find out how tea restaurants survive in the rival restaurant industry in Macau, qualitative and quantitative methods were used to see how they meet the needs of their customers. For the quantitative method, an online survey questionnaire in bilingual English and Traditional Chinese was conducted with 280 respondents on customer purchase habits, importance of restaurants’ attributes and social media insights on tea restaurants, and the data was analysis by SPSS for the relationship and significance. For the qualitative method, 7 interviews were conducted with the business owners of the old tea restaurants which that have been opened for more than 20 years, including marketing efforts and their attitudes towards digitalization. To find out the marketing strategy of Macau’s old tea restaurants in the digital transformation era, it was found that “place” and “product” are the most important marketing mix for customers. Tea restaurant owners focus on product quality, and generate “word-of-mouth” which is customer-generated marketing, and is an effective way to influence customers for local tea restaurants. Meanwhile business owners will consider digitalize in the near future as well to match the new young customers’ online habits and the need for “place” such as online delivery platform
Keywords: Macau; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph; digitalization; marketing mix; tea restaurant

THE IMPACT OF TRANSFORMATIONAL LEADERSHIP ON EMPLOYEE PERFORMANCE IN MACAU'S LAND TRANSPORT SECTOR: THE MEDIATING ROLE OF EMPLOYEE WORK ENGAGEMENT - Cai, Shi Xin (University of Saint Joseph, 2024)
Public transportation is an important component of urban infrastructure and has a significant impact on the convenience and well-being of citizens. In Macau, with rapid economic development and urbanization, an efficient land transport system is essential to support sustainable development. Previous research has primarily focused on the sustainable development of the transportation sector in Macau, with little attention given to studies concerning employees. Therefore, the purpose of this study is to examine the impact of transformational leadership on employee work performance in the land transportation sector in Macau, with a particular focus on the mediating role of employee work engagement. Through a quantitative research methodology, this study utilized an online questionnaire to collect data from 194 employees from the bus and LRT sectors in order to achieve the research objectives. Convenience sampling and snowball sampling methods were used in this study to analyze the data through SPSS software to assess the relationship between transformational leadership, employee work engagement and employee performance. The findings reveal that there is a significant positive relationship between transformational leadership and employee performance, as well as a significant positive relationship between transformational leadership and employee work engagement. In addition, employee work engagement played a partial mediating role between transformational leadership and employee performance. The findings suggest that transformational leadership not only directly enhances employee performance, but also indirectly enhances employee performance by increasing employee work engagement. These insights have important practical implications, indicating that adopting transformational leadership behaviors can effectively enhance employee engagement and performance, thereby improving organizational effectiveness. Specifically, managers in Macau's transportation sector should pay attention to and cultivate transformational leadership behaviors in order to enhance employee work engagement and performance, and thus achieve higher organizational effectiveness and building a strong team
Keywords: Employee Work Engagement; Employee Work Performance; Thesis and Dissertations Master of Organisational Psychology (MOP); Transformational Leadership; University of Saint Joseph

REMINISCENCE THERAPY IN INSTITUTIONALIZED ELDERLY PEOPLE: CASE STUDY = TERAPIA DE REMINISCÊNCIAS EM IDOSOS INSTITUCIONALIZADOS: ESTUDO DE CASO - Araújo, Filipa Maria Santos (University of Saint Joseph, 2024)
Keywords: Depression; Elderly; Mental Health; Reminiscence Therapy; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; Well-being

Financial valuation of coca-cola company (NYSE: KO) - Jiang, Ye (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; financial statement; intrinsic value; valuation models

澳門融合教育小學資源教師的工作困難與需求 =: INCLUSIVE EDUCATION IN MACAO’S PRIMARY SCHOOL：THE WORK DIFFICULTIES AND NEEDS OF PRIMARY RESOURCE TEACHER - Chong, Hei Tong (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 小學資源教師; 工作困難; 融合教育

探討教師及家長視角下澳門推行生命教育之現況 =: EXPLORING THE CURRENT SITUATION OF LIFE EDUCATION IN MACAU FROM THE PERSPECTIVES OF TEACHERS AND PARENTS - Lei, Choi In (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 教師自我效能; 生命教育; 親社會行為

初任教師在融合教育中教學困擾及因應策略: 以澳門某三所私立學校的初任教師為例 = TEACHING CHALLENGES OF NOVICE TEACHERS AND COPING STRATEGIES IN INCLUSIVE EDUCATION: A STUDY OF NOVICE TEACHERS IN THREE PRIVATE SCHOOLS IN MACAO - Wong, Man U. (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 初任教師; 因應策略; 教學困擾; 融合教育

SPORTS FACILITIES IN HIGH-DENSITY URBAN AREA - Wong, Si Weng (University of Saint Joseph, 2023)
How can we provide more sports areas in a high-density urban environment? Nowadays, most cities in Asia are experiencing high-speed development (Satterthwaite, 2023). There is an intensely increasing demand for land that is confronted with an insufficient supply of space, resulting in a shortfall of suitable construction space to meet the rising demand. Over the past few decades, different countries and cities have created various solutions for this issue. This shortage of space has been resolved in various ways, for example: through land reclamation, renovation, and architectural design (Grydehoj, 2015). This dissertation seeks to analyse and discuss how architects have used design to expand spaces within the limited available areas for public spaces like sports facilities (Carmona, 2021). Understanding how sports modalities influence architecture and space utilisation for sports activities will also be covered. Additionally, it will examine case studies on how to better implement the program in a limited urban area with regards to the typology connections of sports facilities and their interaction with users. Finally, this dissertation is practice-based and oriented, the case study and project development will focus on a sports facility in the high-density populated Taipa Centre (Macau). This specific project solution will address the real problem for the city, and research will conclude by analysing the constraints of sports architecture in high-density areas, providing design solutions for these situations, and thereby contributing to the improvement of public spaces in a city
Keywords: Centrality; High-Density Urban Spaces; Indoor-Outdoor Interaction; Sports Facilities; Stacking; Theses and Dissertations Master of Architecture (MARCH); University of Saint Joseph

UNITING - FRAGMENTED SPACES ARCHITECTURE CENTRALIZING HERITAGE INTERPRETATION - Un, Cheng Wai (University of Saint Joseph, 2023)
For many people, an art museum is a place to display artifacts, artworks, and the temporaryhistory of a community or country. It also advocates for an artist’s viewpoints on art. In fact,museum design is closely related to politics. The purpose for building a museum in a city is toexhibit information about the development of the local culture. Moreover, high culturalvalue land is usually built with museums displaying their heritage nearby, so that people canexplore and learn more about the local historical background and artifacts of the place.The abandoned Iec Long Firecracker Factory in Taipa Center, Macau has been on hold formany years and has also been used as a war game venue that resulted in scratches on thewalls of the dilapidated old heritage buildings. Recently, the Macau government has finalizedits plans for the revitalization of this local heritage site. Due to its dispersed layout andsurrounding landscape, there are some design constraints around the preservation of thisimportant heritage site. The design for high cultural value land should not only consider thepreservation and renovation of old buildings but also consider more ways to effectively usethe site as an important public venue for the city.For developing the methodologies of this project, several concepts and case studies wereanalyzed to extract ideas that can be referenced and to unveil strategies for designing apossible solution to this problem. This dissertation intends to create a model for developingand integrating architectural design into this heritage site and will study the spacearrangements for both the indoor space and the outdoor space within the concept of afragmented space integration. Fragmented space, means that a place is designed using adecentralized layout. This conceptualization of a design can preserves the original appearance of the cultural value of land and at the same time, the space can be used moreefficiently to create a circulation for the public to visit and enjoy the location
Keywords: Theses and Dissertations Master of Architecture (MARCH); University of Saint Joseph; articulation architecture; decentralized layout; functional museum; integration with architecture; spatial narrative

CUSTOM CLUSTER: DEMAND-DRIVEN VERTICAL HOUSING ARCHITECTURE - Un, Ka Kin (University of Saint Joseph, 2023)
Vertical housing is essential for modern cities because of its efficiency in using space (Wang, J. Murakami, A. 2019). The architecture of vertical housing is often determined by developers and designers. Therefore, the architecture of the building is fixed, and the end users are not involved nor can they influence its final appearance. For residential buildings, the unit sizes are based on market demand at a given point in time, which does not reflect the dynamic needs of the population as they evolve and may result in a mismatch between the supply and the demand for housing. The design of housing towers that have demographic characteristics and family size is dependent on housing size and can be very uncharacteristic and repetitive. The research question identified and addressed in this study is: How can residential buildings meet the evolving demand for housing units? Based on this question, this research paper develops a prototype for residential to resolve the dilemma between the supply and the demand in terms of the apartment size and layout. This research is a project-oriented project that focuses on residential that reflects the different family sizes required to be housed in the building and is combined with the open building method to maximize building performance. Ultimately, this research represents a meaningful innovation for market-driven architecture and defines architectural design based on the changing needs of the population using the open construction method. It also provides an opportunity to improve the design efficiency and develop a method for future growth, upgrades, and user needs. It may also be able to reflect the current housing ratio of the residential building. This work can be further explored to verify its effectiveness for other housing types and community living spaces
Keywords: Theses and Dissertations Master of Architecture (MARCH); University of Saint Joseph; Vertical residential design; demand-driven architecture; form follows function; open building; residential clusters; stacking design

Comparative study: The Human rights situation in China, the USA and Europe - Chu, Pok Tou; Lao-Phillips, Jenny Oliveros (University of Saint Joseph, 2023)
This thesis mainly discusses and compares the human rights situation and the problems in China, the USA and the UK. Also, the thesis will give the solution of how to make the world's human rights situation more fairly. Because we sometimes listen to these countries use cruel ways to suppress the opponents from the news. So I think this will be very suitable for understanding the current human rights situation, problems and movements in these countries. This thesis mainly uses the secondary data analysis method to collect and analyse the data. After analysing the data, three main issues affecting human rights were identified. These issues are race, religion, and network privacy. Other important factors still influence human rights, but this dissertation focused on the three issues identified. Finally, I will give two to three recommendations to practice human rights more fairly. Although the step will be very small, we can greatly improve the fair human rights in the future
Keywords: China; Europe; Human rights; Human rights situation; Thesis and Dissertations Master of Government Studies (MGS); USA; United Kingdom; University of Saint Joseph

TURNING THE SDGS INTO LEGAL COMMITMENTS: Catarine Isabel Pereira Batista - Batista, Catarine Isabel Pereira (University of Saint Joseph, 2024)
This dissertation examines the current implementation of specific Sustainable Development Goals (SDGs) within the Macau legal system, despite the non-mandatory nature of these goals and how they were implemented. The SDGs, established by the United Nations, provide a comprehensive framework for addressing global social, economic, and environmental challenges. While Macau is not obliged to adopt the SDGs, this study aims to explore the extent to which the principles and objectives of specific SDGs have been integrated into the legal system of Macau. Through an analysis of relevant laws, and policies, this research seeks to identify alignment and visible gaps between the SDGs and the Macau legal framework. The findings of this study may contribute to a deeper understanding of the voluntary implementation of the SDGs in Macau and provide insights for other jurisdictions facing similar circumstances
Keywords: Hard Law; International Law; Legal system; Macau SAR; Soft Law; Sustainable development goals; Thesis and Dissertations Master of Lusophone and International Public Law(MLIPL); University of Saint Joseph

Innovation Analysis and Research on the Mode of KOL Live Commerce - Fong, Hou Man (University of Saint Joseph, 2024)
With the rapid development of digital media, internet celebrity live streaming has become a key factor in influencing the consumer decision-making of adolescents, presenting unique regional characteristics in different socio-cultural and economic contexts. This study investigates the differences in consumption habits among adolescents in Macau and Mainland China and their impact on the innovation and reform of the commercial model of internet celebrity live streaming. The methodology employs a questionnaire survey and data analysis to systematically compare the consumption behavior of adolescents in Macao and mainland China, collecting live streaming consumption habits of adolescents in both regions. Statistical methods are used to compare and analyze the consumption patterns within the regions. The analysis indicates that influencers, as internet celebrities with a large number of fans on social media, have a significant impact on adolescents' consumption decisions through their recommendations and evaluations. Firstly, the convenience and diversity of e-commerce platforms provide adolescents with a wealth of consumption choices, such as characteristics and usage effects of products. Secondly, the recommendations and evaluations of influencers have become an important reference for adolescents' consumption. Results show that adolescents in Macau tend to seek entertainment and interaction in their consumption of internet celebrity live streaming, whereas those in Mainland China place greater emphasis on the practicality of the live streaming content and the cost-effectiveness of the products. Moreover, the study reveals the roles of socio-cultural and economic levels in the differences in consumption between the two regions. Based on these insights, it is recommended that live streaming platforms should advance the innovation and reform of their business models to cater to different market characteristics—such as optimizing content recommendation algorithms, enhancing interactive elements, and improving the integration of e-commerce features, thereby promoting business sustainability and economic benefits
Keywords: Adolescent Consumption Habits; Internet Celebrity; Live Streaming; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

NEUROFINANCE - ANALYZING AND UNDERSTANDING STOCK TRADER’S DECISION-MAKING PROCESS BASED ON REAL-TIME MONITORING OF EMOTIONAL REACTIONS - Hsu, Hsin-Tzu (University of Saint Joseph, 2023)
Human emotions can be meticulously associated with decision-making, and emotion can generate behaviours. Due to the fact that it could be bias and exhaustively complex to examine how human beings make choices, important groups of study in finance are stock traders and non-traders. The objective of this work is to analyze the connection between emotions and the decision-making process of investors and non-investors to understand how emotional arousal might dictate the process of deciding policy. As facial expressions are fleeting, neuroscience tools such as AFFDEX (Real-Time Facial Expression Analysis), Eye-Tracking, and GSR (galvanic skin response) were adopted to facilitate the experiment and its accompanying analysis process. Thirty-seven participants attended the study, ranging from 18 to 72 years old; the distribution of investors and non-investors was twenty-four and thirteen, respectively. The experiment initially disclosed a thought-provoking result between the two groups under the certainty and risk-seeking prospect theory; there were more risk-takers among non-investors at 75%, while investors were inclined toward certainty at 79.17%. The implication could be that the non-investing individuals were less complex in thought and therefore pursued higher returns besides a high probability of losing the game. In addition, the automatic emotion classification system indicates that when non-investors confronted a stock trending chart beyond their acquaintance or knowledge, they were psychologically exposed to fear, anger, sadness, and surprise. Investors, on the contrary, were detected with disgust, joy, contempt, engagement, sadness, and surprise, where sadness and surprise overlapped in both parties. Under time pressure conditions, 54.05% of investors or non-investors tend to make decisions after the peak(s) of emotional arousal. Variations were found in the deciding points of the slopes: 2.70% were decided right after the peak(s), 37.84% waited until the emotions turned stable, and 13.51% were determined as the emotional indicators started to slide downwards. Several combinations of emotional responses were associated with decisions. For example, negative emotions could induce passive decision-making, in this case, to sell the stock; nevertheless, it was also examined that as the slope slipped downwards to a particular horizontal point, the individuals became more optimistic and selected the "BUY" option. The support of physiological monitoring tools makes it possible to capture the individuals' responses and discover the science of decision-making. Future works may consider expanding the study to more significant demographic populations for further discoveries
Keywords: Decision-making; Emotions; Investors; Physiological Monitoring; Stock Trading; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

INFLUENCE OF ORGANIZATIONAL CULTURE ON WORK ENGAGEMENT: A MEDIATING ROLE OF JOB SATISFACTION IN MACAU SIX GAMING CONCESSIONAIRES - Wong, Ka Son (University of Saint Joseph, 2024)
The Macau six gaming concessionaires are encouraged to diversify their business activities beyond the gaming sector to promote a more balanced economy in Macau. It is worth noting that a substantial portion of the workforce within these organizations is employed in non-gaming sectors. Unlike previous studies that primarily concentrated on the gaming sector, this study aims to assess the extent of work engagement among all employees, encompassing both gaming and non-gaming employees, within the six gaming concessionaires of Macau. It also aims to explore the correlation between organizational culture and work engagement, as well as the mediating role of job satisfaction in this relationship. The survey design utilized convenience and referral sampling methods to select the sample. A quantitative approach was employed, and data was collected through an online self-response questionnaire with a total of 396 participants. The study findings reveal a positive correlation among all variables, with a particularly strong relationship observed between supportive organizational culture and various aspects of work engagement. Notably, the mediating variable of job satisfaction, specifically the nature of work, had a more significant impact than the direct effect of organizational culture on emotional and physical work engagement. These findings suggest that organizations should prioritize the development of a supportive organizational culture to enhance work engagement. Furthermore, it is crucial to provide employees with motivating and meaningful work that gives them a sense of accomplishment upon completion. Future studies could explore the relationship between organizational culture and work engagement by examining two distinct employee groups, such as local employees and expatriates
Keywords: Job Satisfaction; Macau Gaming Concessionaires; Nature of Work; Organizational Culture; Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph; Work Engagement

SOCIAL MEDIA AND UNIVERSITY STUDENTS' PERSPECTIVE OF RELIGION: A COMPARATIVE STUDY OF EVERY NATION IN THE PHILIPPINES AND MACAU - Tabilas, Analeah Marie R. (University of Saint Joseph, 2024)
This research analyzed and compared the Instagram content of Victory Philippines and Every Nation Manila to evaluate its impact on the faith perception of university students associated with these churches. In this digital age, institutions have embraced the shift towards online interactions, including adapting religious practices such as worship services to online platforms. Religious organizations are navigating the dynamics between online and offline communication methods as they adapt to engaging with their audience through social media channels. While previous research has delved into online religious content and virtual church services, no prior studies have specifically compared the social media communication strategies of Every Nation churches in Manila, Philippines, and Macau. The research employed a mixed-method approach, compromising interviews, focus groups, and quantitative content analysis. As per the interviews, these took place with four pastors and four media content creators within the Metro Manila region of Every Nation Philippines, commonly recognized as Victory Philippines, and one pastor and one content creator of Every Nation Macau. These interviews helped gather insights into their thought processes and analyze their social media strategies and plans. Three distinct focus group discussions were carried out, involving 15 undergraduate students from Manila and Macau affiliated with Victory Philippines and Every Nation Macau. The participants were equally divided into three groups. These students also actively engage with the Victory Philippines and Every Nation Macau Instagram posts. These focus group discussions were employed to analyze patterns to understand their thought processes. Furthermore, a quantitative content analysis was carried out on Victory Philippines and Every Nation’s Instagram account as part of the study. Despite the active engagement on social media platforms by Victory Philippines and Every Nation Macau, both organizations maintained a strong offline church community. Interviews conducted indicated that the online activities of these churches significantly influenced the faith of students, while their spiritual growth was further supported by an inclusive offline community. This approach exemplified a multi-generational ethos, fostering collaboration between younger and older members towards the shared objective of evangelism. This research validates the Figuring and Disfiguring theoretical framework of Taylor (2007, apud Åhman and Thorén, 2021). The results of the empirical data may provide strong practical guidance to churches of any size as they build and develop their online presence while strengthening their offline presence
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

EFFECT OF EMPLOYEE PERFORMANCE MANAGEMENT ON EMPLOYEE INCENTIVE: A CASE STUDY OF N COMPANY - Xie, Yue Na (University of Saint Joseph, 2024)
With the comprehensive opening of the global economy, the intensification of market competition and the increasingly prominent value of human resources, all trades and professions are facing unprecedented challenges. In order to remain competitive in the market, human resource management plays an increasingly important role. As an important part of human resource management, enterprise performance management can be used as a key tool to drive the release of employees' potential, which has attracted more and more attention from enterprises. More and more performance management-related systems have been introduced into enterprises. However, in the system introduction and implementation process, there are different degrees of problems, such as ""mechanically copied"" and ""process"". Therefore, according to the specific situation of different enterprises, it is necessary to formulate the corresponding performance management system to maximize the role of motivating employees. This paper explores enterprise performance management's influence on the employee incentive effect. The implementation of enterprise performance management and its influence on employee incentive are analyzed through the literature review, case analysis and empirical analysis. Research has found that effective enterprise performance management can significantly improve the work enthusiasm and satisfaction of employees, thus enhancing the overall performance of enterprises and promoting all-round development. At the same time, this paper also discusses the key factors affecting the incentive effect of enterprise performance management, and puts forward the corresponding optimization suggestions
Keywords: TCA; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph; performace management; performance incentive

EXPLORE THE EFFECT OF ORGANIZATIONAL CULTURE AND ORGANIZATIONAL LEADERSHIP ON EMPLOYEE ENGAGEMENT: THE MODERATING ROLE OF ORGANIZATIONAL COMMITMENT IN PUBLIC SECTOR AND GAMING SECTOR IN MACAU - Iu, Pek Wa (University of Saint Joseph, 2024)
The current study examined responses from 342 full-time and part-time employees in Macau’s gaming and public sector. The intention was to examine the relationship and explore the effect of organizational culture (innovative, supportive, and bureaucratic) and organizational leadership (transformational and transactional) on employee work engagement (cognitive, emotional, and physical) with the moderating role of organizational commitment (affective and continuance). The objectives of this study are mainly: 1) to explore the relationship between organizational culture and leadership with employee engagement respectively; 2) to further investigate employee engagement and the difference between the gaming sector and the public sector, and 3) to explore the moderating role of organizational commitment between the organizational culture and leadership to employee engagement respectively. Understanding the relationship between these essential elements is crucial for the individual and organization which ultimately leads to a sustainable and utmost performance for the benefit of Macau's constant economic development. While regression analysis represented transformational leadership as the powerful predictor of the three facets of work engagement to employees in both sectors. Though there was no relationship between the variables and the moderators, there was a positive interaction between transformational leadership, affective commitment (TFL x AC), and emotional and physical work engagement of the employees from the gaming sector, there was a positive interaction between innovative culture, affective commitment (IC x AC) and cognitive work engagement and a negative interaction between transactional leadership, continuance commitment (TL x CC) and emotional work engagement in the public sector subgroup. Results were interpreted concerning the organizations, leaders, and employees in both sectors in Macau, followed by a discussion on the implications of enhancing work engagement
Keywords: Macau; Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph; gaming sector; organizational commitment; organizational culture; organizational leadership; public sector; work engagement

ORGANIZATIONAL JUSTICE AND PSYCHOLOGICAL WELL-BEING AMONG HEALTHCARE WORKERS IN MACAO - Kaewmanee, Celina dos Santos (University of Saint Joseph, 2023)
This study examined the relationships between organizational justice, job satisfaction, and subjective well-being of medical doctors and nurses in Macao. It applied a quantitative methodology through a cross-sectional applying self-response questionnaires to 149 healthcare workers. Consistent with the group-engagement model (Tyler & Blader, 2003), findings indicate that organisational justice and job satisfaction improve subjective well-being. Yet, inconsistent with the model and our hypotheses, organizational justice did not affect work satisfaction. Finally, nurses experienced less positive justice perceptions than doctors. The study provides insights into the relationship between organizational justice, job satisfaction, and subjective well-being among healthcare professionals, which might help enhance working conditions. Healthcare organizations should prioritize promoting job satisfaction and justice perceptions to increase healthcare personnel's subjective well-being. The cross-sectional design limits causal inferences about variable relationships, and the self-reported data may have social desirability or response biases. Still, the originality and value of this paper lie in its contribution to the literature on the well-being of healthcare workers, particularly in the unique context of Macao. To our knowledge, this is the first study in Macao to examine the relationship between organizational justice, job satisfaction, and subjective well-being among healthcare workers
Keywords: Healthcare; Job Satisfaction; Organizational Justice; Subjective well-being; Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

Emotional Support Influence Work Engagement and Mental Well-being in Macau: The Moderating Effect of Self-reflection - Sou, Kam Chan; Kuok, Angus C. H. (University of Saint Joseph, 2023)
The purpose of this study is to examine work engagement and mental well-being in Macau, specifically after more than three years of COVID. Examine whether external factors such as emotional support from supervisors, co-workers, and family members have a positive impact on work engagement and mental well-being, and whether the internal factor self-reflection with its three aspects of need for self-reflection, engagement in self-reflection, and insight from self-reflection moderates the relationship between emotional support, work engagement, and mental well-being. The target audience consists of Macau's integrated resort, hospitality, and gaming industry employees. According to the Affective Event Theory (AET), affective events at work generate emotional responses that influence the attitudes and behavior of employees in the workplace. In this study, this theoretical framework was used to clarify the interplay of variables that explain emotional support from supervisors, co-workers, and family members, work engagement, and mental well-being. An online self-response survey (N=325) was used to conduct quantitative and cross-sectional research. There was also a combination of simple random sampling, convenience sampling, and referral sampling. All variables were found to be correlated, and while perceived supervisor support was a significant predictor of all aspects of work engagement and mental well-being, family and co-worker support only predicted certain aspects of these variables. Self-reflection partially moderated the positive effects of certain emotional support on work engagement and mental well-being
Keywords: Co-worker Support; Emotional Support; Family Support; Mental Well-being; Perceived Supervisor Support; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; Work Engagement

Can The Organisation Help? Exploring The Relationship Between Emotional Intelligence, Resilience And Burnout Among Counselling Professionals With Organisational Socialisation As Moderator - Mak, Sin Kei (University of Saint Joseph, 2023)
The phenomenon of burnout has been recognised as a worldwide occupational health issue after being vastly studied for decades. Trait Emotional Intelligence (trait EI) and resilience have been identified as personal protective factors (Gutierrez & Mullen, 2016; Listopad et al., 2021), while organisational socialisation is suggested to be an organisational factor in helping people in preventing burnout (Taormina & Law, 2000). With the purpose of 1) investigating the phenomenon in the counselling profession, as well as 2) exploring how trait EI and resilience are related to burnout and whether organisational socialisation might impose moderating effects in between, the present study examined 115 counselling professionals currently employed and working in organisational settings in Macau by snowball sampling, using a quantitative and cross-sectional approach through self-reported online questionnaires. From the data obtained, different burnout patterns were observed according to job titles and work settings, indicating that counselling professionals with different specialties and work in different settings have unique sources of stress, which resulting in differences in their burnout patterns. No between-group differences were observed in age and work experience, while male participants have a higher burnout perception than female participants in the current study. On the other hand, current results suggested trait EI and four components of resilience (determination, endurance, adaptability and recuperability) are negatively correlated to counselling professionals’ burnout perception, providing supportive evidence that trait EI and resilience are protective factors against burnout. Moderation analysis results revealed that organisational socialisation has some moderating effects on the relationship between trait EI, resilience and burnout. However, differences in direction and intensity indicated that the moderating effects of organisational socialisation might be influenced by individual differences. Further studies are needed to better the understanding of the moderating effect of organisational socialisation. Limitations of the current research and implications for counselling professionals and organisations were also discussed in the study
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph; burnout; counselling professionals; organisational socialisation

A STUDY OF RELATIONSHIPS BETWEEN JOB AUTONOMY, ORGANISATIONAL JUSTICE, ORGANISATIONAL CULTURE AND EMPLOYEE ENGAGEMENT IN MACAU - Cheong, Wan Sze (University of Saint Joseph, 2024)
With the increasing number of tourists coming to Macau after the three years of lockdown period, more quality services are expected. However, organisations are now facing a big challenge in maintaining sufficient employee, managing their employees’ performance and productivity. Employee engagement plays an important role because it will not only affect individual performance but also the performance of an organisation. This is the first study to provide evidence of the engagement level of general employees working in Macau, and of its relationships with job autonomy, organisational justice and organisational culture. The study results revealed that the levels of vigour, dedication and absorption of employees working full time in Macau were slightly above the mid-point value 3 of the scale, with about 30% of employees were found less engaged or disengaged. Criteria autonomy, method autonomy, schedule autonomy, organisational justice and collectivism culture were positively and significantly correlated with all three dimensions of employee engagement (i.e. vigour, dedication and absorption). There is no significant negative relationship between power distance culture and employee engagement. Method autonomy was the strongest positive predictor of all three dimensions of employee engagement, followed by organisational justice, while collectivism culture was a positive predictor for vigour and absorption. The implications for management will be discussed in terms of organisational support and communication
Keywords: Employee engagement; Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph; autonomy; organisation al justice; organisational culture

Research on Risk Management Practices and Countermeasures of Overseas Operations in State-owned Enterprises - Wang, Huan Huan (University of Saint Joseph, 2024)
In the current context of intensified economic globalization, Chinese state-owned enterprises (SOEs) have actively responded to the "Belt and Road" initiative by expanding their overseas operations, seeking new growth points through competition and cooperation in the global market. However, along with opportunities come the necessity for risk management in the overseas operations of SOEs. Based on theories of systematic and non-systematic risks, this thesis employs methods such as case study analysis and multiple linear regression to thoroughly examine key risk types in SOEs’ overseas operations, including political risks and exchange rate risks. Using quantitative models like the Analytic Hierarchy Process (AHP) and neural network early-warning models, the thesis empirically tests the effectiveness of mechanisms for risk identification, assessment, and control. Data sources include national statistics and corporate annual reports, and techniques such as Principal Component Analysis (PCA) and cluster analysis are applied to reveal statistical characteristics of risk factors and the internal and external linkage mechanisms of risk events. The thesis points out that the management of risks in overseas operations of SOEs not only relies on scientific assessment and precise early warning but also requires the establishment of a risk management framework and governance system that aligns with international rules. Through in-depth analysis of the overseas operations of enterprises like PetroChina and Huawei, the thesis distills strategies for risk prevention and control, such as diversified investment strategies and the construction of compliance risk control systems, and conducts a comprehensive evaluation of the current risk management system, proposing pathways for sustainable development. The outcomes of the research aim to help SOEs enhance their level of risk management, ensure national economic security, and also provide theoretical guidance and practical reference for the implementation of international strategies by SOEs
Keywords: Overseas operation; Risk assessment; Risk control; Risk management; State-owned enterprise; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

PROJECT MANAGEMENT ADOPTION AND MATURITY LEVEL IN INFORMATION TECHNOLOGY INDUSTRY OF MACAU AND HENGQIN - Wong, Ka Seng (University of Saint Joseph, 2023)
Projects are tactical and operational initiatives, and achieving specific outcomes through projects can help organizations achieve strategic goals. The effective use of project management tools and techniques is essential to achieve successful results, since the goal is to maximize the realization of the project's plan by effectively using the budget, time, and resources provided by the project owner to achieve the project's original purpose. The Project Management Maturity Model (PMMM) is a tool for measuring project management capabilities and is essential to improve project and portfolio performance in different industries. The main objective of this research is to analyze and characterize the maturity level and capacity of the IT industry in Macau and HengQin based on the assessment of the PMMM. The research also aims to assess and compare the maturity level in the IT industry in Macau and HengQin. An online survey was conducted and sent to IT project managers from Macau and HenqQin. A total of 34 responses were collected, divided into 3 different parts: Part I - General Information, Part II - Project Management Areas, and Part III - Perception. The results indicate that, in general, Project Managers state that their companies do not follow Project Management standards and best practices, classifying as Low and Very Low essential PM areas such as Planning and Scheduling (68%), Scope (61%) and Communications (64%). From a comparison perspective, project managers in Macau follow less formal frameworks than Hengqin in managing the triple constraints of the project. The collected data also indicate that Macau's communication management and stakeholder engagement are less mature than Hengqin's. Furthermore, the data indicate that maturity level is not necessarily related to education level, which means not higher education has a higher maturity level. Recommendations are provided for the IT industry in both areas, and specific comments are provided for each group or professionals. In conclusion, this work allows a novel characterization and a better understanding of the Project Management adoption and maturity level of the IT Industry in Macau and Hengqin
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph; information technology; maturity level; project management; project management maturity model; project maturity assessment

Consumer purchase intention towards floral products: a study based on the five consumption values - Lei, Si Nga (University of Saint Joseph, 2023)
This dissertation focused on the consumers’ consumption behavior in Macau flower retailers. It revealed what factors affect consumers’ choice of flower shops during purchase. Also, what contributes to the customers’ loyalty towards a flower retailer by having interviews with the female target groups aged between 20 to 50 who work in the office. This study is important to the flower business owner because the result can allow them to understand the thoughts and feelings of their consumer. By interviewing 11 heavy users of floral products with 16 questions based on the five consumption values, we can communicate with the consumers directly and learn the reasons behind their purchasing behavior. Questions have been divided into 5 consumption values according to the previous research by (Sheth, Newman, & Gros, 1991), including functional, conditional, social, emotional, and epistemic values. The research has collected data on how and at what level these values may affect consumer consumption choices individually. The finding part analyzed the reason why those values affect consumers’ choices. Most of the interviewees stated that service is the most important compared to quality because the owner should be enthusiastic to provide product information and understand the consumer very well to impress and retain them with good personal service
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; consumption behavior; floral product; purchase intention

The attractiveness of Taobao: why do people always come back despite negative feedback - Chan, Nga Man (University of Saint Joseph, 2023)
Online shopping in Macau has developed rapidly in recent years. And the success of Taobao is significantly hard to not notice. Its’ sales are breaking the record every year. However, there are a lot of negative comments towards Taobao. Various researches and data have shown that live-streaming is one of the biggest contributions towards Taobao’s sales and record breaking. This research aims to investigate deeply to understand how Taobao counters those issues and the role of live-streaming in relation to it. Based on a review of the literature in the relevant areas , qualitative methodology is adopted after thorough considerations. A small sample size of 10 were selected to conduct semi-structured in-depth interviews and the participants agreed to respond to answer the original interview questions and the follow-up questions. Analysis of the responses demonstrated e-customer service is the most influential variable towards repurchase intention. Live-streaming strategy can effectively and directly reduce constomer’s uncertainty of products and increase the efficiency of responsiveness. And product uncertainty and responsiveness speed are variables that impact purchase intention. The result demonstrated live-streaming's effectiveness in combating multiple negative aspects of Taobao and strengthening the positive aspects. On this basis, live-streaming is an impactful method to combat Taobao. In addition, e-service in terms of sufficiency of the staff’s communication skill have been found important towards customer’s satisfaction. A gap related to such an issue has been recommended in the further research recommendations along with other factors or sample groups, which are needed to explore deeply in the future
Keywords: Authenticity; Customer satisfaction; E- Service quality; Repurchase intention; Taobao; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Strategy Christian Chruches Use in Marketing and Building Brand in Macau: A Case Study of Macau Baptist Church - Chan, Ka Yue (University of Saint Joseph, 2024)
This research chooses Macau Baptist Church in Macau as the research object, studying the brand and marketing strategy adopted by the church and determining what is essential for Christian churches when they do marketing to build brand awareness. Branding is essential in church communication mechanisms to recruit members and build loyal membership to reach sustainability. This topic is a relatively new study in the research field; the Macau Baptist Church case filled the gap of lack of Asia sampling and provided the perspective from the Baptist in branding church. The research sets off to answer the question of what marketing strategies Christian churches in Macau can adopt to build brand awareness, adopting a qualitative case study research method. The primary data was collected through in-depth interviews with leaders involved and included in the marketing effort of recruitment and evangelisation in Macau Baptist Church. Secondary materials are analysed and collected through printed materials published by Macau Baptist Church, an online social media platform and monthly meeting minutes. Participant observation notes are used in the process of analysing the effectiveness of the strategy used by the church. In branding a Christian church, the key is to understand and accurately interpret the church identity and build a God-centred church to help attendees have a strong relationship with God with the a posteriori of understanding the word of God. A priori experience with God through the services and evangelical campaigns hold by the church. Then, the vision and mission, goal setting, review, and reform will be determined so the church can sustain itself in modern days and achieve church growth
Keywords: Asian church marketing; Church branding; Church marketing; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Impact of Monetary Rewards and Employees’ Benefits on Frontline Staff Motivation in the Retail Industry - Ho, Un Ian (University of Saint Joseph, 2024)
Macau's retail industry was familiar to all sectors. Retailers take up massive responsibility for the Macau economy. There are few manufacturers in Macau, so products and goods are imported. As the front-line staff of a retail store, employees would need to face many people daily; it can be tiring and stressful for them. Therefore, this study examined the motivational factors of front-line staff in the retail industry. It is crucial to understand various motivational factors, as one of the challenges that retail entrepreneurs face is employee retention. This study evaluated the characteristics of motivation so that managers can develop some strategies for their employees. The qualitative research method was adopted in this study. In-depth interviews were conducted to determine various motivators and the reasons behind their motivation. This study used purposive sampling, and eight candidates were selected to conduct the interview. The results of the interviews concluded that monetary rewards like salary and sales incentives have the most significant effect on motivation. Relationships with colleagues and superiors also affect their motivation in the working environment. Moreover, employee benefits like public holidays, maternity leave, etc, are also one of the motivators. Different participants mentioned other motivators, such as recognition, teamwork, learning and growth opportunities, teamwork, and fit of interest. Based on the research question, this study concluded that monetary rewards have a larger effect on employees' motivation than job benefits. Managers and leaders can develop strategies based on this research, and future research can also examine some other motivational factors with a larger sample
Keywords: Frontline Staff; Macau Retail; Motivation; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

THE VALUATION OF WALMART INC - Wong, Nga Man (University of Saint Joseph, 2024)
A world-class retailer, Walmart Inc. (WMT) operates in multiple formats, including physical and online stores. Walmart began operations in 1962 and currently owns 10,616 merchandise units around the world. Most of Walmart's revenue comes from the United States segment, 17% from the Walmart International segment, and 14% from the Sam's Club segment. Walmart offers many products, such as groceries, consumables, general merchandise, and health products. With its marketing strategy of low-cost products, Walmart has successfully navigated through economic prosperity and recessions in different periods. However, there is still intense competition in the retail industry, so we will analyze the company's internal factors across the economic climate and external factors and see how the company positioned itself to adapt to the trends in the industry to achieve the current intrinsic value. Three valuation models have been completed to determine Walmart’s intrinsic value. We will then compare that figure with WMT's stock price at the end of fiscal year 2022, which will benefit investors by providing valuable reference information
Keywords: Master of Business Administration; THE VALUATION OF WALMART INC; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; VALUATION; Walmart

THE IMPACT OF WORLD HEALTH ORGANIZATION’S OFFICIAL ANNOUNCEMENTS ON PHARMACEUTICAL COMPANIES STOCK RETURNS - Iam, Hou In (University of Saint Joseph, 2024)
In early 2020, the COVID-19 virus spread rapidly around the world within months. After countries around the world announced the outbreak of COVID-19, many industries suffered a severe recession, but a few industries were able to buck the trend and maintain good performance. The outbreak has driven strong demand for medical products and pharmaceuticals. As the epidemic continues to spread, people are in urgent need of drugs and vaccines to treat COVID-19, which directly promotes the development of the pharmaceutical industry (Alam et al., 2021). This study aims to explore the impact of announcements from the World Health Organization (WHO) or similar official agencies on the development of the epidemic during the COVID-19 epidemic on the stock prices of specific pharmaceutical companies. The study uses event study methodology to analyze the impact of events in the COVID-19 pandemic on these companies. Through an event study on 7 major events during the COVID-19 pandemic, this study found that the stock price changes of different pharmaceutical companies are not uniform. The WHO announcement of a global pandemic and the emergency authorization announcement of drugs have had different significant impacts on different types of pharmaceutical companies. This study provides new information for understanding the stock return change of specific pharmaceutical companies during the COVID-19 epidemic
Keywords: COVID-19; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph; pharmaceutical; stock returns

COMPARATIVE ANALYSIS IN TELEVISION JOURNALISM “TDM (TELEDIFUSÃO DE MACAU, S.A) AND TVS (TELEVISÃO SANTOMENSE)” NEWSCAST CASE STUDIES - Pinho, Silvino Vaz Sacramento (University of Saint Joseph, 2024)
This study delves into the television news practices of TDM (Teledifusão de Macau, S.A.) and TVS (Televisão Santomense) over the past five years (2018-2023), using a systematic approach, this research begins with an introduction outlining the broadcasters' contexts and influences. A content analysis of a representative sample of news programs from both channels forms the core of the study. To gain deeper insights, the research employs a mixed methodological approach. Qualitative data is gathered through interviews with the chief journalist of TVS and 150 residents from Água Grande and Cauê Districts (Angolares ). Additionally, a quantitative analysis is conducted through an online survey targeting the Community of Portuguese-speaking Countries in Macao, garnering 150 responses. The findings highlight the need for improvements to increase viewership. While both broadcasters cover similar news topics (politics, economics, social issues), their presentation styles differ. TDM and TVS adopt a formal and structured approach, but their visual storytelling techniques reflect cultural and regional preferences. The study then interprets the results, examining historical context, cultural influences, and audience preferences to understand the divergent approaches to television journalism. This comprehensive analysis provides valuable insights to enhance news viewership and offers a deeper understanding of the factors shaping television journalism in these two distinct contexts
Keywords: Macao; Media; Sao Tome and Principe; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph; newscasts; television journalism

THE MODERATING EFFECTS OF POWER DISTANCE ON THE RELATIONSHIP BETWEEN PERCEPTIONS OF ORGANISATIONAL POLITICS AND ORGANISATIONAL JUSTICE - Kong, Fion Ming Ying (University of Saint Joseph, 2023)
The aim of this research is to investigate how power distance orientation effects the relationship between perceptions of organisational politics and perceptions of organisational justice. A quantitative cross-sectional study was conducted on 172 full time workers in Macau, where respondents self-responded to questionnaires that were translated back-to-back into Chinese in order to accommodate the populations native language. This study found that power distance was contrary to our initial hypothesis of high-power distance equals to high politics and low justice. It was found that high power distance in facts equates to lower political perceptions and higher justice perceptions. This study contributes to understanding power distance in Macau as it is not noted in the Hofstede cultural dimensions. We also learned that having a longer distance between a position of power can contribute to less political activity and more sense of justice for the employees
Keywords: Organisational Justice; Organisational Politics; Power Distance; Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

A Financial Valuation of 3M Company (MMM) - Ao, Man Leng (University of Saint Joseph, 2024)
To evaluate 3M's intrinsic value and compare the calculated results with the stock market price as of 31 December 2022. To study 3M's future operating strategies and the internal and external factors that may impact the Company's operations
Keywords: Financial Valuation; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A FINANCIAL VALUATION OF ORACLE CORPORATION - Maung, Ye Thu Anug (University of Saint Joseph, 2023)
Oracle Corporation (hereinafter referred to as Oracle, ORCL, or ‘the Company’) is an American multinational company that provides solutions of products and services that serve the enterprises’ information technology (IT) environment. This thesis is to conduct a business analysis of the Company from a financial perspective, determining the Company’s intrinsic value as of May 31, 2021, and comparing it with the respective market value. Thus, this thesis will study, evaluate, and present an overview of the Company, an analysis of the Company’s market, industry, strategy, financial performance, including external and internal factors, a ten-year pro forma financial statement forecast, and the techniques of using the three discounted cash flow models to estimate the intrinsic value of Oracle. The obtained results from the three valuation models, including the Enterprise Discounted Cash Flow (EDCF) model, the Adjusted Present Value (APV) model, and the Discounted Economic Profit (DEP) model, show that the Company’s intrinsic values were estimated at $74.57, $75.21, and $74.82, respectively. When the results were used to compare with the market price of Oracle’s shares as of May 31, 2021, at $78.74, it reflects that the Company was overvalued
Keywords: Analysis; Financial Valuation; Oracle Corporation; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

MULTICULTURAL CAREGIVER TEAMS IN ELDERLY CENTRES IN MACAO: COMMUNICATION AND PERCEIVED SERVICE QUALITY - Mejia Dominguez, Victor Alejandro (University of Saint Joseph, 2023)
This study explored the effect of communication (i.e., among staff, and between staff and clients) and of cultural diversity on job satisfaction (i.e., intrinsic, extrinsic, and general) and perceived service quality of formal caregivers working in elderly services in Macao. We applied a quantitative methodology, based on a cross-sectional design using a self-response questionnaire to 162 staff in six elderly centres in Macao. Based on an extensive review of the literature, we proposed that: H1) cultural diversity is negatively related to (a) intrinsic job satisfaction, (b) extrinsic job satisfaction, (c) general job satisfaction, and (H5) negatively related to perceived competence and service quality; (H2) communication (a) among staff and (b) between staff and clients is positively related to intrinsic job satisfaction (H3) extrinsic job satisfaction, (H4) general job satisfaction, and (H6) perceived service quality; and finally that (H7) intrinsic, (H8) extrinsic, and (H9) general job satisfaction mediate the relationship between (a) cultural diversity, (b) communication among staff and (c) communication between staff and clients, and perceived service quality. We found that more communication among staff was related to higher intrinsic, extrinsic and general job satisfaction, and perceived competence and service quality. And intrinsic job satisfaction mediated the positive effect of communication among staff on perceived service quality. Opposite to predicted communication between staff and clients was related to lower levels of job satisfaction. And cultural diversity was positively related to satisfaction, as well as perceived competence and service quality. The theoretical and practical implications of findings, as well as limitations and suggestions for future research were discussed
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph; caregivers; communication; elderly services; job satisfaction; multicultural teams; service quality

THE EFFECTS OF TEACHER SELF-EFFICACY AND PERCEIVED AUTONOMY ON TEACHER WORK ENGAGEMENT: THE MEDIATING EFFECT OF PERCEIVED ORGANISATIONAL SUPPORT - Wan, Sok Leng (University of Saint Joseph, 2023)
The aims of the present study are to investigate the level of work engagement of the inclusive teachers in Macau and what potential factors would contribute to the increase of their level of work engagement. In this research, the framework of the self-determination theory developed by Ryan and Deci in 2000 was partially employed. I suggested the inclusive teachers’ self-efficacy and perceived autonomy to act as the independent variables, while perceived organisational support was involved as the mediating variable. Quantitative method was applied in this study by using an online self-response questionnaire (N= 150). The stratified sampling strategy was applied as well in order to ensure the representativeness. No gender difference of work engagement level was found among Macau inclusive teachers. Positive correlations were found among all variables. Besides, perceived organisational support was expressing positive mediating effects on the relationships between independent and dependent variables under some specific circumstances. For example, the relationship between efficacy to use inclusive instructions and emotional and physical work engagement; the relationship between perceived autonomy and cognitive, emotional, and physical work engagement. Theoretical and practical implications for the non-tertiary schools and inclusive teachers can be found in this study. Future studies should be continued to investigate the limitations and suggestions of this field of research
Keywords: PERCEIVED ORGANISATIONAL SUPPORT; TEACHER PERCEIVED AUTONOMY; TEACHER SELF-EFFICACY; Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph; WORK ENGAGEMENT

The 50 Reasons for Voluntary Turnover: A Qualitative Exploration of Factors Contributing to Former Teacher Attrition in Macau - Ao, I. Leng (University of Saint Joseph, 2023)
Teacher turnover is a global issue that has not received much research attention in Macau despite studies indicating that teachers in the region experience high levels of stress and burnout. Given that private school teachers account for a significant proportion (88.6%) of the non-tertiary education system in Macau, this qualitative study focused on this specific group who voluntarily resigned from their positions. Through in-depth interviews with 13 former teachers from different kindergartens, primary, and secondary schools, the research identified 50 reasons categorized into 15 factors under three categories. Although schoolrelated factors account for the most, personal reasons were found to be the primary driver. The findings of the study highlight the complex nature of teacher turnover which can be attributed to both single and multiple factors, in both direct and indirect forms. The factors could also interplay in both unidirectional and mutual relationships. A conceptual framework for teacher turnover in Macau was developed to address the 15 contributing factors and the complex interplay of these factors. This study could fill the gap in the literature and serve as a valuable resource for policymakers and school leaders seeking to reduce teacher attrition rates in the region
Keywords: Macau; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; leavers; teacher turnover

Integrating Internal Corporate Communication (ICC) Strategies to Enhance Occupational Safety and Health (OSH) Management: Chan Ka I - Chan, Ka I. (University of Saint Joseph, 2024)
This dissertation examines the relationship between internal corporate communication (ICC)strategies and occupational safety and health (OSH) Management practices in Macau's hospitality industry. The primary objective is to investigate how communication approaches can enhance workplace safety protocols and improve OSH outcomes for corporations in the leisure and entertainment sectors. The study aligns with Macau's several policies and economic development on promoting health and safety. It highlights the critical role of OSH Management in the post-COVID-19 business environment, influencing consumer choices and industry practices. The mixed-methods research identified critical success factors, including aligning OSH goals with corporate objectives, utilizing diverse communication platforms, and establishing a safety culture. Areas for improvement were also uncovered. The findings provide valuable insights for hospitality organizations, emphasizing the critical role of internal communication in driving effective OSH Management. By integrating communication strategies with OSH initiatives, organizations can cultivate a robust safety culture, ensure regulatory compliance, and enhance employee well-being and customer satisfaction - key factors for long-term business success
Keywords: Communication; Hospitality; Occupational Safety and Health; Organization; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Study on Influencing Factors of University Students' entrepreneurial Intention: Greater Bay Area as an example - Yu, Yuan Bao (University of Saint Joseph, 2024)
Keywords: Macro level; Micro level; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; college student; entrepreneurial Intention; entrepreneurship

Post-pandemic Human Resources Challenges in Macau’s Hospitality Industry: Christy, Chu Ian I - Chu, Ian I. (University of Saint Joseph, 2024)
In today's rapidly changing and fiercely competitive environment, talents are the key factor for a company's success and success, and a good strategy for retaining talents is how to use effective management measures to grasp employees' focus, vitality and service on work enthusiasm can generate dedication and loyalty to the enterprise, making the enterprise more consolidated and sustainable. Previous studies have shown that human resource management measures can increase employee contribution. Therefore, this study takes the important role of human resource management as an intermediary to explore how the human resource management of Macau's hospitality industry is affected by the COVID-19 pandemic and the changes in post-pandemic human resource management. At the same time, the company's commitment to its employees after the outbreak is further analyzed for the success of the solutions made by the human resource management of the hospitality industry in Macau. The research results are expected to be used as a reference for leaders or managers in the hospitality industry when an unexpected pandemic occurs, by enhancing and improving human resource management. The qualitative research method was adopted, and in-depth interviews were conducted with hotel employees. The key findings of this research were that there are five factors affecting human resource management post-pandemic in the hospitality industry. More importantly, we found that Macau’s hospitality industry needs to transform in the future, which will also have a key impact on human resources management
Keywords: Dilemmas 2; Diversified 1; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph; Vulnerabilities 3

Plugin Program Reconfigurable Architecture System For Sustainable Future - Au Yeung, Kam Sheung (University of Saint Joseph, 2023)
The primary research focus of this dissertation revolves around the concept of a "plugin" program. It raises a fundamental question about whether a building can attain long-term usability through metabolic flexibility (plugin units and their reconfigurable space), promoting adaptability (accommodating various program transfers), and meeting sustainable future criteria. Specifically, this dissertation inquires whether this "plugin" building design, with its reconfigurable units and metabolic system, can adapt to different spatial programs and become sustainable architecture
Keywords: Building program transfer; Metabolism Architecture; Plugin capsule units; Reconfigurable; Sustainable Architecture; Theses and Dissertations Master of Architecture (MARCH); University of Saint Joseph

EDUCATORS' PERSPECTIVE OF STUDENTS WITH SPECIAL EDUCATIONAL NEEDS (SEN) AND THEIR SENSE OF BELONGING, SELF-COMPETENCE, AND AGENCY - Carvalho, Edna Line Henriques de (University of Saint Joseph, 2024)
What strategies did educators use to cultivate a sense of belonging, self-competence, and agency among students with Special Educational Needs (SEN)? Did educators face any challenges in implementing these strategies? Were the findings of this study specific to the inclusive school in Macau, or can they be generalised to other educational settings? This study brings to light educators' inner perspective of students' sense of belonging, self-competence, and agency. Specifically, it aims to uncover the academic and emotional needs of students with SEN and the importance that these may have in promoting a positive educational experience. By gathering the perspectives of educators in an inclusive school in Macau who work side-by-side with these students daily, we can understand how essential these elements are in contributing to their overall development. The purposive sampling approach was used in this study to further investigate various experiences and perspectives of educators within an inclusive classroom setting. The educators interviewed provided insight into an inclusive classroom with students with SEN in full-time attendance. The educators sampled in this study facilitated the search for strategies, challenges and support systems to cultivate a sense of belonging, self-competence and agency, among students with SEN. Findings showed educators' understanding of the importance of students with SEN's sense of belonging, self-competence and agency. The educators' awareness of their students' interactions with peers, and the educators themselves, was prominent, revealing how the sense of belonging for students with SEN affected these relationships. Regarding students' sense of self-competence, according to educators, students with SEN had opportunities to showcase their confidence in specific classroom areas and to exercise independence in the classroom, within the set curriculum and lesson plans. In the findings, educators illuminated the importance of agency in students with SEN. However, they were apprehensive about changes in lesson plans, cultivating a fully independent classroom setting and providing choices to students with and without SEN. The study's implications highlight the educational practices and policies that effectively supplement students with SEN's academic and social environments. The findings of this study aim to guide curriculum developers, educators and parental figures in fostering positive learning experiences for students with diverse learning needs
Keywords: Heutagogy; SEN; Self-competence; Students' agency; Thesis and Dissertations Master of Education (MED); University of Saint Joseph

THE RELATIONSHIP BETWEEN PSYCHOPATHOLOGY AND RESILIENCE OF SECONDARY SCHOOL STUDENTS IN MACAO - Chan, Ngan Ieng (University of Saint Joseph, 2023)
School-age children and adolescents face several psychological conditions frequently associated with negative consequences on behavioral and mental problems. Their level of mental resilience may affect their responses to academic or interpersonal issues and coping with challenges, which in turn affects their mental health. This study aims to characterize the current status of the psychopathology and resilience of secondary students and to analyze the relationship between psychopathology and resilience in a sample of 80 girls aged 12–18 was selected by cluster sampling from one private secondary school with six grades in Macao. In this study, we used the Achenbach System of Empirically Based Assessment (ASEBA) to assess behavioral and emotional problems and the Resilience Scale for Chinese Adolescents to assess resilience. A total of 78 valid questionnaires were obtained for CBCL, 78 for TRF, 80 for YSR, and 77 for Resilience Scale and data were analyzed by using SPSS. The results reveal that clinical prevalence of Total Problems (YSR, 27.5% > CBCL, 19.2% > TRF, 15.4%) and Internalizing Problems (YSR, 22.5% > CBCL, 17.9% > TRF, 11.5%) from the perspective of adolescents was higher than that from the perspectives of parents and teachers. Senior students exhibited higher frequency on the borderline clinical range than Junior students. (χ2(2, N=80) =14.56, p<.001). The average score of resilience is 3.24±0.51, which is above the middle level. Regarding the YSR scale and Resilience scale, we found that the score of Affect Control is significantly negatively correlated with the score of Internalizing Problems (r = -.354, p<.01). Family Support is also significantly negatively correlated with the score of Internalizing Problems (r = -.302, p<.01). Good affect control and family support can reduce various emotional and behavioral problems. The results of the study found the resilience level can negatively affect internalizing problem behaviors and externalizing problem behaviors. The results are promising and can give clues for preventing and promoting measures regarding mental health issues to both family and school education contexts, as creating a sustainable development strategy of improving adolescents’ mental resilience quality
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; psychopathology; resilience; secondary students

EXPLORING COOPERATIVE LEARNING IN PROMOTING EQUITY, INCLUSION, AND COLLABORATION IN INCLUSIVE CLASSROOMS: A CASE STUDY - Loi, Man Hong (University of Saint Joseph, 2024)
This study presents a case study that explores teachers’ perspectives on the role of cooperative learning as a pedagogical approach in promoting equity, inclusion, and collaboration within inclusive classrooms. Additionally, it identifies both the perceived benefits and challenges associated with its application. The researcher sought data from primary school teachers in one inclusive school in Macau and employed in-depth semi-structured interviews. Twelve participants were involved in this qualitative study. The findings underscore the significant impact of cooperative learning in creating inclusive, engaging, and equitable educational environments, particularly for students with special educational needs. Overall, the participants viewed cooperative learning as a valuable pedagogical approach that fosters equity, interaction, student engagement, and collaboration in inclusive classroom settings. While cooperative learning presents several benefits in promoting an inclusive and equitable learning environment, the findings also reveal unique challenges that require careful management and adaptation by teachers. Some of these challenges include certain students dominating group work, difficulties in integrating students with different disabilities, and time management issues for effective cooperative learning implementation. Overall, the case study contributes valuable insights into to the complex dynamics of cooperative learning in mixed ability classes
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; cooperative learning; inclusion; inclusive education; inclusive practice

The Integration of Blockchain Technology in Accounting and Auditing - Almeida, Ermelinda Nazaré António de (University of Saint Joseph, 2024)
The emergence of blockchain technology in 2008 marked a significant milestone in the evolution of digital currencies, paving the way for the emergence of cryptocurrencies such as Bitcoin. Since then, blockchain has undergone four generations of development, expanding its applications across various sectors. In particular, the integration of blockchain into accounting and auditing practices has garnered significant attention due to its potential to transform traditional methods. However, there's a lack of clear understanding of how blockchain impacts traditional auditing practices and finance recordkeeping and the implications for audit quality. Significant challenges and uncertainties hinder its widespread adoption, including technical hurdles, regulatory complexities, and practical barriers. This dissertation aims to determine the transformative impact of blockchain technology on auditing practices and finance recordkeeping. In order to fully understand the impact of blockchain on auditing practices and finance recordkeeping, the dissertation utilizes a mixed sequential research approach that is divided into three phases. The first approach involves gathering qualitative data through interviews with blockchain experts. The second approach involves collecting secondary qualitative data through a systematic literature review to determine the changes that blockchain has brought to traditional auditing practices and finance recordkeeping. This is followed by a bibliometric analysis to identify current trends in blockchain research related to auditing practices and finance recordkeeping. The third approach involves gathering data through an online-focused survey distributed to finance and other industry professionals to determine the challenges organizations face in implementing blockchain technology in auditing practices and finance recordkeeping. Additionally, in phase three, case studies will be conducted based on the survey responses to examine the hindrances and challenges faced by organizations in implementing blockchain and its impact on auditing practices in different regions and among different demographic groups. As the findings indicate, Integrating blockchain technology into accounting and auditing practices can bring about significant improvements in transparency, efficiency, and fraud prevention. However, there are several challenges that must be overcome for successful implementation, such as technical difficulties, regulatory uncertainties, and privacy concerns. To overcome these hurdles, it is necessary to establish clear regulatory frameworks and innovative solutions. Although smart contracts offer automation, they also pose security risks that need to be addressed. Despite these challenges, blockchain has the potential to revolutionize auditing by enabling real-time auditing and enhancing integrity verification. To ensure audit quality, auditors must adapt to new responsibilities and stay up-to-date with emerging trends. Collaboration among stakeholders and continuous education and training programs are key to driving the successful adoption of blockchain technology
Keywords: Accounting; Audit Quality; Auditing Practices; Blockchain Technology; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

NATURAL HAZARDS AND THE ROLE OF MANGROVES AS A NATURE-BASED SOLUTION FOR COASTAL PROTECTION IN MACAO SAR - Lam, Sut Ieng (University of Saint Joseph, 2023)
The inundation problem in Macao is getting more attention recently, especially after the destructive impacts of typhoons Hato (2017) and Mangkut (2019). The inundation caused by storm surges is getting more severe with the rapid sea-level rise in Macao. Moreover, the potential threat of a tsunami in Macao, may be enhanced with rising sea-level. This research evaluated the risk of coastal hazards in Macao by analyzing the local meteorological data. The results of the analysis indicate a rising trend in the tropical cyclone intensity and more severe storm surges are expected to occur in the future. Moreover, this research explores the potential of Nature-based Solutions (NbS), particularly mangroves, to address the inundation problem in Macao. The study included a preliminary laboratory-based experiment and the application of local mangroves data in numerical models. The results of the experiment and numerical models demonstrate the ability of mangroves to attenuate waves. These findings, although preliminary, indicate that mangroves could be a promising NbS to address inundation issues in Macao. To effectively implement this NbS, further field investigations are needed to measure attenuation in-situ, as well as determine optimal locations for mangrove restoration projects
Keywords: Inundation; Mangroves; Master of Environmental Sciences and Management (MESM); Nature-based solutions; Sealevel rise; Storm surges; University of Saint Joseph; Wave attenuation

STRATEGIES FOR BUILDING A SMART TOURISM CITY: A CASE STUDY OF MACAO SAR AND THE PERCEPTION OF EXPERTS - Da Rosa Ho, Hoi Lam (University of Saint Joseph, 2024)
This dissertation explores the strategies for developing a smart tourism city in the background of Macao Special Administrative Region (SAR) and the perceptions of different experts in Macao. Awared that the Macao government aims to expedite the development of a livable, smart, and green Macao and requires smart technology to be applied to upgrade the people’s livelihood. This is a long-term ambition to achieve and whether success remains uncertain. Through literature review, understood that the traditional tourism industry must be transformed and innovated to enhance competition since the 90s. And smart tourism cities provide enhanced tourists’ experience and residents’ better quality of life. Although prior research have studied the tourist behavior of smart tourism contents or evalutated strategic plans for the construction of a smart tourism city, there is no previous research explored on the topic. Therefore, this dissertation through qualitative research methods including on-site observations, analyzing government-released documents and interviewing relevant experts. The findings present the seven components of the conceptual framework, including physical infrastructures, technology applications, experience sharing, big data, business co-creation, technical professionals, and cyber security, are strongly support the smart tourism city development in Macao. Provide a clear understanding for the relevant stakeholders to practice in a smart tourism city context. In addition, from the perspective of experts, the key for successfully develop Macao as a smart tourism city is that should apply ‘government-led, multi-party participation, and marketing operation’ in every component of the framework. The key for success depends on all stakeholders actively participae the activities. Four recommondations also present at the end of this disseartation. Prospects the development of smart tourism city in Macao can enhance both the quality of tourists’ experience and residents’ life as well as driven the long-term economic growth sustainably
Keywords: Smart Tourism City; Technology and tourism development; Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Teaching Portuguese and Patuá Languages at the University of Saint Joseph and its contribution to the Portuguese and Patuá languages in Macau - U, Elvino Agostinho (University of Saint Joseph, 2024)
This study analyses how to contribute to the Portuguese cultural language in Macau. Macau has a long Portuguese governing history, which has lasted for around 450 years and formed the Portuguese cultural heritage. One of the elements is Portuguese and Patuá languages, the languages the Macau residents used to speak. Since the Portuguese and Patuá cultural heritage influence happened, the Macau government has tried to preserve the Portuguese cultural language as much as possible. In Macau, the University of Saint Joseph is a part of the Portuguese and Patuá language contribution in conducting Portuguese programmes for students. This study aims to find out how to effectively promote the Portuguese and Patuá cultural language via the Macau education system and how to benefit the development of the Portuguese cultural language in Macau. To find out the efficient way of the Portuguese and Patuá cultural language contribution at the University of Saint Joseph, we applied snowball analysis to find the key interviewees to conduct face-to-face semi-structured interviews with six interviewees. The results show that the Portuguese and Patuá cultural languages are vital to the Macau education system, especially for students learning Portuguese. For students, learning Portuguese should be compulsory in Macau
Keywords: Audio-lingual method; Patuá drama; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph; cultural difference; cultural identity; learning Portuguese; reading-lingual method; translation theory

ASSESSING ADVERSE CHILDHOOD EXPERIENCE (ACEs) IN CHILDHOOD AND ADOLESCENT: TRANSLATION AND ADAPTATION OF ITEM-CA FOR CHINESE POPULATION IN MACAO - Lo, Antonio Man Ho (University of Saint Joseph, 2024)
Adverse Childhood Experiences (ACEs) are common in life trajectories, and continued exposure to childhood adversities has long-term consequences that can lead to lifelong physical, mental, and emotional deficiencies. This study aims to address the research gap in the ACEs context in Macao by enhancing our understanding of the cultural sensitivity, applicability, and acceptability associated with assessing ACEs among Chinese childhood and adolescents in Macao. The study utilized the Chinese version of The International Trauma Exposure Measure – Children and Adolescents (ITEM-CA) to facilitate the exploration of cultural adaptation needs related to ACEs measurement tools in Macao. Employing a qualitative methodology with an explanatory and descriptive design, the study collected opinions and suggestions through an online questionnaire from professionals working with children aged 7-17 years old, as well as parents or caregivers of children within the same age group. Several key findings emerged from the study. Firstly, it underscored the adequacy and pertinence of the Chinese ITEM-CA in covering the topics of traumatic events and deeming it more suitable for children aged 12 or above. Secondly, it emphasized the importance of maintaining anonymity and the involvement of dedicated and trained personnel throughout the ACEs assessment process. Lastly, it highlighted the need to increase public awareness regarding traumatic events and ACEs in Macao society. These findings have significant implications for researchers studying the prevalence of ACEs in Macao and for policymakers in Macao implementing ACEs surveillance. Additionally, there is a recommendation for organization, especially schools, to respond to ACEs using trauma-informed approaches, supporting the well-being of children, fostering resilience, and minimizing the risk of re-traumatization
Keywords: ACEs; Adolescent; Adverse Childhood Experiences; Chinese; ITEM-CA; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

GOVERNMENT PUBLIC RELATIONS STRATEGIES IN MACAU: A STUDY ABOUT THE TOURISM PROMOTION - Nip, Si Man (University of Saint Joseph, 2024)
I have met many friendly and patient professors and classmates during my two years of university. I would like to take this opportunity to thank them for the support and encouragement when I encountered difficulties, also professors detailed sharing and explanations in my learning and growing. Taking classes with my job at the same time is a very challenging task, especially in the thesis writing stage, it is difficult to manage the time allocation as well as concentration on thesis writing, and I even had the thoughts of giving up for a few times, but I am very thankful to my supervisor for his continuous support and encouragement during the thesis writing period, and for his attentive guidance whenever I have confusion during the time, he has provided me with a lot of practical and valuable advice, which inspired me a lot. In addition, I would like to thank those who helped me to complete the questionnaire survey. Without their help, I believe it would have been difficult for me to collect enough questionnaires. I would also like to take this opportunity to thank the two interviewees who agreed to be interviewed, as it is a difficult task to conduct interviews as a student in Macau. I would like to thank both for their support of the academic research, and the experience that they shared with us is very important to this study. Last but not least, I would like to thank my family, friends, and colleagues for always providing me with positive support, listening to my concerns, and helping me to overcome difficulties one after another. Once again, I would like to thank all those people who have helped me to complete my thesis
Keywords: Government public relations; Public relation in Macau; Public relation strategies; Public relations; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

COMPARATIVE STUDY ON HOW CORPORATE COMMUNICATION AND MEDIA CHANGE THE WAY ENTERPRISES CONVEY MESSAGES TO AUDIENCES DURING THE PANDEMIC PERIOD AND THE POST-PANDEMIC ERA. CASE STUDY: SJM RESORTS MACAU - Chan, Hoi Man; Simões, José Manuel; Monereo, Zita Carmen (University of Saint Joseph, 2024)
This research study explores the corporate communication strategies and media shifts adopted by large enterprises in Macau during the COVID-19 pandemic and post-pandemic era. Taking SJM Resorts, a large enterprise roots in Macau for over 60 years, as an example to analyze the shift and changes in its corporate communication practices and media usage during the pandemic and post-pandemic era. Moreover, recent literatures on related topic were reviewed to support this research. The researcher invited eight leaders from the case study to conduct semi-structured interviews for qualitative analysis, whilst to distribute 500 e-questionnaire surveys to public for collecting empirical data for quantitative analysis. Issues such as the proportion of offline and online media usage and corporate communication and media strategies and impacts were raised. The study result provides theory and practice reviews for related academic fields. Since there are relatively few research reviews on enterprises’ corporate communication and media landscape during the pandemic and the post-pandemic era at recent stage, this study can fill this gap, provide new research results to the related field as well as enrich the current literature database in related fields
Keywords: Brand marketing; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph; corporate communication; digital marketing; offline media; online media

The Financial Valuation of Chevron Corporation - Chenda, Elisa Francisco; Lao-Phillips, Jenny Oliveros (University of Saint Joseph, 2024)
Chevron Corporation (CVX) is one of the world’s largest energy companies, which operates across the entire Oil and Gas industry, including exploration and production as an Upstream operation and refining and marketing as a Downstream operation. Chevron has a strong presence worldwide, with operations in North America, South America, Africa, Asia, and Europe, which includes more than 180 countries, where the US, in terms of production, represents 39.4% of the net oil-equivalent production in 2022. Its global presence, sustained by its competitive advantages, is challenged by its worldwide competitors, industry factors, and the economic environment. It is essential to understand the impact of such changes on the industry and the Company to accurately assess the intrinsic value of Chevron and its future positioning. To provide investors with helpful information, comparing the intrinsic value resulting from three valuation models with the Company's market share price as of December 31st, 2022, is essential
Keywords: Intrinsic value; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph; forecast; stock market price

Analysis of Cross-Cultural Consumer Perception Based on Multiple Physiological Monitoring Tools - Carvalho, Ana Catarina Line Henriques de (University of Saint Joseph, 2024)
As the world becomes more globalized, it is now more important than ever for brands and advertisers to find effective ways to engage with consumers of different cultural backgrounds. Developing marketing that targets people of different cultural backgrounds, or multicultural marketing, carries specific nuances and complexities that may make traditional methods fall short. With this being said, there is still a lack of studies that explore the correlation between consumer's cultural background and their overall brand perception. Neuromarketing has proven to be an effective tool to understanding consumer behavior, by utilizing neuroscience tools. To employ a more sophisticated and in-depth understanding of consumer perception, the current research study makes use of neuroscience tools and aims to study the influence of cultural background in brand perception, while in a controlled environment. Using physiological neuroscience tools, namely, facial expression analysis (FEA), electrodermal activity (EDA), and eye-tracking (ET), a total of thirty-eight individuals, with ages between 19 and 50 years old, from 12 different countries and regions, participated in this research study. Findings suggest that participants of different cultural backgrounds perceive multicultural commercials as more favorable than monocultural commercials. However, future research should be done with a larger sample size, as well as include a wider variety of commercials. Research would also benefit from adopting a statistical analysis to help determine the significance of the results obtained
Keywords: Consumer Behavior; Multicultural; Neuromarketing; Neuroscience; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph